Hierarchical FeCoP nanosheets array anchored on phenolic resin derived N-doped porous carbon as a high-efficiency bifunctional electrocatalyst for alkaline water splitting - Qin Wang; Jiaxin Pei; Xiaoya Wei; Yangyang Li; Hongxin Li; Jiangyong He; Bi Chen; Jian Li; Yu Meng; Long Yan (Fuel, 2027)

Transcription factor SlbZIP12 affects tomato shelf life by mediating the ethylene biosynthesis at postharvest stage - Abdul Karim Amin; Wenyi Zhu; Pengwei Li; Shi Shi; Mengru Qin; Yan He; Huizhen Zhang; Hong Yao; Shuqi Chen; Hamza Latif; Mohammad Yousof Soltani; Mahmood Hemat; et al. (Postharvest Biology and Technology, 2026)

A mechanism of interannual variations in summer moisture over the Tibetan Plateau from the perspective of Lagrangian pathways - Hongwen Liu; Wenshou Tian; Hao Wu; Li He; Hua Qin; Hongying Tian; Tao Wang (Atmospheric Research, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

A novel pathogenic synonymous DHCR7 variant unveiled by aberrant splicing in Smith-Lemli-Opitz syndrome - Yan Zhou; Qin Zhang; Quanze He; Guohua Yang; Haibo Li; Yu An (Human Genetics, 2026)

Investigation on optimization of hydrogen fuel cell ejector based on five-level spatially rotatable orthogonal test model - Yue Deng; Baiping He; Chao Li; Yaorui Shen; Boquan Qin; Jianqin Fu (Fuel, 2026)

Fabricating highly-dispersed W-O-Si structure via silanols modulation over WOx/SiO2 catalyst enables efficient olefin metathesis - Haoxuan Tan; Jianhao Jiao; Yun Zu; Qiang Li; Yucai Qin; Ye Yang; Kai He; Zhongxing Geng; Lijuan Song (Fuel, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Unraveling the aroma-producing mechanism of the xerophilic fungus Xerochrysium coryli via integrated transcriptomic and volatile metabolomic analysis - Zengye Yang; Weili Yang; Zhengchuan He; Jin Zhou; Chongde Wu; Yizhi Tang; Ruina Zhang; Jiayi Li; Yuhang Zou; Mingyue Zhang; Yanqing Qin; Yao Jin (Fungal Biology, 2026)

Asymmetric competition for non-structural carbohydrates regulates tiller mortality and spike formation in winter wheat under varied planting densities - Qin Fang; Xiaokang Lv; Hongguang Wang; Haoran Li; Jianning He; Dongxiao Li; Ruiqi Li (Field Crops Research, 2026)

Rationally tailoring defect levels in Prussian blue analogues for enhanced rubidium adsorption - Gan Li; Wanghai He; Qiang Li; Fei Xu; Jiazheng Qin; Ting Wang; Mingshan Yang; Xin Hu; Dahuan Liu (Desalination, 2026)

Cobalt nanoparticles-embedded wood-derived biochar as a peroxymonosulfate activator for wastewater purification - Piao Xu; Yangzhuo He; Wenyang Li; Lin Hu; Ziwei Wang; Hong Qin; Fuqi Wu; Ying Zeng; Shengyi Wu; Yuan Zhu (Chemical Engineering Journal, 2026)

Development of a monospecific monoclonal antibody and a homogeneous chemiluminescence immunoassay for selective detection of “stopped” lomefloxacin - Tong He; Danfeng Qin; Zizhe Li; Gelin Liu; Zhanhui Wang; Kai Wen; Yantong Pan (Analytica Chimica Acta, 2026)

Synergistic effects of biochar and probiotic fermentation agent on soil aggregate stability, carbon sequestration, and heavy metal(loid)s passivation in paddy fields - Keqi Zhao; Xue Yu; Xifeng Qin; Ruijie Li; Lin Luo; Xiaomei Yang; Liuqin He; Anwei Chen; Jiachao Zhang; Hongli Huang; Xichen Zhao (Agriculture, Ecosystems & Environment, 2026)

Synergistic analysis and vertical transport attribution of carbon monoxide surface concentrations and satellite column loadings over China - Shuo Wang; Jason Blake Cohen; Kai Qin; Luoyao Guan; Pravash Tiwari; Ye Feng; Xiaolu Li; Qin He; Zhengqiang Li; Cheng Fan; Dacheng Wang (Remote Sensing of Environment, 2026)

Revealing the effect of surface NaCl on the sintering mechanism in ash deposition process: Insights from a novel coupled kinetic-thermodynamic phase analysis method - Zhihao Chang; Jing Guo; Chong He; Yusen Li; Xiaoming Li; Yuhong Qin; Yuexing Wei (Journal of Environmental Chemical Engineering, 2026)

CFD analysis of operating parameters and machine learning-aided optimization of reactor performance in a polyethylene pyrolysis fluidized bed - Ling Qin; Lianyong Zhou; Zhongmei Li; He Lei; Li-Tao Zhu (Fuel, 2026)

Corrigendum to “Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China” [Food Res. Int. 242 (2026) 120014] - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Investigating flavor characteristics in orange juice from three new bud mutation varieties of longleaf orange using molecular sensory science - Yujiao Cheng; Tianpeng Xiao; Jiying Zhang; Guowei Hu; Tiangang Lei; Guohua Li; Kelin Du; Qin Long; Yongrui He; Jun Wang; Min Zhang; Linhua Huang (Food Chemistry, 2026)

PlCXCL12a differentially modulates SGIV and RGNNV replication during single and co-infection and regulates chemotaxis-associated immune responses - Jinpeng Chen; Shen Li; Yixiang Li; Yusheng Li; Xin He; Qiwei Qin; Min Yang (Fish & Shellfish Immunology, 2026)

Thermal-environment optimization towards lower HVAC energy and childhood respiratory incidence in Shanghai - Chanjuan Sun; Huiyun Wang; Yajing Luo; Qin Jia; He Li; Xin Zhou; Haidong Wang (Energy and Buildings, 2026)

Unravelling saltmarsh organic carbon sources: biomarker-isotopic integration for credible blue carbon accounting - Jinge Zhou; Hua He; Han Chen; Jingfan Zhang; Zhe Lu; Shuchai Gan; Guoming Qin; Lulu Zhang; Xingyun Huang; Neil Saintilan; Ding He; Yongxia Jia; et al. (CATENA, 2026)

Resuspension of droplet residues from medical protective clothing: Effects of material properties, surface roughness, and initial droplet size - Xian Li; Huibo Qin; Nan Zhang; Liangyu Zhu; Fan Liu; Junzhou He; Wei Hua; Shifeng Zhao; Lingjie Zeng (Building and Environment, 2026)

A dual-mode self-verification strategy based on the bimetallic ion amplification effect: Enabling highly sensitive detection of the chemotherapy-induced cardiac toxicity biomarkers IL-6 and MPO - Haiying He; Bolu Sun; Jiali Kang; Mian Chen; Chenyu Qin; Xiangdong Wang; Yuxin Dong; Jiaru Fu; Yaru Zhang; Yuqiong Wu; Huajie Li; Lin Yang; et al. (Analytica Chimica Acta, 2026)

Preparation and characterization of latex-poly(butadiene-maleic acid) coated open tubular silica columns for ion chromatography-A proof-of-concept study - Ge He; Miao Zhang; Haiyan Li; Shuchao Wu; Purnendu K. Dasgupta; Chuchu Qin; Weixiong Huang (Analytica Chimica Acta, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Investigation into effect of non-collinear current on regular and irregular waves using wave-current interaction basin experiments - Haoyu Li; Kai Wei; Yanchao He; Chunlin Du; Yongle Li; Shunquan Qin (Ocean Engineering, 2026)

Apatite fingerprints the magmatic-hydrothermal processes of the Wajilitag alkaline‑carbonatite complex, NW China - Li-Peng Qin; Wu-Bin Yang; Guo-Feng Xu; Pan Qu; He-Cai Niu (Lithos, 2026)

Dietary patterns reshape organ-specific biodistribution and toxicity upon exposure to polystyrene nanoplastics: Role of ROS-mediated intestinal senescence - Jie Dai; Tao Wu; Xialei Liu; Yijun Dong; Lan He; Peng Li; Jiamiao Qin; Sheng Wen; Lina Zhao (Journal of Hazardous Materials, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

Cohesion and interface dual-effect driven molecular lock adhesive by multiple dynamic covalent bonds - Jiajun Zhu; Qin Lu; Rimei Chen; Li Wang; Lingli Tian; Zhiping Chen; Yu Meng; Ziheng Zhang; Hui He (Chemical Engineering Journal, 2026)

Interrogating vascular determinants of repair: Biofabricated constructs for precision intervention in peripheral neuropathies - Mouyuan Sun; Shuangyang Li; Xuankai Fan; Yiqian Xu; Yaxian Luo; Luying Qin; Jingyu Zhang; Zhixu He; Lianjie Peng; Xinyi Feng; Tao Qiu; Tian Zhang; et al. (Chemical Engineering Journal, 2026)

Spring deep flooding reduces methane emissions from paddy soils through combined physical, carbon pool, and microbial functional mechanisms - Kui Li; Dengming Yan; Aohui Sun; Chanyuan Qin; Ziheng Pang; Zhiyong Liu; Jin Zhou; Jianping He; Kainan Xiang; Kai Zeng; Yelan Yu; Zeheng Li; et al. (CATENA, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

A self-supervised learning based method for fish disease diagnosis utilizing extremely limited samples - Zehui Liu; Shanshan Ye; Xuanzhi Li; Xianwu Luo; Jiaji Pan; Miaolei He; Wei Qin; Jun Xiao; Yaoyi Cai; Tiantian Shen; Yu Li; Hao Feng (Computers and Electronics in Agriculture, 2026)

High-level estrogen impairs memory via estrogen receptor signaling in a hypothalamic–hippocampal neural circuit - Xin Li; Nan Zang; Qianru Zhao; Yuxiang Sun; Udhaya Kumar Siva Kumar; Mengyu Hua; Wenjun Zhou; Yanyan Qi; Hu Chen; Longqing Xia; Jun Qin; Lei Sun; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Microbial carbon pump promotes refractory organic carbon accumulation in karst waters: Coupled responses of bacterial communities and dissolved organic matter under thermal stratification - Jia Qin; Xinlu Su; Yikun Jia; Peng Chen; Qiufang He; Wen Lai; Tao Zhang; Jianhong Li; Junbing Pu (Journal of Hydrology, 2026)

Gut dysbiosis and Escherichia coli-associated enrichment of antibiotic resistance genes in diarrheal yak calves - Ze Cao; Huanyu Gong; Huilin Qin; Ting Wei; Xiaoqiang He; Kairi Yang; Xiaowei Li; Yanwen Wang; Yunqiang Jia; Xi Lan; Wen He; Xiaoping Jing; et al. (Journal of Hazardous Materials, 2026)

Targeted domestication of Enterobacter-dominated consortia for enhanced uranium immobilization via phosphate-mediated biomineralization - Jinxin Li; Jianhong Ma; Guicheng He; Qinglin Zhang; Han Qin; De Li; Rui Wang; Wei Zhang; Hui Zhang; Yongdong Wang; Feng Li; Yongmei Li (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Motion consistency-guided spatiotemporal learning: a robust framework for low-altitude infrared object detection - Leiyang Zhong; Liyue Yan; Tian Qin; Mengying Wu; Dejin Zhang; Li He; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Resilient bioconversion of nitrite-rich organic wastes by black soldier fly larvae: Detoxification mechanisms and microbiome-mediated nitrogen cycling - Chaowei Qin; Mengjun Long; Jiabao Chen; Dan Shao; Shanshan Zhao; Long Chen; Zhenyu Zhang; Lijun Duan; Huan He; Juan Cortes Ortiz; Hui Wei; Qing Li; et al. (International Biodeterioration & Biodegradation, 2026)

Integrated mechanism of arsenic retention by carbon structure and lattice oxygen during temperature-driven Shenmu coal gasification with sewage sludge addition - Yujia Du; Shugang Guo; Hugang Li; Yuhong Qin; Xiaofeng Liu; Tingrui Shi; Haofei Li; Wanyao Li; Qizhi Guo; Yuexing Wei; Chong He; Stanislav V. Vassilev (Fuel, 2026)

EcPSMB9 contributes to antiviral responses through autophagy-related and MHC I-associated processes and associates with EcPSMB8 in grouper - Jinpeng Chen; Xin He; Shen Li; Yuhui He; Shina Wei; Yun Sun; Qiwei Qin; Min Yang (Fish & Shellfish Immunology, 2026)

Microcystin-LR disrupts gut metabolic homeostasis through microbiota–metabolite axis remodeling in grass carp - Lixin Ma; Junyuan Tan; Xiaomin Zheng; Zhuojin He; Zhendong Qin; Li Lin; Fei Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Na-rich Na3.2V1.9Fe0.1O2(PO4)2F cathode unlocks high energy density and wide-temperature operation in sodium-ion batteries - Qiang Fu; Qin He; Fangxiang Song; Keliang Wang; Jing Li; Xianquan Ao; Rong Li (Chemical Engineering Journal, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Iodine vacancy-engineered BiOI steering selective singlet oxygen generation for high-flux antibiotic degradation with peroxyacetic acid activation - Yuchen Chu; Ting Zhou; Yuxi Zeng; Siying He; Jiawei Yue; Wenjun Wang; Yang Yang; Ziwei Wang; Fanzhi Qin; Hongda Liu; Xiaoming Li; Jie Liang; et al. (Chemical Engineering Journal, 2026)

Dually enhanced methylcellulose conductive gel with self-healing, stretchability and anti-swelling for wearable microstructured triboelectric nanogenerator - Chenyu Li; Can Yang; Jingting Chen; Zimo Qin; Yue Xiao; Wenjie He; Shuzheng Liu; Gang Qin; Jia Yang; Qiang Chen (Chemical Engineering Journal, 2026)

Enhanced vegetation activity leads to a significant increase in riverine particulate organic carbon concentrations in China - Mengze Qin; Mingxu Li; Lingli Yu; Yinghua Zhang; Xiaoyan Kang; Boming Liang; Jiankun Chen; Youbin Deng; Xuanbo Wang; Xuyang Zhang; Yijia Li; Jie Li; et al. (CATENA, 2026)

An Interpretable Machine Learning Model for Predicting the Presence of Talaromycosis in HIV Patients Lacking Skin Lesions - Jiaguang Hu; Wenming He; Qun Tian; Yanqiu Lu; Peng Zhang; Jinyu Qin; Chuan Qin; Ying Wu; Cheng Huang; Xu Li; Luhuai Feng; Linghua Li; et al. (Mycopathologia, 2026)
Introduction The existing predictive models for talaromycosis in people living with HIV without skin lesions are limited by established risk factors and traditional statistical approaches. This study aims to develop an interpretable machine learning(ML) model for predicting the presence of talaromycosis in HIV patients without skin lesions and to validate its clinical applicability. Methods This retrospective multicenter study involved the analysis of electronic medical records from four tertiary hospitals in China, covering the period from 2010 to 2019. The training dataset comprised 1009 HIV patients with opportunistic infections, while external validation was conducted using data from 305 patients at an independent center. From an initial set of 36 variables, twelve key features were selected, including albumin, absolute lymphocyte count, hemoglobin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST/ALT ratio, C-reactive protein, white blood cell count, platelet count, peripheral or abdominal lymphadenopathy, CD4 + T-cell count, and age. Five ML algorithms were evaluated using tenfold cross-validation. Model performance was measured using the AUC, ACC, and F1-score. Calibration curves and decision curve analysis (DCA) were employed to assess the model’s reliability and clinical net benefit. The optimal model was subsequently implemented as a web-based tool. Results The Support Vector Machine (SVM) exhibited superior performance compared to other models, achieving an AUC of 0.809 (95% CI 0.778–0.838), an ACC of 0.714, and an F1-score of 0.689. External validation demonstrated enhanced performance metrics, with an AUC of 0.921 (95% CI 0.889–0.951), ACC of 0.853, and an F1-score of 0.819. DCA indicated a significant net clinical benefit across various risk thresholds, and calibration curves showed strong concordance between predicted and observed risks. Conclusion The interpretable SVM model effectively stratifies the risk of talaromycosis in people living with HIV without skin lesions in endemic regions, aligning with WHO recommendations for early diagnosis and treatment of priority fungal pathogens. Its integration into a web-based tool enhances clinical accessibility for early intervention in resource-constrained settings.

Network Pharmacology and Experimental Validation Reveal Wu Miao Pill’s Therapeutic Effects on Acute Gouty Arthritis Through P2X7R Regulation - Wei-qin Gao; Xue-zhong Gong; Cen Chang; Li Li; Yang-yi Gu; Dong-yi He (Biochemical Genetics, 2026)

Cytotoxic properties of pentacyclic triterpenes isolated from the flowers of Rhododendron pachypodum - Jie Luan; Yang Liu; Yu Zhang; Ying Wang; Qin Song; Bing Chen; Gaohong Zhang; Jiangbo He; Xian Li (Natural Product Research, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Scavenger receptor B1 modulates antimicrobial peptide expression and cellular immunity against bacterial infection in Ostrinia furnacalis - Zhaoyang Han; He Zhang; Yulin Liu; Yanzhe Qi; Zupeng Gao; Qin Lu; Shuzhong Li; Honglun Bi; Congjing Feng (Journal of Invertebrate Pathology, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Investigating key free radical reactions and their impact mechanisms during coal spontaneous combustion - Junjie Qin; Lanjun Zhang; Xuyao Qi; Jinhu Li; Yang Wu; Yibo Zhao; Wenjing He; Ming Xia; Ying Wang (Fuel, 2026)

A web-based platform for real-time stewed beef freshness monitoring: Integrating anthocyanin colorimetric film with deep learning - Ning He; Zhihan Zheng; Yiqun Zhang; Tengfei Wang; Yingying Dong; Xiaodong Li; Yuchen Qin; Dan Zheng; YingChun Zhu (Food Chemistry, 2026)

Nε-(carboxymethyl)-L-lysine exacerbates renal lipotoxicity via RAGE/AMPK-mediated renal tubular lipophagy impairment in diabetic mice - Yijun Dong; Peng Li; Jie Dai; Jiamiao Qin; Lan He; Tao Wu; Xialei Liu; Zhenhuan Zhao; Lina Zhao (Food Bioscience, 2026)

Multiscale transport mechanisms and spatial heterogeneity in sound-field-enhanced fluidized-bed CaO/CaCO₃ thermal energy storage processes - Shengnan Yan; Hongteng Wu; Liangsheng He; Yue Zhao; Haigang Wen; Zhenggui Li; Xiaobing Liu; Qin Zhao (Chemical Engineering Journal, 2026)

Electronic tuning of δ-MnO2 via interlayer Ag+ for efficient ozone decomposition under humid conditions - Ting Li; Zhongyu Wang; Xinyao Lei; Yuyan He; Minghao Shi; Mingjia Zhang; Shule Zhang; Qin Zhong (Chemical Engineering Journal, 2026)

Lithium recovery from clay lithium deposits using ammonium persulfate: Process and mechanism study - Zhixiang Li; Luxiang Ma; Weiqing Lai; Jiacheng Li; Chunxi Hai; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Yuan Zhou; Xiwei Qin; Yuliang Ma (Chemical Engineering Journal, 2026)

Direct recovery of silver and simultaneous purification of silicon from end-of-life photovoltaic modules via a one-step hydrothermal method - Danyan Qin; Kai Zhang; Shihao He; Xian Xie; Jie Liu; Long Peng; Yingzhu Li; Di Wu; Yaokai Zhong; Yun Shen; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

GmENDO-like 1, a structurally divergent homolog of S1/P1-type endonuclease, modulates the vegetative-to-reproductive phase transition in soybean - Qinshan Gong; Hongxia Liu; Qin Nie; Jiahui Tong; Wenjing Li; Myonghwa PAK; Yuanyuan Mei; Kaixuan He; Dan Wang; Ning Ning Wang (Plant Cell Reports, 2026)

Reactive OPCs in CNS Injury: From Functional Diversity to Therapeutic Translation - Shengnan Wang; Hong Liu; Jiali Li; Yimin Yuan; Ziwei Dai; Zhida Lan; Chao Huang; Xiaojie Wei; Cheng He; Zhida Su; Shangyao Qin (Neuroscience Bulletin, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

Corrigendum to “Organic fertilizer application enhances soil multifunctionality and yield of upland high-quality rice and reshapes potential microbial ecological networks” [Appl. Soil Ecol. 223 (2026) 107046] - Xiaqing Xu; Xiahong He; Yingfen Qin; Shu Wang; Jianqiang Li; Ping Xiang; Qiliang Yang; Yunfei Tuo (Applied Soil Ecology, 2026)

Spring deep flooding alters patterns of nitrogen pool allocation and microbial functional potential in paddy soils - Kui Li; Aohui Sun; Chanyuan Qin; Ziheng Pang; Zhiyong Liu; Jin Zhou; Jianping He; Yingying Ye; Kai Zeng; Yelan Yu; Hua Wang (Applied Soil Ecology, 2026)

Organic fertilizer application enhances soil multifunctionality and yield of upland high-quality rice and reshapes potential microbial ecological networks - Xiaqing Xu; Xiahong He; Yingfen Qin; Shu Wang; Jianqiang Li; Ping Xiang; Qiliang Yang; Yunfei Tuo (Applied Soil Ecology, 2026)

USP9X regulates copper-induced CASP9/CASP3/GSDME-dependent pyroptosis by deubiquitinating JAK1 - Huaduan Zi; Hengcheng Tang; Xiaoxi Yang; Xiaojin Li; Yanmeng Li; Anjian Xu; Qin Ouyang; Sisi Chen; Pingping He; Yanling Li; Qianyu Zhu; Bei Zhang; et al. (Apoptosis, 2026)

Environmental nutrients and tissue non‐structural carbohydrate storage jointly drive spatial flowering patterns of seagrass - Gaoquan He; Liuyuan Zou; Le‐Zheng Qin; Wen Li; Jie Wang (Limnology and Oceanography, 2026)
Sexual reproduction is a cornerstone for sustaining the resilience of seagrass meadows, which are globally threatened by anthropogenic nutrient loading in coastal waters. However, how environmental nutrients regulate seagrass flowering remains poorly understood. To fill this knowledge gap, we surveyed 13 seagrass meadows across three regions along the eastern coast of Hainan Island in the South China Sea. This study aimed to investigate the direct and indirect effects of inorganic nutrients (i.e., water column and sediment porewater) on the flowering traits (i.e., flowering frequency and flowering intensity) of the seagrass Enhalus acoroides . Our results revealed contrasting effects of inorganic nutrients on seagrass flowering. Specifically, water column ammonium persistently inhibited flowering, whereas water column phosphate promoted flowering with an optimal threshold concentration of ~ 2.9 μ mol/L. In contrast, sediment porewater nitrate + nitrite promoted seagrass flowering at concentrations above ~ 1.5 μ mol/L, whereas water column nitrate + nitrite favored flowering at concentrations below ~ 2.5 μ mol/L. Partial least squares path model revealed that inorganic nutrients had strong direct effects on seagrass flowering (|mean standardized effect| = 0.30–0.65) and indirect effects (|mean standardized effect| = 0.40–1.00) mediated through enhanced positive influences of belowground traits (i.e., non‐structural carbohydrate [NSC] storage, C%, and biomass) and intensified negative influences of aboveground traits (i.e., NSC storage, C%, and biomass) on flowering. These findings elucidate the cascading regulatory pathways through which inorganic nutrients affect seagrass flowering and underscore the urgent need for targeted ambient nutrient monitoring to enhance the sexual recovery potential of seagrass meadows under ongoing environmental change.

EcPSMB8 Contributes to Antiviral Immunity in Grouper by Modulating MHC I Signalling and Virus‐Induced Autophagy - Jinpeng Chen; Xin He; Bangsong Meng; Min Guo; Shen Li; Shina Wei; Qiwei Qin; Min Yang (Journal of Fish Diseases, 2026)
The PSMB8 gene belongs to the immunoproteasome β‐subunit (PSMB) family and has been implicated in diverse physiological processes in mammals, including tumorigenesis, autophagy and apoptosis. However, its role in antiviral immunity in groupers remains largely unexplored. In this study, we cloned and characterised EcPSMB8, a homologue of PSMB8, from the orange‐spotted grouper ( Epinephelus coioides ), and investigated its potential involvement in antiviral immune responses. EcPSMB8 encodes a conserved 275‐amino‐acid protein that is ubiquitously expressed in grouper tissues and predominantly localised in the cytoplasm. Functional analyses showed that EcPSMB8 overexpression was associated with reduced replication of both Singapore grouper iridovirus (SGIV) and red‐spotted grouper nervous necrosis virus (RGNNV). This antiviral effect was accompanied by suppression of basal and virus‐induced autophagy, as indicated by decreased LC3‐II accumulation and reduced expression of autophagy‐related genes. Meanwhile, EcPSMB8 overexpression correlated with enhanced major histocompatibility complex class I (MHC I)‐associated immune signalling, including increased promoter activities of MHC I‐A, ISRE and IFN3, as well as upregulation of related cytokines. Together, these findings suggest that EcPSMB8 may contribute to grouper antiviral defence through coordinated modulation of immune signalling and autophagy. Importantly, a specific polyclonal antibody against EcPSMB8 was generated, providing a useful tool for protein‐level analyses and supporting future studies on antiviral immune mechanisms in teleost fish.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Congenital tuberculosis transmitted via the placenta: identification by metagenomic next-generation sequencing - Xingchen Gao; Ruiqi Qin; Shengjin Li; Yanli Yang; Jing He (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Effects of Simulated Tunnel Darkness on Histology of Schizothorax macropogon - Yanlin Wei; Hongze Li; Junjie Huang; Wei Liu; Jianguang Qin; Jianzhang Lv; Tao He (Fishes, 2026)
Schizothorax macropogon is an endemic fish species of the Tibetan Plateau whose distribution largely overlaps with hydropower facilities. In this study, the fish were exposed to simulated tunnel darkness for 7 days to evaluate microstructural changes in the gills, dorsal muscle, and midgut. The results showed that gill lamellae exhibited divergent trends with continued bending and shortening in the dark group, contrasting with rupture in the control group. Moreover, the number of mitochondria-rich cells in the dark group increased initially and then decreased, while remaining stable and evenly distributed in the control group. No significant pathological damage was observed in the skeletal muscles of both groups, and muscle fiber diameters displayed a “V”-shaped trend over time in both groups. However, muscle fiber diameters were significantly smaller in the dark group than in the control group. Furthermore, intestinal villus height decreased continuously over time in both groups, with goblet cell numbers initially rising before falling and consistently remaining lower in the dark group compared to the control group. These findings suggest that short-term exposure to darkness may disrupt circadian rhythms, induce behavioral anomalies and energy metabolism disorders, leading to microstructural alterations in gill, muscle, and intestinal tissues that reflect either adaptation or damage. This study provides histological insights into the physiological effects of tunnel darkness on fish and offers key scientific evidence for optimizing lighting conditions in plateau tunnel fishways.

10-Gingerol induces ferroptosis via TFEB-mediated NRF2 lysosomal degradation in NSCLC - Siying Li; Kaihua Shi; Lei Huang; Ziqing Li; Zhuo Qin; Yanan Sun; Caifang Qin; Chunmei Wang; He Li; Jinghui Sun; Wei Liu; Jiping Wu; et al. (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Bioactive coumarins and chromones with anti-neuroinflammatory effect from Gerbera piloselloides - Cong Zhang; Kuan Lin; Qing-Qin He; Hao Gong; Li-Juan Hu; Mei Zhou; Shi Chen; Wei Liu; Xian-Sheng Ye; Xi-Ji Shu (Phytochemistry Letters, 2026)

Coastal fronts influence the formation and migration of middle-to-late Holocene mud depocenters on the inner shelf of the East China Sea: Insights from a diol index - Lilei Chen; Jiandong Qiu; Jian Liu; Yoshiki Saito; Feng Li; Xiaoyong Duan; Bin Chen; Xingliang He; Maogang Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Robust prediction of CO2 absorption in blended amines via structure-concentration integration: A machine learning approach for imbalanced and data-scarce systems - Binmin Li; Tengxian Qin; Zehua Xu; Zhi Yang; Guiyang Ye; Jiaoying Huang; Yuanting Qiao; Xuelan Zeng; Song He; Yawen Zheng; Junyao Wang (Journal of Environmental Chemical Engineering, 2026)

Multi-role synergistic effects and mechanisms of M. verticillatum in regulating the coupled cycling of Fe-Mn-N-P in lake sediments - Yingying Qin; Weifang Huang; Xianyou He; Longguo Li; Naiwen Li; Bo Lai (Journal of Environmental Management, 2026)

An experimental study on the ignition and combustion characteristics of ultrafine boron particles - Ruining He; Xin Bai; Xuan Ren; Yilin Zhao; Xin Wang; Jinhu Liang; Fei Qin; Ce Sun; Taufiq Yap Yun Hin; Chong-Wen Zhou; Henry J Curran; Yang Li (Fuel, 2026)

Integration of single-cell RNA sequencing and untargeted metabolomics reveals the metabolic regulatory mechanism of theabrownin intervention on the liver of high-fat diet mice - Li Cailin; He Zhigui; Qin Shaowei; Sam Al-Dalali; Liu Zhengquan; Liang Jin (Food Bioscience, 2026)

Carbonate aquifer promoting a diverse and carbon-active aquatic habitats in a subtropical river system - Ligeng He; Guanghui Jiang; Jianming Qin; Zhaoyi Li; Fang Guo (Environmental Research, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Microcystis aeruginosa-driven acute toxicity compromises immune–metabolic regulation and hepatocyte integrity in grass carp - Lixin Ma; Junyuan Tan; Xiaomin Zheng; Zhuojin He; Zhendong Qin; Li Lin; Fei Shi (Environmental Pollution, 2026)

Reinforced clusteroluminescent cellulose nanospheres by strengthening hydrogen bonds networks - Yu Meng; Qin Lu; Yangbing Wen; Zhiping Chen; Rimei Chen; Lingli Tian; Li Wang; Jiajun Zhu; Hui He (Carbohydrate Polymers, 2026)

Spartina alterniflora invasion enhances soil priming effect by altering carbon use efficiency - Xingli Li; Xiuwei Zhang; Jun-Qin Gao; Mai-He Li; Josep Peñuelas; Jordi Sardans; Qianwei Li; Minghua Song; Chen Liang; Huabing Liu; Jiatao Zhu; Fei-Hai Yu (CATENA, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Quartz compositions decipher the source and magmatic-hydrothermal evolution of Himalayan LCT-type pegmatites - Yong-Neng Zhao; Jun-Xing Zhao; Noreen J. Evans; Chang-Tong He; Rui-Zhe Shi; Shen Gao; Li-Qun Zhu; Ke-Zhang Qin; Ming-Jian Cao (Mineralium Deposita, 2026)

Two new diterpenoid alkaloids from Aconitum legendrei Hand.-Mazz - Ming-Lu Zheng; Feng-Tai Qiu; Qing Tang; Lin Chen; Qin He; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

An automated vertebral heart scale measurement tool based on deep learning: Facilitating screening for prevention of canine cardiomegaly - Jing Chang; Rui Qin; Huijie Jiang; Jinfan Wei; Haotian Gong; Shijun Li; He Gong; Shuang Zhang (Preventive Veterinary Medicine, 2026)

A win-win recycling strategy for spent lithium-ion batteries: Prioritized selective lithium extraction afterwards triggers intrinsic catalysis - Yifan Sui; Zeqiu Chen; Yue Chang; Yaoguang Guo; Jie Guan; Xuning Zhuang; Fei He; Zhenming Zhang; Weihua Gu; Qianqian Chen; Li Fan; Qin Xu; et al. (Journal of Hazardous Materials, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Multi-scale geographical origin discrimination of geographical indication rice based on multi-source data fusion combined with machine learning: A case of Panjin rice - Qin Wang; Yangyang Lu; Changyan Zhou; Xiaobei Li; Xujiao Li; Zhiyong Zhao; Xiangwei He; Xiaoyan Zhao; Yanmei Zhang (Food Research International, 2026)

Natural polyphenols in the treatment of IBD: pathological intervention activities and delivery system constructions - Yi Zhang; Yi Chen; Yuyu Zhang; Qi Zhang; Lijuan Wang; Qingmei Liu; Liping Chen; Qin Dong; Yihao Wen; Ziyou He; Yawen Hu; Yuxin He; et al. (Food Research International, 2026)

Fluorination-induced nucleation and crystallization in uniaxially oriented polypropylene film - Wenxuan Li; Yuan Zhang; Shuangjing Zhou; Ba Qin; Weichen He; Chunjiu Li; Chenchen Xia; Honghong Gong; Zhicheng Zhang (Chemical Engineering Journal, 2026)

A vacancy-engineered Ce-doped NiCo-LDH electrode material for efficient, selective, and stable groundwater defluorination in FCDI systems - Xingtian Wang; Xinyue Jiang; Pengcheng Tang; Junfeng Zhu; Yuwen Wang; Huiqin Li; Dan He; Yuxuan Ma; Yuhan Qin; Boping Ren; Xiaojing Wang (Chemical Engineering Journal, 2026)

Sustainable furan-based polymers driven by bicyclic rigidity: From renewable monomers to high-performance materials - Yanxin Zhang; Xiaoru Quan; Qin Liu; Dege Li; Xin Yuan; Shuangfei Zhao; Yirong Feng; Wei He; Kai Guo (Chemical Engineering Journal, 2026)

Dual mechanism of electrochemical regulation to reduce soil Nitrous Oxide emissions-microbial recruitment and electron transfer pathway optimization - Yufeng Li; Lunalan Kang; Xiangyang Qin; Ren Fei; Anxiang Lu; He Qishuang (Bioresource Technology, 2026)

Overt physiological responses and atypical behavior evoked in adult zebrafish in the novel tank test by two acute ‘survival’ stressors - Yunzhe Song; Jiahao Cui; Huiling Cai; Yunqian Zhang; Yixin Qin; Zhaowen Zhou; Haoyu Feng; Shulei He; Kai He; Yucheng Liu; Jiyi Wang; Jiayou Jiang; et al. (Behavioural Processes, 2026)

Metagenomic insights into the effects of tillage regime and branch-pruning mulch on soil carbon cycling and microbial function in apple orchards - Xiuli Li; Deguo Lyu; Ze Tao; Lijie Li; Jiali He; Sijun Qin (Plant and Soil, 2026)

Determinants of the variability of PGPB effects on zinc biofortification and crop yield: a meta-analysis - Hua He; Lu Peng; Jinzhi Liu; Fangchi Yang; Xiu Li; Qin Lan; Xiaoyan Tang; Yanyan Zhang; Bing Li; Changquan Wang; Yingjie Wu (Plant and Soil, 2026)

Synthesis and antihepatoma activity of dimeric 1-O-acetylbritannilactone derivatives - Guang-Xuan Du; Li-Qin He; Meng-Xiang Qin; Yun-Bao Ma; Xiao-Yan Huang; Yong-Cui Wang; Tian-Ze Li; Ji-Jun Chen (Medicinal Chemistry Research, 2026)

Gut microbiota-tryptophan-serotonin axis drives anxiety-like behavior via NLRP3-mediated neuronal pyroptosis in the medial prefrontal cortex - Guiqiang Zhou; Xing Wang; Tongzhou Qin; Ling Guo; Jiajin Lin; Zhaowen Zhang; Peng Gao; Yan Zhou; Wei He; Jing Li; Guirong Ding (Apoptosis, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Correction: Water-soluble platinum(II)-porphyrin based on oxygen response for cell hypoxia imaging - Meng-Yan Chai; Yu-Li Dang; He Qin; Li-Xia Xie; Xin Zheng; Lijie Liu; Guoxing Liu; Yu-Qiang Xiang; Cao-Yuan Niu; Sheng-Qiang Guo (Molecular Diversity, 2026)

Secondary metabolites from the endophytic fungus Hypoxylon sp. HK-37 derived from Aquilaria sinensis - Zheng-Zhuo Ren; Kai-Lei He; Fei Wu; Li Yang; Jing-Zhe Yuan; Ze-Sheng Li; Hao-Fu Dai; Wen-Jian Zuo; Hui-Qin Chen (Phytochemistry Letters, 2026)

Nickel(II)-induced charge separation modulating in Ni-coordinated covalent organic framework for boosting dual-pathway hydrogen peroxide production - Qinfeng Rong; Junxia Qin; Shuying Li; Zhiling Huang; Sijing He (Journal of Environmental Chemical Engineering, 2026)

Depth-specific mechanisms regulate phosphorus cycling in dryland soils under long-term precipitation change - Huijun Qin; Mingzhu He; Jing Zhou; Chunming Xin; Shengzhong Du; Chengyi Li; Guojun Han (Journal of Environmental Management, 2026)

Efficient pollutant removal by iron-carbon bioretention system in long-term operation: Stability and performance - Zhou Jianqiang; Song Xichen; Wang Xiaojuan; He Jiangtao; Zhou Yawen; Qin Jie; Xiao Yifei; Gao Suxia; Li Hua; Liu Jianlin; Li Wei; Cao Lianbao; et al. (Journal of Environmental Chemical Engineering, 2026)

Pulsed ultrasound-assisted deep eutectic solvent-mediated stabilization and bioactivity enhancement of hydrolysable tannins from chestnut (Castanea mollissima) burrs - Xingying Xue; Zhiwen Qi; Hao Zhou; Ran Tao; Wenjun Li; Qin He; Jiandu Lei; Chengzhang Wang (Food Research International, 2026)

Effect of molecular weight and protein content on the interfacial activity of soybean soluble polysaccharides - Yujian Li; Zhan Bao; Siyi Gu; Zhaojun Wang; Maomao Zeng; Zhiyong He; Qiuming Chen; Fang Qin; Jie Chen (Food Hydrocolloids, 2026)

Integrated HTO@fiber interfacial evaporator for concurrent photovoltaic cooling, lithium extraction, and desalination - Qihao He; Yang Xiao; Da Li; Guangzhao Qin; Xiong Zheng (Desalination, 2026)

4-hydroxybenzoic acid-assisted formic acid preserves lignin structure during efficient hemicellulose removal in bamboo biorefinery - Weidong Li; Hanwen Ge; Sen Ma; Lei Liu; Lin Luo; Zihao Qin; Aiyong He; Chao Wang; Xianhai Zeng (Chemical Engineering Journal, 2026)

High-density microfluidic Chip (HD-μChip) for multiplex detection in miniaturized immunoassays - Yiran He; Min Wang; Zhaoxu Luo; Xiaodong Ma; Min Jiang; Yanhua Chen; Jingyi Qin; Yayun Gu; Xin Li; Ying Shi; Hong Wang; Ye Shen; et al. (Chemical Engineering Journal, 2026)

Construction of recombinant Lactococcus lactis expressing VP1 from duck hepatitis a virus types 1 and 3 and evaluation of its immune effect - Yafei Qin; Yaru Fan; Meijuan Zhang; Saisai Zhao; Xinhong Man; Dalin He; Youxiang Diao; Junxun Li; Jingdong Hu; Yi Tang (Veterinary Research Communications, 2026)

Myricetin alleviates myocardial infarction-induced cardiac fibrosis in mice by upregulating SIRT1 to inhibit TGF-β1/Smad2/3 signaling - Xiaojv Xiong; Rui Dai; Guangji Wang; Xin Guo; Qin He; Jijun Liu; Gang Chen; Pan Lu; Shuang Li; Denghai Liu; Jinhua Liu; Manhua Chen (Molecular & Cellular Toxicology, 2026)

The Association Between Prepubertal Polycyclic Aromatic Hydrocarbon Exposure and Physical Development During Puberty in Chinese Girls: A Longitudinal Study - Yan Li; Zongwei He; Qin Zhang; Shudan Liu; Jie Luo; Yu Tian; Yujie Wang; Qin Liu (Exposure and Health, 2026)

Are different configurations of pilot-scale constructed wetlands carbon sources or carbon sinks? - Yichu Wang; Hao Qin; Tao Liu; Tao Lang; Sihan Li; Zihang Zhang; Shuhao He; Yi Chen (ENGINEERING Environment, 2026)

Study on the thermal desorption mechanism of organic-contaminated clay under thermo-flow coupling: based on pore structure - Zonghui Liu; Song He; Dajian Pang; Yeyang Chun; Jiawei Qin; Guangyuan Li (Bulletin of Engineering Geology and the Environment, 2026)

The progress of multiphysics field coupling research on petal-shaped fuel rod - Binxian He; Shusong Qin; Zequan Huang; Jinyi Cao; Wenchao Zhang; Jianchuang Sun; Jincheng Wang; Lipeng Du; Qian Li; Weihua Cai (Annals of Nuclear Energy, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Northward Propagation of the First Monsoon Intraseasonal Oscillation in the Arabian Sea: A Moisture Mode Perspective - Qin He; Kuiping Li; Yang Yang (International Journal of Climatology, 2026)
The summer monsoon onset in the Arabian Sea (AS) is closely linked to the northward propagation of the first monsoon intraseasonal oscillation (FMISO). Based on the moisture mode theory, this study investigates the underlying mechanism driving the FMISO's northward movement. Originating in the equatorial western Indian Ocean, the FMISO evolves eastward and northward across the AS, manifesting as a southeast‐northwest‐oriented convective belt that ultimately triggers the AS summer monsoon. The FMISO's northward propagation is governed by meridional contrast in moist static energy (MSE), with accumulation occurring north of the convection center and dissipation to the south. MSE budget analysis reveals that the zonal MSE advection, dominated by the moisture component, serves as the primary driver of MSE tendency. Physically, during the monsoon transitional period, the seasonal moisture evolution in the northern Indian Ocean has formed a mean eastward moisture gradient in the AS. Its interactions with FMISO‐induced easterlies (north of the convection center) and westerlies (south of the convection center) enhance moisture to the north and reduce it to the south, thereby propelling the FMISO northward. During the FMISO's northward propagation, notable positive sea surface temperature anomalies appear to the north of the convection center. By altering the air‐sea turbulent heat fluxes, these anomalies account for approximately 35%–40% of the positive MSE tendency, though their signal is obscured in net turbulent heat flux measurements due to complete cancellation by the pronounced negative effects of surface wind speed. This detailed exploration of FMISO dynamics potentially advances our understanding of the monsoon onset process in the AS.

The Role of Atlantic Multidecadal Oscillation in Decadal Summer Temperature Variability Over the Tibetan Plateau in Observations and Pacemaker Simulations - Yanfeng He; Minhua Qin; Chuntao Yu; Huiting Feng; Hongwei Chen; Ming Li; Tao Wang; Min Wan; Shanlei Sun; Wenjian Hua (International Journal of Climatology, 2026)
Previous studies have suggested that internal oceanic modes such as the Interdecadal Pacific Oscillation (IPO) and Atlantic Multidecadal Oscillation (AMO) have significant effects on the decadal temperature variability over the Tibetan Plateau (TP). However, assessments of decadal variability are very sensitive to the length of study periods. Thus, the dominant factors regulating the decadal temperature variations over the TP and the associated mechanisms have not been clearly identified. This study utilised long‐term temperature observations, global reanalysis and climate model simulations to examine the decadal variations and the underlying mechanisms of surface air temperature (SAT) over the TP during boreal summer from 1901 to 2020. Results show that there exist decadal variations in summer TP SAT, with warm periods during 1929–1960 and 1999–2020 and cold periods during 1901–1928 and 1961–1998. It has also been found that the decadal changes in summer TP SAT are closely associated with the AMO. In contrast, TP SAT has a weak relationship with the IPO during 1901–2020. North Atlantic pacemaker simulations further show a zonal wave train pattern propagating from the North Atlantic to East Asia, which triggers anomalous anticyclonic circulations over the northern TP and Lake Baikal. The regional anticyclonic circulation anomalies over the TP not only weaken the subtropical westerly jet stream but also facilitate the water vapour transport into the TP and further cause local warming over the TP. Our findings elucidate the role of internal climate variability in shaping the decadal variability of summer TP SAT and also help reduce uncertainties in future projections of TP SAT changes.

First report of Nigrospora chinensis causing leaf blight on Coffea arabica in China - Yang Liu; Tingping Zhang; Li Xie; Qiong Chen; Haohao Yu; Xingfei Fu; Feifei He; Shiwen Qin (Journal of Plant Pathology, 2026)

CTGAN-based multi-objective optimization of rotary tillage blade design for coastal saline alkaline soils - He Sun; Xiaoliang Li; Xuan Luo; Qing Ma; Ning Jin; Chengpeng Qin; Haoran Bai (Computers and Electronics in Agriculture, 2026)

Efficient generation of highly reactive FeIVO2+ via the Fe(II)/Cl2 reaction for water purification - Shaoxiong He; Yuxin Wu; Wenlei Qin; Shenzhou Li; Wanting Cheng; Ping Li; Shizhong Wang; Gangfeng Ouyang; Mingshan Zhu; Jingyun Fang (Water Research, 2026)

Enabling BiO2-x as a paradigm-shifting multifunctional platform by uniquely harnessing low-energy 720 nm light triggering photothermal-catalytic effect - Nannan He; Yiting Qin; Songwei Li; Mengqiang Tian; Bingli Wang; Hongliang Wang; Guifen Zhu (Journal of Environmental Sciences, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Feasibility and optimization of CO2 hydrate sequestration after CH4 hydrate production: a case study in the South China Sea - Yuxuan Li; Zhaobin Zhang; Bo Zhang; Rick Chalaturnyk; Shouding Li; Jianming He; Hang Bian; Xiao Li; Cheng Lu; Xuwen Qin (Fuel, 2026)

Selective hydrogenation of nitriles to primary and secondary amines via Ni0/Ni2+ dual sites - Tongtong Fan; Jiaheng Qin; He Wen; Siyu Li; Hong Zhao; Tong Li; Xiao Zhang; Jiantai Ma; Yu Long (Fuel, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Self-assembled intestinal-targeted nanospheres composite carriers for 2-hydroxychalcone delivery to treat Citrobacter rodentium induced colitis - Xiaoli Qin; Boya Li; Xinjun Qiu; Kai Zhao; Wenjing Niu; Fuyu Yang; Binghai Cao; Huawei Su; Yang He (Chemical Engineering Journal, 2026)

Glycoengineered mesenchymal stem cell exosomes with dual-tissue targeting ameliorate glycolipid metabolism in type 2 diabetes mellitus - Yingyue Xiang; Jidong Liu; Xue Liu; Nan Zang; Mengmeng Yang; Liming Wang; Jia Song; Jun Chen; Kewei Wang; Longqing Xia; Xinguo Hou; Li Chen; et al. (Chemical Engineering Journal, 2026)

Behaviorally inspired by blue-whale throat-pleats during filter feeding: A thermoresponsive hydrogel for achieving efficient solar-driven cyclic water release and purification - Yan-Shu Xiong; Mei Li; Tanli Lu; You-Ya Sun; Hai-Qin Lu; Wen Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2026)

Rice-fish co-culture improves soil quality and microbial function: the role of fish refuge - Chanyuan Qin; Kui Li; Aohui Sun; Jin Zhou; Jianping He; Chao Yu; Yelan Yu; Minxing Hou; Kai Zeng; Hua Wang (Journal of Soils and Sediments, 2026)

A Network Information-Based Behavior Change Wheel for Populations at High Risk of Developing Gastric Cancer - Wen-Lei Huang; Shi-Guang Ren; Le-Jian He; Fen Xie; Hui-Lan Zhai; Dan-Dan Wang; Lu Jiang; Xue-Qin Li (Journal of Cancer Education, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

Mechanistic insights into the sediment accumulation and fractionation of PAHs: Role of sedimentary organic carbon and an assessment of environmental implications - Weijie Liu; Xinli Xing; Xingchen Liu; Andrew J. Sweetman; Gaigai He; Shibin Qin; Peng Li; Li Liu; Xiaoshui Li; Shihua Qi (Water Research, 2026)

Tempol suppresses ferroptosis and relieves chronic intermittent hypoxia-induced lung injury through the inhibition of TLR4 and activation of the Nrf2/GSH axis - Ran Li; Ruiting Qin; Zhijuan Liu; Xiaojie He; Dan Li; Li Ai (Tissue and Cell, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Dual-action g-C3N4 nanomaterials: Direct bactericidal activity against Xanthomonas oryzae pv. oryzae and plant immunity priming for sustainable disease control - Xiaojie Cheng; Xiaojian Qin; Siyao Li; Zhangyang Luo; Xueyan Yang; Yiwen Huang; Xiang Tao; Huanhuan Shao; Dongyan Liu; Xinyi He; Xiaoyan Wang; Bin Yong (Pesticide Biochemistry and Physiology, 2026)

Synergistic coupling of FeS/FeNi nanoparticles with 3D N, S dual-doped porous carbon network for bifunctional ORR/OER electrocatalysts and zinc-air batteries - Wenji Liang; Junwei Shi; Zhenhua Qin; Jinguang Cai; Yun He; Jianfen Li (Fuel, 2026)

Unveiling the mystery of baijiu blending based on flavoromics - Jiawen Duan; Dan Qin; Lu Gao; Fei He; Yize Zhang; Hehe Li; Jinyuan Sun; Fazheng Ren; Baoguo Sun (Food Research International, 2026)

Can urinary OH-PAHs serve as biomarkers for indicating inhalation exposure to PAHs of children: Evidence based on a panel study - Wenjing Zhao; Jiajun He; Zhangning Li; Huanming Li; Xiaojie Zhou; Sreynith Lis; Xinyi Wang; Suzhen Cao; Beibei Wang; Xiaoli Duan; Ning Qin (Environmental Pollution, 2026)

Experimental and numerical investigation on seismic performance of seawater sea-sand coral aggregate concrete filled UHPC tubular columns - Chengdong Lu; Dingkuan He; Bo Shan; Peicheng Qin; Tianyu Li; Bin Huang; Xinlin Fu; Gang Liu (Engineering Structures, 2026)

Transcriptomic insights into TiO2 nanoparticle-assisted enhancement of growth, lipid production, and dark fermentation wastewater treatment in Chlorella sp. DT025 - Xiaolong Wu; Jialu Xu; Bangxiang He; Qin Zhang; Yequan Sheng; Xin Tan; Yanbin Li (Bioresource Technology, 2026)

Inoculation with Enterobacter D27 and Bacillus D79 promotes cherry rootstock growth and changes the rhizosphere microbial community structure - Ze Tao; Fangdong Li; Zhaoqing Tong; Bingxue Li; Deguo Lyu; Jiali He; Sijun Qin (Applied Soil Ecology, 2026)

Climate warming and forest expansion significantly enhance China’s forest methane sink - Youbin Deng; Mingxu Li; Xiaoyan Kang; Li Xu; Boming Liang; Jiankun Chen; Lingli Yu; Xuanbo Wang; Xuyang Zhang; Mengze Qin; Changhui Peng; Nianpeng He (Agricultural and Forest Meteorology, 2026)

Water-soluble platinum(II)-porphyrin based on oxygen response for cell hypoxia imaging - Meng-Yan Chai; Yu-Li Dang; He Qin; Li-Xia Xie; Xin Zheng; Lijie Liu; Guoxing Liu; Yu-Qiang Xiang; Cao-Yuan Niu; Sheng-Qiang Guo (Molecular Diversity, 2026)

Dietary salidroside and astragalus polysaccharides enhance the growth performance and hypoxia tolerance of juvenile Chinese mitten crabs (Eriocheir sinensis) - Long He; Shusheng Xiao; Xiaodan Wang; Jianguang Qin; Liqiao Chen; Erchao Li (Aquaculture, 2026)

Dietary α-ketoglutarate improves the feed efficiency and growth performance of Chinese mitten crab (Eriocheir sinensis) fed low-protein diets by modulating protein metabolism and intestinal health - Jinping Li; Long He; Song Wang; Wen Li; Xiaodan Wang; Erchao Li; Jianguang Qin; Liqiao Chen (Aquaculture, 2026)

Establishing LMBV infection resistance models in largemouth bass: Exploration and confirmation of pathways and genes relevant to disease resistance in breeding programs - Shen Li; Bangsong Meng; Wenxuan Ouyang; Liqun Wang; Jinpeng Chen; Xin He; Qiwei Qin; Min Yang (Aquaculture, 2026)

Diverse impacts of cadmium exposure on adolescent liver health: Suppression of steatosis and promotion of fibrosis - Si-Jie Hong; Li-Wei Hong; Xiao-Qin He; Xiao-Qing Yang; Xiao-Hong Zhong; Jin-Zhun Wu (Toxicology Letters, 2026)

Optimizing irrigation and nitrogen rates for sustainable wheat production: Balancing yield and nitrate leaching in a 7-year field study - Haoran Li; Bin Jia; Hongguang Wang; Dongxiao Li; Qin Fang; Jianning He; Xiaokang Lv; Ruiqi Li (Soil and Tillage Research, 2026)

Biomimetic intensified NH/CH···π interaction via metal oxide-mediated interfacial polarization for robust nanoplastics capture by polyurethane foam - Xuan Zhang; Fei He; Bojin Li; Nan Nan Xia; Qin Wu (Journal of Hazardous Materials, 2026)

Identification, evolutionary and characteristic analysis of apoptosis - related caspase gene family in Tachysurus fulvidraco and their expression profiles under bacterial, parasitic, and viral infections - Peng Tang; Yueping Chen; Tong Yue; Zhangyan Liang; Jianying Yang; Qiao Wang; Yang He; Chuanjie Qin; Zhengyong Wen; Qingchao Shi; Li Zhou; Jun Wang (Fish & Shellfish Immunology, 2026)

Performance stability and recovery strategy of pre-denitrification coupled partial nitritation/anammox-hydroxyapatite processes for enhanced organic matter, nitrogen and phosphorus removal from swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Chao Rong; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2026)

Detecting and comparing extinction debts of amphibians in China under climate change - Yu-Xiao He; You-Hua Chen; Xiao-Qin Shi; Chao-Sheng Mu; Dan-Dan Yu; Jia-Qi Li; Hai-Gen Xu; Jian-Ping Jiang (Biological Conservation, 2026)

Therapeutic Intervention of Corticospinal Tract Sprouting after Unilateral Traumatic Brain Injury via METTL1-Mediated tRNA m7G Modification - Zhenpeng Li; An Jiang; Bengang Qin; Jintao Fang; Xubo Li; Fanbin Gu; Wenting He; Liwei Yan; Jiantao Yang; Canbin Zheng; Qingtang Zhu; Honggang Wang (Molecular Neurobiology, 2026)

Groundwater level prediction in urban karst regions: The comparison of ensemble learning and deep learning models by considering climate conditions - Xiaoqing Song; Ruihan Xiong; Zhenzhu He; Danyuan Luo; Shuyi Li; Ying Wang; Qin Peng; Shilong Yang; Yuxuan Fang; Aiguo Zhou; Xu Guo; Hanxiang Xiong (Urban Climate, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Bioactive sesquiterpene lactones with cytotoxic activity from Youngia japonica - Hao Gong; Kuan Lin; Lei Zhang; Yi Huang; Li-Juan Hu; Xiao-Ya Liu; Hao Ming; Si-Qi Wang; Qing-Qin He; Xian-Sheng Ye; Shu-Xiu Zhu (Phytochemistry Letters, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Functional characterization of GmSRS14 in regulating root nodule development of soybean - Kangjun Fan; Yue Wu; Yonghua Qin; Hongzao He; Lu Lv; Gang Li; Jiao Liu; Rui Qin; Hong Liu (Journal of Plant Physiology, 2025)

Temporal variation in soil detachment capacity of high-severity post-fire in dry-warm valley forest lands in Southwest China - Xiaosong Qin; Yi Wang; Longxi Cao; Wei He; Yongkang Li; Dongdong Hou; Yufan Wang; Jia Xu (Journal of Hydrology, 2025)

Research on the synergistic recovery of iron and electricity production performance in acid mine drainage using fuel cells - Zhaocong Ren; Yue Zhang; Jinyuan Jiang; Lihong Wei; Haoyang Song; Wei Tan; Yajun Li; Dongni Shi; Lei He; Hongke Qin (Journal of Environmental Chemical Engineering, 2025)

The effect of physical-chemical combined clogging on the area density and permeability of geotextile envelopes for subsurface drainage systems in arid regions - Shuai Qin; Chenyao Guo; Jingwei Wu; Shuai He; Haoyu Yang; Chenzhi Yao; Xinman Jiang; Hang Li (Geotextiles and Geomembranes, 2025)

Dynamic DIA proteomics of mare's milk reveals distinct colostrum signatures and stage-specific lactation profiles - Luan Yue; Wendan Tang; Cao Li; Xiaoyu Yue; Xiaoyun He; Aleksandr Mikhailovich Zaitsev; Mu Zhang; Valery Vasilievich Kalaschnikov; Jingyi Li; Qin Wang (Food Chemistry, 2025)

Multi-system toxicity of lead (Pb) in Procambarus clarkii: Integrated analysis of tissue damage, immune dysfunction, oxidative stress, and microbial dysbiosis via multi-omics approaches - Lang Zhang; Ziwei Song; Qiuying Qin; Li He; Juan Tian; Yali Yu; Yingchun Mu; Liqi Zhong; Zongbin Cui; Jinhua Gan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

From energy drain to resource gain: A high-rate system for synergistic carbon capture and ammonia retention - Ruize Gu; Dongyi Li; Yujie Zhu; Yanling Yu; Wenyong Qin; Weiyan Li; Xinlei Chu; Weihua He; Yujie Feng (Chemical Engineering Journal, 2025)

Methionine in embryonic development: metabolism, redox homeostasis, epigenetic modification and signaling pathway - Chang Yan; Biyan He; Chenjun Wang; Wanzhen Li; Siming Tao; Jingqing Chen; Yuquan Wang; Ling Yang; Yingjie Wu; Zhenlong Wu; Ning Liu; Yinghe Qin (Critical Reviews in Food Science and Nutrition, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Alveolar macrophages polarization switch via α2-adrenoceptor activation ameliorates pulmonary inflammation following kidney ischemia reperfusion - Jieyu Li; Zhigang Qin; Xinhai He; Ling Jiang; Xiangfeng Liu; Zhengwei Xue; Xiao Li; Yueming Xu; Peng Li; Jianteng Gu (Inflammation Research, 2025)

Regional-scale patterns and drivers of soil CO2 emissions in steppe ecosystems - Wei Song; Xiaodong He; Shuping Qin; Minjie Yao; Xiangzhen Li (Soil Ecology Letters, 2025)

Study on the irradiation mechanical behavior of three-petal fuel rods contact based on multi-physics field coupling - Weihua Cai; Shusong Qin; Binxian He; Hao Yang; Xiangfei Meng; Wenchao Zhang; Qian Li; Jianchuang Sun (Annals of Nuclear Energy, 2025)

Cathayanon E induces apoptosis and enhances oxaliplatin sensitivity in colorectal cancer through suppression of MCL1 - Liang Cen; Xin Hu; Guozhen An; Lichao Wang; Yanghao Hu; Junjie He; Hanghang Qin; Yongsen Li; Hongjuan Cui (Apoptosis, 2025)

Water quality analysis of organic pollutants in electronic industry manufacturing wastewater based on spectral analysis and molecular level exploration - Run Yuan; Yihe Qin; Han Li; Weiqing Huang; Haiming Huang; Xuwen He (Journal of Water Process Engineering, 2025)

Assessment of coffee endophytic yeasts for efficient mucilage removal and consistent quality improvement in coffee production - Yukai Suo; Na Yang; Hongmin Yang; Liping Li; Zhiyan Lan; Weiguang Wang; Feifei He; Shiwen Qin (Food Chemistry, 2025)

Analysis of antiviral functions, differences and apoptotic effects of two novel MHC-Iα genotypes in orange-spotted grouper (Epinephelus coioides) - Jinpeng Chen; Xin He; Bangsong Meng; Liqun Wang; Shen Li; Wenxuan Ouyang; Yun Sun; Qiwei Qin; Min Yang (Fish & Shellfish Immunology, 2025)

Green manure species synergize with organic fertilization to enhance soil nutrient–microbial interactions and wheat productivity in oasis drip–irrigated systems - Liyang Cheng; Hao He; Shuai Li; Mengmeng Yu; Tingting Wan; Jie Qin; Chunyan Li; Junhua Li (Field Crops Research, 2025)

Promoted chlorobenzene deep oxidation over CeCo10Ox-P nanosheet catalyst via acid site and oxygen vacancy rational construction - Yahao Wang; Mingjiao Tian; Yaruo Zhao; Han Xu; Dong Guo; Jiaxun Zhang; Zeyu Jiang; Qin Yang; Lu Li; Chi He (Chemical Engineering Journal, 2025)

F, O-co-regulated Ni-Co-S mesoporous heterostructured electrodes for supercapacitor applications - Xuzhao Han; Baojing Luo; Hailin Zhang; Yue Xing; Qin He; Yu Gu; Gaihua Li; Shuang Liu (Chemical Engineering Journal, 2025)

Design of EVOH nanofibers aerogel integrated with phase change materials for sustained solar-driven seawater desalination - Ye Zhang; Yi Wu; Shanshan Li; Mengqi Wang; Ke Liu; Ming Xia; Qin Cheng; Jia Xu; Shanshan He; Dong Wang (Chemical Engineering Journal, 2025)

Climate warming plays an important role in dissolved organic carbon loss in deep soil layers across China - Lingli Yu; Mingxu Li; Xiaoyan Kang; Li Xu; Boming Liang; Jiankun Chen; Youbin Deng; Xuanbo Wang; Xuyang Zhang; Mengze Qin; Changhui Peng; Nianpeng He (CATENA, 2025)

High-severity fire reduces soil erosion resistance: A study based on 4-year field monitoring data in dry-warm valley in Southwest China - Xiaosong Qin; Yi Wang; Longxi Cao; Ping Ren; Wei He; Yongkang Li; Dongdong Hou; Yufan Wang; Jia Xu (CATENA, 2025)

Intercomparison of multiple chemical mechanisms in simulating severe haze event over the North China plain - Zhen Li; Yicong He; Shaocai Yu; Hongkui Wang; Fan Fan; Chuang Qin; Ye Chen; Weiwei Dai; Zixi Jin; Dongliang Zhao (Atmospheric Environment, 2025)

Xanthouhumol relieves stress-induced depressive-like behaviors through the Sirt1/NF-κB/NLRP3 pathway - Gangqiang Lin; Yi Zhang; Jing Qin; Yong He; Li Fan; Qing Tan; Peng Xie (Psychopharmacology, 2025)

Disulfide bond-driven nanoassembly of lipophilic epirubicin prodrugs for breast cancer therapy - Haimeng Yuan; Yao Chen; Yuting Hu; Yanxin Li; Hongyuan Zhang; Shenwu Zhang; Qin Chen; Wenhu Zhou; Jin Sun; Zhonggui He; Yuequan Wang; Cong Luo (Journal of Pharmaceutical Investigation, 2025)

Woodlands as refuges and resources for paddy spider communities: Varying importance with land consolidation intensity - Pengyao Li; Ruxia Qin; Mingzhu Shen; Changliu Wang; He Xiao; Jian Liu; Wenjin Qian; Meichun Duan (Agriculture, Ecosystems & Environment, 2025)

New insights into the Holocene temperature conundrum from long-chain alkyl diol paleothermometers in the East China Sea inner shelf - Lilei Chen; Feng Li; Jian Liu; Xiaoyong Duan; Xingliang He; Bin Chen; Maogang Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

High-resolution magnetostratigraphy of the Lower Cretaceous Dabeigou Formation in the Luanping Basin, northern China - Zhongshan Shen; Zhiqiang Yu; Zuohuan Qin; Dangpeng Xi; Gang Li; Huaiyu He; Chenglong Deng; Zhonghe Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Vegetation restoration improves phosphorus content and availability in tailings slag - Mengting Li; Xinying Sui; Xiaohong Wu; Jinsong He; Jiancong Wang; Qingying Liao; Jun Wang; Wei Wang; Xingxing Qin; Renjie Wang; Yong Wang; Wende Yan (Journal of Environmental Management, 2025)

Recovering spent Li-ion batteries as Li2CO3 and NCM (nickel cobalt manganese) carbonate precursor by thermal reduction and co-precipitation combined process - Xingwen Lu; Yue He; Zebiao Huang; Jiating Li; Zenghua Qi; Jianqiao Qin; Fei Wang (Journal of Environmental Chemical Engineering, 2025)

Synergistic dewatering of construction foundation sludge via tripartite strategy: High-efficiency flocculation and floc skeleton reinforcement mechanism - Shixin Zhang; Jiahui Zhang; Dilin He; Yixin Zhang; Shiyu Yuan; Xiaomin Tang; Huaili Zheng; Sen Li; Yuxin Chen; Yu Qin (Journal of Environmental Chemical Engineering, 2025)

Modification effect of prenatal polyunsaturated fatty acids on the associations between air particulate matter exposure and infant's growth: A birth cohort study - Yu Liu; Xiaonan Gu; Lili Qin; Xuanqing He; Minyan Lan; Yujing Chen; Qian Chen; Zhen Wang; Zhaoyan Liu; Lizi Lin; Jing Wei; Yanhong Wei; et al. (Environmental Pollution, 2025)

Role of low-dose cadmium exposure to the pathogenesis of gestational diabetes mellitus - Huan Chen; Jinlian Bin; Zhongqiang Cao; Yidan Luo; Pengshu Song; Jiajia He; Shi Lu; Gaga Mahai; Jianqiu Zheng; Yuanyuan Li; Jie Qin (Environmental Pollution, 2025)

Impact of Ca supplement to the single-stage partial nitritation/anammox-hydroxyapatite process in treating swine manure digestate: deterioration mechanism and recovery strategy - Yunzhi Qian; Shilong He; Chao Rong; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Divergent effects of cropland management practices and global change factors on microbial necromass across ecosystems: implications for soil organic carbon - Chen-Hao Lyu; Wen-Jun He; Peng Chen; Xin-Xin Jing; Guo-Shi Zhang; Run-Qin Zhang; Zi-Yan Li; Zhi-Guo Li; Yi Liu (CATENA, 2025)

Mechanistic study of pexidartinib-induced toxicity in human hepatic cells - Si Chen; Yuxi Li; Xilin Li; Nan Mei; Xiaobo He; Matthew S. Bryant; Xuan Qin; Feng Li; Lei Guo (Chemico-Biological Interactions, 2025)

Efficient and stable removal of organic matter, nitrogen and phosphorus from swine manure digestate by coupling high-rate activated sludge and single-stage partial nitritation/anammox-hydroxyapatite processes - Yunzhi Qian; Shilong He; Yan Guo; Fuqiang Chen; Junhao Shen; Yu Qin; Yu-You Li (Bioresource Technology, 2025)

Diurnal NO emission underestimation constrained using overlapping TROPOMI swaths - Qin He; Kai Qin; Xiaolu Li; Lingxiao Lu; Man Sing Wong; Jason Blake Cohen (Atmospheric Environment, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Transcriptome Reveals Molecular Characteristics and Immune Response in Triploid Cyprinid Fish Infected with a Novel Pathogenic Aeromonas sp. AS1-4 - Qin-Yang He; Jie Peng; Ruo-Xing Yu; Ting Luo; Yao-Hui Li; Zi-Rou Zhong; Zi-Le Qin; Fei Wang; Jian Li; Sheng-Wei Luo (Marine Biotechnology, 2025)

The impacts of fine particulate matter on ankylosing spondylitis incidence in Southwest China - Xiaopeng Qin; Jiang Xue; Yizhang Xia; Zhen Du; Wenjie Tao; Rongqing He; Boli Qin; Yukang Wu; Yuhang Luo; Zhongxian Zhou; Shaofeng Wu; Chenxing Zhou; et al. (International Journal of Biometeorology, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Synthesis of novel phthalide bearing thiazole, 1,3,4-oxadiazole, and oxime ether groups as potential antifungal agents - Yong Li; Taotao Wu; Guobin Chen; Jian He; Yong Zhang; Qin Zhang; Pengfei Zhou; Wenzhang Chen; Lingling Fan (Molecular Diversity, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Ecosystem engineering and global changes are increasingly enhancing China’s terrestrial carbon sinks - Mengyu Zhang; Honglin He; Li Zhang; Xiaoli Ren; Liang Shi; Guirui Yu; Zhong’en Niu; Keyu Qin; Tiecheng Li (Resources, Conservation and Recycling, 2025)

Closed-loop ammonium removal enabled by EPS-based hydrogel derived from cyanobacterial blooms - Yu Huang; Xing Zhang; Xiaoying Lv; Jingyi Zhao; Ni Xie; Tingting Dong; Zeng He; Mingyan Qin; Bo Wei; Yalin Li (Process Safety and Environmental Protection, 2025)

OsATG1 and OsATG8 exhibit autophagy-independent functions to oppositely regulate ROP GTPase-mediated plant immunity in rice - Feng He; Hui Tao; Ruyi Wang; Jinling Liu; Zeyun Hao; Debao Wang; Xuetao Shi; Fan Zhang; Jiawei Long; Hao Zhang; Xiao Yang; Mengchao Qin; et al. (Molecular Plant, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Self-stimulative fluorination diffusion reaction fabricating sequential gradient anti-reflection layer on polymer films for record light transmittance - Mingfei Zhong; Kun Fan; Xiang Li; Yitian Qin; Jingyi He; Zhengyi Fang; Shuai Yang; Yongjiu Li; Yang Liu; Xiangyang Liu (Chemical Engineering Journal, 2025)

Constructing the linear adsorption of *CO and suppressing hydrogen evolution by alkaline earth metal for efficient CO2RR - Xupeng Qin; Qizheng An; Shen Cheng; Honglei Chen; Wanlin Zhou; Haixin Sun; Yuhao Zhang; Yanzhi Xu; Changli Li; Yaling Jiang; Jingfu He; Qinghua Liu (Chemical Engineering Journal, 2025)

Post-depositional effects on chromium in black shales and implications for paleo-redox reconstructions based on chromium isotopes - Ziyao Fang; Xiaoqing He; Xi Yu; Dandan Li; Xiaolin Zhang; Yanan Shen; Liping Qin (Chemical Geology, 2025)

Understanding fear generalization in adult zebrafish in predator-based assays - Jiayou Jiang; Jiyi Wang; Daniil D. Martynov; Nikita I. Golushko; Yixin Qin; Yunqian Zhang; Chonguang Zhao; Chaoming Wang; Yucheng Liu; Haoyu Feng; Huiling Cai; Kai He; et al. (Behavioural Processes, 2025)

Soil Carbon Availability Drives Depth‐Dependent Responses of Microbial Nitrogen Use Efficiency to Warming - Qiufang Zhang; Wenkuan Qin; Xiaojie Li; Jiguang Feng; Yuehmin Chen; Zhenhua Zhang; Jin‐Sheng He; Andreas Richter; Joshua P. Schimel; Biao Zhu (Global Change Biology, 2025)
Microbial nitrogen use efficiency (NUE) describes the partitioning of organic N between microbial growth and N mineralization, which is crucial for assessing soil N retention. However, how warming affects NUE along soil depth remains unclear. Based on a whole‐soil‐profile warming experiment (0 to 100 cm, +4°C) on the Qinghai‐Tibetan Plateau, combined with 18 O and 15 N isotope labeling techniques, we determined soil carbon (C) composition, edaphic properties, and microbial parameters. The results showed that NUE declined with soil depth in both control and warming treatments, driven by microbial C limitation. The response of NUE to warming varied with soil depth. Warming reduced topsoil (0–30 cm) microbial N growth, ultimately leading to a decrease in NUE, but had no effect in deep soils (30–100 cm). Jointly, these findings highlight that warming may exacerbate soil N loss in topsoil, and that maintaining microbial C and N availability could be a key strategy for preserving microbial N sequestration under warming conditions.

Multiple Impacts of Climate Change and Anthropogenic Activities on Lacustrine Trophic State - Ge Xie; Yibo Zhang; Qing Wang; Kun Shi; Yunlin Zhang; Yongqiang Zhou; Boqiang Qin; Junliang He; Na Li (Global Change Biology, 2025)
The trophic state index (TSI) serves as a fundamental indicator for evaluating the water quality of lake ecosystems. Under climate change and human activities, global lake TSI has changed significantly, yet its response mechanisms remain unclear. To address this challenge, we developed a generalized TSI estimation model by integrating semi‐analytical algorithms with machine learning techniques, based on a comprehensive dataset comprising 3756 pairs of in situ measurements and remote sensing observations. The developed model demonstrated superior predictive performance with R 2 of 0.77 and RMSE of 8.25 for the testing dataset. Applying the model, we reconstructed a 21‐year time series (2003–2023) TSI for 14,189 global lakes with surface area ≥ 10 km 2 . The global mean TSI was estimated to be 54.07 ± 0.31. Among the lakes, 4.1% were classified as oligotrophic (TSI ≤ 38), 18.9% as mesotrophic (38 61). Globally, TSI showed a significantly increasing trend at a rate of 0.19 per decade ( p

Energy Decomposition-Driven Design of Trop2-Targeting Peptide - Yu-Chao Meng; He Liu; Bi-Shao Sun; Hong-Yuan Liu; Hong-Wei Li; Qiu-Yu Liao; Mouxin Huang; Qin Ouyang (Cell Biochemistry and Biophysics, 2025)

Prediction and verification of arsenic phytoavailability in paddy soil based on CD-MUSIC model in the Xiangjiang River Basin - Qian Tian; Jian He; Shuangling He; Qin Zhang; Hongbin Li; Limei Peng; Daoyou Huang; Hanhua Zhu; Xinliang Liu; Qihong Zhu (Journal of Hazardous Materials, 2025)

Canopy nitrogen and water addition affect fine-root survival strategies and carbon allocation in a warm-temperate forest in China - Wen Li; Yanzhu Su; Yiwen Qin; Fuwei Li; Tenglong Zhou; Yaqi He; Jianing Mao; Mengke Li; Chang Liu; Yifei Shi; Dandan Zhu; Chunyu Shen; et al. (Forest Ecology and Management, 2025)

Robust configuration planning for net zero-energy buildings considering source-load dual uncertainty and hybrid energy storage system - Genzhu Li; Xiaofeng Xu; Xiaochun Cheng; Qin Wang; Yan Zhang; He Wu; Dunnan Liu (Building and Environment, 2025)

A Framework for Mining Intercity Relationship of PM2.5 Based on Granger Causality Test: Application to Cities in China - Ran-Ran He; Dong-Qin Li; Sun Zhang (Environmental Modeling & Assessment, 2025)

Quantitative Reconstruction of Salinity and Precipitation Changes in Central Asia over the Past 3 200 Years Using Diatom and Pollen Records of Lacustrine Sediment in Aibi Lake of SW Junggar Basin - Long Pan; Guoqiang Li; Xiaoyan Wang; Ming Jin; Xinrong He; Luo Qin; Zhong Wang; Wenwei Zhao; Chunzhu Chen; Yuanlu Liu; Jin Yang; Lele Shu (Journal of Earth Science, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Inverse thermoreversible methylcellulose-based and recyclable conductive gel for versatile triboelectric nanogenerator with rough interface under complex conditions - Jia Yang; Chenyu Li; Zhenyang Li; Zhiwen Liu; Wenjie He; Yue Xiao; Shuzheng Liu; Gang Qin; Aiguo Zhou; Qiang Chen (Chemical Engineering Journal, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Green solvent hydrothermal recycling of end-of-life crystalline silicon photovoltaic modules - Kai Zhang; Shihao He; Danyan Qin; Xian Xie; Wei Zhang; Pan Deng; Jintao Li; Hongdan Rao; Heming Deng; Tao Mei; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2025)

Mechanically optimized hydrogel enhances functional recovery after spinal cord injury - Yubing Yang; Chenguang Zhao; Jinghao Zhao; Hua Zheng; Chengdong Zhou; Jing Li; Shengshou Ye; Shuang Wang; Dong Wang; Xin Zhang; Xijing He; Jie Qin (Chemical Engineering Journal, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

Endothelial GTPBP3 directs developmental angiogenesis and neovascularization after limb ischemia via the mtROS/HRl/ATF4/mTORC1 axis - Donglu Qin; Jiarui Hu; Yang Yang; Xin Li; Jia He; Jin Chen; Xin Guo; Cheng Wei; Fengjiao Wang; Ting Yi; Chenyu Li; Bilian Yu (Angiogenesis, 2025)

Effects of dietary SFA/MUFA ratios on serum biochemical indices, lipid metabolism-related gene expression, and muscle quality in Yellow River carp (Cyprinus carpio haematopterus) during FO finishing strategy - Yuhang Sang; Xinlu Li; Zijie He; Chaobin Qin; Chao Xu; Guoxing Nie; Yuanyou Li; Dizhi Xie (Aquaculture, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Potential impacts of polyethylene microplastics and heavy metals on Bidens pilosa L. growth: Shifts in root-associated endophyte microbial communities - Ziang He; Yanxue Wang; Yiyun Fu; Xiaoxiao Qin; Wei Lan; Dongyi Shi; Yingxuan Tang; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2025)

Enhancing municipal sludge composting efficiency: The synergistic impacts of montmorillonite and coconut shell biochar additives on heavy metal passivation and microbial community succession - Wanxuan Qin; Asfandyar Shahab; Xiaojie Sun; Jieyue Li; Kemeng Li; He Xiao (Journal of Environmental Chemical Engineering, 2025)

Fabrication of electrically conductive polysulfone loose nanofiltration composite membranes with a dually charged separation layer for efficient separation of dye/salt mixtures: Electric-field-assisted formation of porous support layers - Kang Li; Shuhao Qin; Wei Gao; Mingmi Wu; Man Yang; Chengtao Gao; Shengbao He; Huiju Shao (Journal of Environmental Chemical Engineering, 2025)

Solid bitumen formation and resulting differential porosity development in the Mesoproterozoic Xiamaling shale during artificial thermal maturation - Ji Chen; Jingwen Zheng; Daxiang He; Peng Cheng; Qin Zhou; Tengfei Li; Haifeng Gai (International Journal of Coal Geology, 2025)

Encapsulated benzoic acid alleviated LPS-induced intestinal damage via NRF2 activation - Yanyan Zhang; Tianjiao Wang; Qing He; Mahmoud M. Abouelfetouh; Qin Fu; Siming Yao; Shiqiang Ju; Zhenlei Zhou; Qiao Li (Food Bioscience, 2025)

Halomonas fermentation promoted the biotransformation of active substances from Dictyophora indusiata pileus and the enhancement of antioxidant capacity - Xueying Zheng; Ying He; Lei Ma; Yanting Sun; Jiazi Yu; Zeguo Feng; Censhu Li; Jiaru Jiang; Xiaoni Zhang; Liguo Qin; Dan Tan; Yali Zhang (Food Bioscience, 2025)

Circulating MicroRNAs in association with urinary arsenic: A community-based multi-center study in China - Wending Li; Zhaoyang Li; Jixuan Ma; Xuedan Xu; Bin Wang; Pinpin Long; Qin Jiang; Yutong You; Jingli Qu; Yufei Wang; Yaxin Wang; Meian He; et al. (Environmental Research, 2025)

Novel pH-responsive and CD44-targeting silica nanoparticles for inflammatory bowel disease therapy - Wenxuan Li; Jingshu Cai; Yuanfeng Gu; Xingwang Li; Wenjun He; Yanyan Chen; Zhuyun Wang; Kemeng Li; Guangcheng Qin; Xiaojie Gu; Jiaoni Zheng; Jiayu Li; et al. (Chemical Engineering Journal, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Adaptive laboratory evolution induces cell wall alterations for succinic acid tolerance in Saccharomyces cerevisiae - Ling Qin; Shoujie He; Jin Hou; Guangjian Li; Yunzi Feng; Mouming Zhao; Mingtao Huang (Bioresource Technology, 2025)

Comparative Metabolomics Analysis of Terpenoid and Flavonoid in Roots of Red Beet and Sugar Beet (Beta vulgaris L.) - Wentao He; Naixin Liu; Qin Zhou; Linxuan Li; Wenwen Zhao (Sugar Tech, 2025)

Ulva clathrata Enzymatic Hydrolysate Protects Wheat from Salt–Alkaline Stress by Regulating ABA Biosynthesis - Chunying Du; Feiyu Li; Fang He; Yongzhou Chi; Bo Zhu; Xiuchao Song; Siqi Zuo; Xinyu Wang; Yimin Qin; Peng Wang (Journal of Plant Growth Regulation, 2025)

Mechanism of Cnidii Fructus in the Treatment of Infertility Based on Network Pharmacology and Molecular Docking Analysis Technology - Jun Feng; Li Zeng; Cheng-yao He; Zheng-qi Liu; Qin Yuan; Chao Zhao; Li Cheng (Biochemical Genetics, 2025)

Seasonal and spatial variations of nutrients and environmental effects under anthropogenic influence in Daya Bay, China - Jincheng Zhao; Jiawei He; Cai Li; Zeming Yang; Cong Liu; Xianqing Zhang; Min Qin; Dejing Tang; Wen Zhou; Zhantang Xu; Yuanyue Cheng (Frontiers in Marine Science, 2025)
Nutrients are crucial factors for the growth of phytoplankton, and their biogeochemical processes directly impact marine biodiversity. In this study, based on two cruise observations in spring and summer of 2024, the seasonal and spatial variations of nutrients, chlorophyll a, and other ecological indicators in Daya Bay were explored. The results indicated that the average concentrations of dissolved inorganic nitrogen and silicate were 3.61 ± 3.99 µM and 26.27 ± 13.91 µM in summer, respectively, compared with 2.48 ± 1.53 µM and 23.8 ± 6.77 µM in spring. The average concentration of dissolved inorganic phosphate was 0.29 ± 0.12 µM in summer, lower than 0.32 ± 0.09 µM in spring. The stoichiometric proportion among nutrients at most monitoring stations were far from Redfield ratio, and a succession from N-limited to P-limited was observed. A transformation has been observed in the dominant composition of dissolved inorganic nitrogen, shifting from ammonia to total oxidized nitrogen as the main component, which is mainly attributable to the decrease in aquaculture activities in Daya Bay over the last 3 years. In addition, the warm wastewater discharge from nuclear power stations directly influences the distribution of phytoplankton in the surrounding areas. This study provides timely information regarding recent shifts in ecological indicators and is significant to the ecological protection, environmental management, and policy adjustment in Daya Bay.

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effect of compound exposure to snowstorm and cold spell on acute myocardial infarction mortality - Jihong Hu; Zhiwei Li; Jingli Zhu; Qin He; Wenjun Cheng; Qianyao Cheng; Yinguang Fan; Hong Su; Huadong Wang; Zhongliang Bai; Xiuya Xing; Jian Cheng (Environmental Research, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

The chromosome-scale genomes of two cultivated safflowers (Carthamus tinctorius) provide insights into the genetic diversity resulting from domestication - Shuo Liu; Saimire Aishan; Qiuyu Liu; Lu Lv; Kang Ma; Kangjun Fan; Kehui Zhang; Yonghua Qin; Gang Li; Xueli Hu; Zunhong Hu; Junwei He; et al. (Theoretical and Applied Genetics, 2025)

Metagenomics reveals an increased proportion of an Escherichia coli-dominated enterotype in elderly Chinese people - Jinyou Li; Yue Wu; Yichen Yang; Lufang Chen; Caihong He; Shixian Zhou; Shunmei Huang; Xia Zhang; Yuming Wang; Qifeng Gui; Haifeng Lu; Qin Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Co-infection by RGNNV and V. rotiferianus in golden pompano: Insights into disease risks and immune responses - Xinshuai Li; Lingfeng Guan; Cuiyu Liu; Jinpeng Chen; Xin He; Yanwei Li; Shaowen Wang; Qiwei Qin; Min Yang (Aquaculture, 2025)

The unnoticed risk: Chronic nitrite exposure disturbs the intestinal barrier, new insights from juvenile starry flounder (Platichthys stellatus) - Jie Lian; Jingchao He; Honglu Guo; Anxin Shi; Xiangyuan Li; Qing Ji; Ziyi Zhang; Xingqiang Wang; Suyue Zhou; Bo Qin; Jiachen Yu (Aquaculture, 2025)

Bioclimatic zonation and spatial-scale dependence of lacustrine microbial assemblages - Shuren Wang; Qinglong L. Wu; Huabing Li; Rujia He; Congcong Jiao; Mengyu Qin; Ye Deng; Guoqing Zhang; Dayong Zhao; Jin Zeng (Science Bulletin, 2025)

Dynamic impact of polyethylene terephthalate nanoplastics on antibiotic resistance and microplastics degradation genes in the rhizosphere of Oryza sativa L. - Yi Li; Weiwei Qin; Xiaomin Xin; Chijian Tang; Yueying Huang; Xinying He; Lixing Chen; Guo Yu; Fangming Yu (Journal of Hazardous Materials, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

A model for predicting permeability of geotextile envelope for subsurface drainage after combined clogging in arid areas - Shuai Qin; Chenyao Guo; Jingwei Wu; Shuai He; Haoyu Yang; Chenzhi Yao; Xinman Jiang; Hang Li (Geotextiles and Geomembranes, 2025)

Mitigation effect and mechanism of different pretreatment methods on reverse osmosis membrane fouling in coal chemical wastewater treatment - Peng Tang; Jialin Shi; Can He; Xifan Li; Guijing Chen; Yi Deng; Jiawang Qin; Baicang Liu (Desalination, 2025)

In-situ surface reconstruction of BiVO4/CuFe2O4 photoanode for efficient and robust solar water oxidation - Tengfei Wang; Kai Song; Houjiang Liu; Hongyan Li; Yufei Zhang; Weijie Ren; Rui Zhang; Kun Li; Fang He; Zhenxing Qin; Huilin Hou (Chemical Engineering Journal, 2025)

Ultrafast separation of Nd and Dy from Co by modified mesoporous silica with a novel phosphate group ligand - Yilai Zhong; Zengyuan Li; Jianchun Qin; Wenlong Li; Chunlin He; Lifeng Chen; Xiangbiao Yin; Mohammed F. Hamza; Yuezhou Wei; Shunyan Ning (Journal of Water Process Engineering, 2025)

Integrated metabolomic and transcriptomic analysis reveals the regulatory effects of IAA on polyphenol biosynthesis and antioxidant activity in Phlebopus portentosus - Taobo Xiang; Feng Ge; Lei Zhu; Gaige Shao; Tao Wu; Hao Fan; Yueqian Liu; Longyu Wang; Jing Wang; Peng Li; Qin He; Ailiang Jiang; et al. (Food Bioscience, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A wild-allele GsPP2C-51-a1 enhances tolerance to drought stress in soybean and Arabidopsis - Cheng Liu; Xianlian Chen; Wei Han; Xiaoshuai Hao; Liang Qin; Wei Luo; Lizhi Zhao; Ning Li; Lei Sun; Jiaoping Zhang; Guangnan Xing; Jianbo He; et al. (Theoretical and Applied Genetics, 2025)

Trait-based analyses reveal the recovery of riverine fish communities after a fishing ban - Zhijun Xia; Qin Wang; Sébastien Brosse; Jani Heino; Zixin Wang; Zhonghua Liao; Xuehua Li; Yongfeng He; Fei Liu; Jianwei Wang (Reviews in Fish Biology and Fisheries, 2025)

Molecular and cellular role of variants of the promoter region of HAND1 gene in sporadic and isolated ventricular septal defect - Jia-Le Qi; Huan-Xin Chen; Hai-Tao Hou; Zhuo Chen; Li-Xin Liu; Qin Yang; Guo-Wei He (Molecular and Cellular Biochemistry, 2025)

A New Pattern of Species Diversification Revealed by Populus on the Qinghai-Tibet Plateau - Jia-Xuan Mi; Fei-Fei Tian; Jin-Liang Huang; Yu-Jie Shi; Jing Li; Fan-Yu Meng; Fang He; Yu Zhong; Han-Bo Yang; Fan Zhang; Liang-Hua Chen; Xue-Qin Wan (Evolutionary Biology, 2025)

Multi-Beam Accelerator-Driven-Systems of Part I: Optimization on Thermal-Hydraulic design of target assembly - Xiaobo Li; Xunchao Zhang; Yuanshuai Qin; Yuan He (Annals of Nuclear Energy, 2025)

Carbohydrate allocation strategies in leaves of dominant desert shrubs in response to precipitation variability - Huijun Qin; Yuanshang Guo; Chengyi Li; Chunming Xin; Rui Hu; Mingzhu He (Agricultural and Forest Meteorology, 2025)

Effect of Interaction of ATG7 and Plasma Metal Concentrations on Cognitive Impairment in Rural China - Xu Tang; Jiejing Cao; Jiansheng Cai; Xiaoting Mo; Yanfei Wei; Kailian He; Zeyan Ye; Yu Jian Liang; Linhai Zhao; Lidong Qin; You Li; Jian Qin; et al. (Journal of Molecular Neuroscience, 2025)

Combustion characteristics, functional groups, and gaseous emission behavior of different coals by TG-FTIR - Chunxiang Chen; Shuo Qin; Jundong Zhu; Lihui He; Bingjie Li; Wenda Wang; Zhulin He (Environmental Science and Pollution Research, 2025)

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Evaluating the water quality of the rice–fish co-culture pattern based on the modified NSF water quality index model - Chanyuan Qin; Jianping He; Chao Yu; Aohui Sun; Kui Li; Huiying Hu; Teng Hu; Yingying Ye; Yelan Yu; Hua Wang (Aquaculture, 2025)

Evaluation of protective efficacy of Pseudomonas plecoglossicida ΔdeoR as an attenuated vaccine against virulent challenge in large yellow croaker (Larimichthys crocea) - Pan Qin; Xingfu Chen; Jinmei Yang; Xin Li; Tong Wu; Jingsong Yang; Bilian Lou; Liangyin He; Youshen Li; Xinhua Chen (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Insights into the photoaging behavior of biodegradable and nondegradable microplastics: Spectroscopic and molecular characteristics of dissolved organic matter release - Xiaoyang Wu; Yifan Liu; Yaofeng Jin; Yue Wang; Mengjie Yuan; Kunyu He; Xiaoyan Zhang; Qin Chen; Zhijing Xue; Rui Wang; Xiaoyun Li (Journal of Hazardous Materials, 2025)

Case study on the combined use of surface seawater injection and depressurization for sustainable natural gas hydrate extraction - Zhaobin Zhang; Yuxuan Li; Shouding Li; Jianming He; Xiao Li; Cheng Lu; Xuwen Qin (Journal of Cleaner Production, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Novel one-step method to construct gellan gum-zein core-shell structured starch beads for regulating starch digestion - Zhiwei Lin; Weixian Li; Chengcheng Zhang; Linjie Zhan; Xiaoyang He; Yang Qin; Qingjie Sun; Na Ji (Food Chemistry, 2025)

Functional design of caprolactam for aliphatic polyamide with enhanced flame retardancy, mechanical robustness, and chemical recyclability - Feng-Ming He; Yan-Fang Xiao; Qin Zhang; Min Jiang; Xin Li; De-Ming Guo; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

An All-Solid-State fluorinated Ion-Conductive elastomer with outstanding mechanical properties and high environmental stability for flexible electronics - Zequan Li; Changsheng Wang; Xueying Duan; Xiangning He; Fuqi Wang; Chuang Ning; Muqun Wang; Zhiyong Qin; Wei Gao; Shuangliang Zhao (Chemical Engineering Journal, 2025)

Antibacterial betaine modified chitosan-based hydrogel with angiogenic property for photothermal enhanced diabetic wound repairing - Kaiyue Zhang; Jingjing Zhu; Weichen Sun; Yu Zhang; Wenjuan Li; Yong Wang; Chengyan Zhou; Yingna He; Jianglei Qin (Carbohydrate Polymers, 2025)

Equol promotes osteogenic differentiation of hPDLSCs by inhibiting oxidative stress via IL1B/NF-κB/CXCL1 signaling axis - Xiaoxi Jiang; Xiao Chen; Lingxiao He; Dan Qin; Minhai Nie; Chunhui Li; Xuqian Liu (Chemico-Biological Interactions, 2025)

Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Loaded Mir-29-3p Targets AhR to Improve Juvenile Idiopathic Arthritis via Inhibiting the Expression of IL-22 in CD4+ T Cell - Xinyi Wei; Kunpeng Sui; Yuanyuan Peng; Sha Li; Yu Fang; Zhi Chen; Xiao Du; Xue Xie; Haiming Tang; QiuYue Wen; JingWei Li; Meilin He; et al. (Stem Cell Reviews and Reports, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Antiviral activity evaluation and action mechanism of chalcone derivatives containing phenoxypyridine - Piao Mao; Li Xing; Bangcan He; Tianyu Deng; Yishan Qin; Yuzhi Hu; Youshan An; Wei Xue (Molecular Diversity, 2025)

Offshore Submerged Aquaculture Flow-Net Interaction Simulation: A Numerical Approach for the Hydrodynamic Characteristics of Nets Produced from Different Materials - Zhiyuan Wang; Wei He; Weiqiang Li; Hongxing Chen; Feng Zhang; Hongling Qin (Journal of Marine Science and Engineering, 2025)
The mechanical and hydrodynamic characteristics of single-piece nets are key to the design and optimization of offshore aquaculture net cages. A numerical approach for offshore submerged aquaculture net materials based on the Morison equations and finite element is proposed, simulating the hydrodynamic characteristics of single-piece nets under varying parameters such as wire diameter, mesh size, and flow velocity, and simulating the impact of marine organism attachment on nets by modifying the drag coefficient. The simulation results of nets made from materials such as Copper–Zinc Alloy (Cu-Zn), Zinc–Aluminum Alloy (Zn-Al), Semi-Rigid Polyethylene Terephthalate (PET), and Ultra-High Molecular Weight Polyethylene (UHMWPE) are compared, which provides a theoretical basis for optimizing design parameters and selecting materials for nets based on force conditions and hydrodynamic characteristics. The simulation results indicate that the current force on the net is positively correlated with flow velocity; the maximum displacement of the net is also positively correlated with the flow rate. Compared to other materials, the Cu-Zn net is subjected to the greatest water flow force, while the UHMWPE net experiences the greatest displacement; the larger the diameter of the netting twine, the greater the current force on the net; the mesh size is inversely related to the current force on the net. With increasing drag coefficient, both the maximum displacement of the net and the current force experiences increase, and UHMWPE material nets are more sensitive to increases in the drag coefficient, which indicates a greater impact from the attachment of marine organisms. The density and elastic modulus of the netting material affect the rate of increase in force on the net. The research results can provide a basis for further research on material selection and design of deep-sea aquaculture nets.

Wave Motion Response Analysis of Flip-Type Ocean Aquaculture Platforms Based on AQWA - Hongling Qin; Li Peng; Zhiyuan Wang; Siqi Wu; Wei He; Yuanping Yang; Jian Li; Hao Zhang (Journal of Marine Science and Engineering, 2025)
The stability of deep-sea aquaculture equipment under extreme sea conditions such as typhoons directly affects the safety and operational reliability of the aquaculture platform, which in turn affects the economic benefits of fish farming. Therefore, it is particularly important to systematically analyze the hydrodynamic response of aquaculture facilities using numerical methods. This paper employs the hydrodynamic analysis software AQWA, integrating the boundary element method of three-dimensional potential flow theory with the Morison equation, to conduct hydrodynamic research on a flip-type aquaculture platform. The calculations include the platform’s amplitude response operators (RAOs), added mass, as well as motion responses and mooring line tensions under extreme sea conditions. The results indicate that the platform’s sway, surge, and heave motions are highly sensitive to wave frequency in the low-frequency range, with a significant resonance phenomenon occurring at a wave frequency of 0.84 Hz. The main wind and wave responses of the platform manifest as surge and roll motions. To address this issue, it is recommended to add additional anchor chains on the short sides of the platform to effectively reduce the amplitude of surge and roll motions. Furthermore, under extreme sea conditions when the platform faces the windward waves on the short side, its motion response frequency is lower than when facing the windward waves on the long side, but the difference in response amplitude between the two conditions is small.

Effects of mono- and multicomponent nonaqueous-phase liquid on the migration and retention of pollutant-degrading bacteria in porous media - Lei He; Ouyang Li; Jianmei Qin; Chunmao Chen; Zhenshan Li; Meiping Tong (Water Research, 2025)

Molecular characterization of MSX2 gene and its role in regulating steroidogenesis in yak (Bos grunniens) cumulus granulosa cells - Jun Ma; Gan Yang; Xuan Qin; Luoyu Mo; Xianrong Xiong; Yan Xiong; Honghong He; Daoliang Lan; Wei Fu; Jian Li; Shi Yin (Theriogenology, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

Characterization of ornithine decarboxylase with histidine decarboxylase activity in natural histidine decarboxylase gene deletion Enterobacter hormaechei RH3 - Huijie Pei; Yilun Wang; Wei He; Yue Zhang; Lamei Yang; Jinhai Li; Yixuan Ma; Xinjie Hu; Shuhong Li; Jianlong Li; Kaidi Hu; Aiping Liu; et al. (Food Microbiology, 2025)

The necessity of enhancing the human health risk assessment of 1,3,6,8-tetrabromocarbazole: Based on in vitro experiments, theoretical calculations, and model predictions - Junchao Ma; Mengxi Ren; Jiangyan He; Pengcheng Shi; Dawei Xing; Xiaochao Tang; Qiang Yang; Yunhong Song; Qiang Li; Tingting Zhao; Chao Qin; Xiaoju Chen (Environmental Pollution, 2025)

Achieving 19.3%-efficiency binary organic solar cells via synergistically dual-phases morphology control - Yushou Zhao; Wenming Li; Xiaofeng Qin; Aiqin Li; Weile Guo; Menglan Lv; Zhicai He; Yong Hua; Dianyong Tang; Bin Zhang (Chemical Engineering Journal, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

CoOx confined in layered montmorillonite serving as PMS activator for wastewater treatment - Piao Xu; Hong Qin; Quyang Tian; Ziwei Wang; Yangzhuo He; Fuqi Wu; Li Du; Guangfu Wang; Wenyang Li; Ying Zeng; Han Wang (Chemical Engineering Journal, 2025)

A β-ketoacyl-CoA synthase encoded by DDP1 controls rice anther dehiscence and pollen fertility by maintaining lipid homeostasis in the tapetum - Yibo Xu; Shixu Zhou; Jingfei Tian; Wenfeng Zhao; Jianxin Wei; Juan He; Wenye Tan; Lianguang Shang; Xinhua He; Rongbai Li; Yongfei Wang; Baoxiang Qin (Theoretical and Applied Genetics, 2025)

Identification and validation of cuproptosis-related genes for diagnosis and therapy in nonalcoholic fatty liver disease - Jinquan Li; Yi Zhang; Xiaohan Ma; Ruiqi Liu; Cuicui Xu; Qin He; Ming Dong (Molecular and Cellular Biochemistry, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Kinetic modeling of sulfonamide degradation by UV/H2O2: Deduction of ROH,UV modeling and application - Xinxin Qin; Xinyue Liu; Yi He; Yichun Zhu; Zuwen Liu; Wentao Li; Mengkai Li; Zhimin Qiang; Junfeng Lian (Chemosphere, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Nitrogen oxides emissions from coastal wetland sediments: Experimental assessment of the influence of vegetation and nitrogen input - Jiang-Chen Gong; Bing-Han Li; Chun-Ying Liu; Qin-Dao Li; Jing-Wen Hu; Pei-Feng Li; Dan He; Gui-Peng Yang (Science of The Total Environment, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Exploring stem cell technology: Pioneering new pathways for female fertility preservation and restoration - Ningjing Li; Xinrong Du; Yuhong Zhao; Qin Zeng; Changli Han; Dongsheng Xiong; Libing He; Guohui Zhang; Weixin Liu (Reproductive Biology, 2024)

Blue carbon storage of tidal flats and salt marshes: A comparative assessment in two Chinese coastal areas - Jinge Zhou; Lulu Zhang; Jingfan Zhang; Shuchai Gan; Zhe Lu; Guoming Qin; Xingyun Huang; Han Chen; Hua He; Yongxing Li; Yingwen Li; Hui Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Enhanced strategies for depressurization in offshore natural gas hydrate exploitation: An in-depth investigation into pathway optimization and production stability mechanisms - Yuxuan Li; Zhaobin Zhang; Shouding Li; Jianming He; Xiao Li; Tao Xu; Cheng Lu; Xuwen Qin (Marine and Petroleum Geology, 2024)

Responses of depth-dependence of C:N:P stoichiometry to check dam in mangrove wetlands - Xingyun Huang; Fangyuan Guan; Yi Zhong; Yu Ni; Ruyi Ding; Guoming Qin; Jinge Zhou; Jingfan Zhang; Han Chen; Hua He; Yingwen Li; Yongxing Li; et al. (Journal of Environmental Management, 2024)

Thyroid hormones and oxidative stress moderated the association between urinary phthalate metabolites and cardiovascular risk factors - Rong He; Hua Bi; Jia He; Yangxu Luo; Xiaotong Li; Qin Li; Rende Huang; Lei Tan (Environmental Pollution, 2024)

Photothermal enhanced antibacterial chitosan-based polydopamine composite hydrogel for hemostasis and burn wound repairing - Liming Chang; Yanai Chen; Min Zhou; Yuanwei Gao; Yong Wang; Wenjuan Li; Zhe Cui; Chengyan Zhou; Yingna He; Jianglei Qin (Carbohydrate Polymers, 2024)

The distribution and driving mechanism of soil inorganic carbon in semi-arid and arid areas: A case study of Alxa region in China - Xinglin Zhu; Jianhua Si; Xiaohui He; Bing Jia; Dongmeng Zhou; Chunlin Wang; Jie Qin; Zijin Liu; Boniface Ndayambaza; Xue Bai; Li Zhang (CATENA, 2024)

rAAV-CRISPR/Cas9-mediated in vivo delivery of porcine embryos to construct knockout pigs - Mengyu Gao; YuTing He; XingLong Zhu; WanLiu Peng; Xinmei Liu; Yanyan Zhou; Yang Deng; Qin Liu; Guangneng Liao; Yi Li; Wei Ni; Guang Yang; et al. (Science China Life Sciences, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Differential analysis of sorting nexin 10 and sterol regulatory element–binding protein 2 expression in inflammatory bowel disease - Bicheng Xie; Anxing Zhang; Canmei Li; Yu Liu; Yao Deng; Ruochang Li; Haichun Qin; Bian Wu; Tian He; Danfeng Lan (Immunologic Research, 2024)

Comparative analyses of immune gene profiles and antioxidant capabilities in the midgut and liver of three species of grass carps (Ctenopharyngodon idella) following gut infection with Aeromonas hydrophila - Wei-Sheng Luo; Zi-Han Xu; Qin-Yang He; Jie Peng; Fei Wang; Jian Li; Sheng-Wei Luo (Aquaculture International, 2024)

Changes in secondary sexual characteristics of female red swamp crayfish (Procambarus clarkii) and relationship to ovarian development: Implications for intensive breeding of seedlings - Lirong Qin; Jinhui He; Kuan Rong; Chao Guo; Jiashou Liu; Tanglin Zhang; Wei Li (Aquaculture, 2024)

Unveiling the toxicological effects and risks of prometryn on red swamp crayfish (Procambarus clarkii): Health assessments, ecological, and molecular insights - Lang Zhang; Ziwei Song; Li He; Shan Zhong; Xiaoqian Ju; Hang Sha; Jing Xu; Qiuying Qin; Jie Peng; Hongwei Liang (Science of The Total Environment, 2024)

Ensuring China's food security in a geographical shift of its grain production: Driving factors, threats, and solutions - Shi Xue; Zhou Fang; Carena van Riper; Wei He; Xuxia Li; Fan Zhang; Ting Wang; Changgao Cheng; Qin Zhou; Zhongde Huang; Yang Bai (Resources, Conservation and Recycling, 2024)

Drinking water safety improvement and future challenge of lakes and reservoirs - Yunlin Zhang; Jianming Deng; Yongqiang Zhou; Yibo Zhang; Boqiang Qin; Chunqiao Song; Kun Shi; Guangwei Zhu; Xuejiao Hou; Yinjun Zhang; Shiwen He; R. Iestyn Woolway; et al. (Science Bulletin, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Impact of COVID-19 on temporal trends and health risks of urinary metal concentrations among residents of Guangzhou, China - Jia Liao; Rende Huang; Xiangyu Jia; Jia He; Qin Li; Xiaotong Li; Jun Yuan; Lei Tan (Environmental Research, 2024)

Hybrid hydrogel loaded with natural plant extract accelerates diabetic wound healing via ROS scavenging and immunoregulation - Xuefeng He; Suyue Gao; Houdong Li; Hengdeng Liu; Shixin Zhao; Hanwen Wang; Shitian Qin; Jingkuang Li; Fei zhou; Julin Xie (Chemical Engineering Journal, 2024)

Fate of soil organic carbon in estuarine mangroves: Evidences from stable isotopes and lignin biomarkers - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; Han Chen; Hua He; Mengxiao Yu; Hui Li; et al. (CATENA, 2024)

Population pharmacokinetics of fluconazole for prevention or treatment of invasive candidiasis in Chinese young infants - Honghong Wang; Dandan Li; Yongjiang Jiang; Jing Liang; Qiaoai Yu; Linghong Kuang; Yuling Huang; Dongjie Qin; Ping Li; Jing He; Feng Xu; Xueli Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Study on the adsorption of phosphate by composite biochar of phosphogypsum and rape straw - Yu Liang; Fengyu Li; Qin Li; Dongsheng He (Environmental Geochemistry and Health, 2024)

Catalytic oxidation of Mn(II) on ferrihydrite and goethite surfaces and the subsequent oxidation and immobilization of coexisting Cr(III) - Rongrong Su; Chunhui Li; Minyu He; Kangsheng Hu; Zhangjie Qin; Shuai Lan (Applied Geochemistry, 2024)

Longitudinal study and predictive modelling of urinary pesticide metabolite concentrations in residents of Guangzhou, China - Xiangyu Jia; Xiaotong Li; Fenfang Deng; Jia He; Qin Li; Chongshan Guo; Jun Yuan; Lei Tan (Chemosphere, 2024)

A critical review on the use of flue gas desulfurization gypsum to ameliorate saline-alkali soils and its prospect for reducing carbon emissions - Haoqian Wang; Feifei Wang; Weiran Qin; Chiquan He; Fushun Wang; Xia Liang; Xiaoping Li (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Insight into the stabilization mechanism of Zn during co-gasification of sewage sludge and coal: Perspective of solid-liquid transition - Tingrui Shi; Yujia Du; Shugang Guo; Yuhong Qin; Chong He; Yuexing Wei; Haofei Li; Wanyao Li (Journal of Environmental Chemical Engineering, 2024)

The metabolic regulation mechanism of gallic acid on biogenic amines and nitrosamines in reduced-nitrite Chinese fermented sausages: A perspective of metabolomics and metagenomics - Qin Zhou; Li Jiang; Jinpeng Zhu; Yunhao Lu; Qiang He (Food Chemistry, 2024)

Corrigendum to “Lactiplantibacillus plantarum causes the abnormal fermentation of bacterial cellulose by Komagataeibacter nataicola during nata de coco production” [Food Bioscience 61 (October 2024) 104603] - Yaqian Yuan; Jiamu Kang; Shuangwen Fei; Xinling Qin; Xue Lin; Xiangrong Wang; Bo Zhao; Cuihua He; Sixin Liu; Congfa Li (Food Bioscience, 2024)

Lactiplantibacillus plantarum causes the abnormal fermentation of bacterial cellulose by Komagataeibacter nataicola during nata de coco production - Yaqian Yuan; Jiamu Kang; Shuangwen Fei; Xinling Qin; Xue Lin; Xiangrong Wang; Bo Zhao; Cuihua He; Sixin Liu; Congfa Li (Food Bioscience, 2024)

Effect of micro-diamond and nano-polycrystalline diamond interfacial microstructure on OLC phase transition - Lifeng Dai; Yanguo Li; Wenqi Luo; He Jia; Yongan Luo; Yanping Yang; Yufei Meng; Xin Han; Wantang Fu; Qin Zou; Yingwei Fei (Chemical Engineering Journal, 2024)

Development of a novel Co-doped carbon fiber from textile waste as catalyst for the highly efficient degradation of organic pollutants: The key role of C–O–Co bond - Bin Fang; Linyu Li; Junmei Guo; Yuhong Qin; Yuexing Wei; Jiansheng Zhang; Chong He; Yichao Chen (Chemical Engineering Journal, 2024)

Performance-based design of residential blocks for the co-benefits of building energy efficiency and outdoor thermal comfort improvement - Shen Xu; Siyao Wang; Gaomei Li; Haizhu Zhou; Chong Meng; Yuchen Qin; Bao-Jie He (Building and Environment, 2024)

A pair of cadinane-type sesquiterpene enantiomers and other chemical constituents from the whole plants of Chloranthus henryi - Meng-Li He; Lian-Lian Xu; Shi-Qin Fu; Yang Liu; Yong-Ming Luo; Fang-You Chen (Biochemical Systematics and Ecology, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

The source of lithium in Lakkor Co Salt Lake on Qinghai-Tibet Plateau, China: evidence from hydrochemical characteristics and boron isotope - Zheng Yan Li; Bin Kai Li; Mao-Yong He; Xue Qin Wen; Jiang Di Zhou (Acta Geochimica, 2024)

Transcriptome analysis reveals hepatic disordered lipid metabolism, lipotoxic injury, and abnormal development in IUGR sheep fetuses due to maternal undernutrition during late pregnancy - Yang Zi; Yulong Qin; Chi Ma; Yina Qiao; Xiaoyi Xu; Yilin Yang; Qiuyue He; Mingyue Li; Yingchun Liu; Feng Gao (Theriogenology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Lanthanum ferrite modified filling materials and its enhancement for phosphorus and COD removal: Performance and mechanism - Qing Li; Bei Yang; Xinyu Chen; Yuting Han; Qin Chen; Shiying He; Yanfang Feng; Yancan Wu; Xiaohui Liang; Lihong Xue; Jie Tang (Journal of Water Process Engineering, 2024)

Acid strength controlled reaction pathways of propylene conversion under olefin cracking conditions over ZSM-5 - Qin Zhao; Fang Li; Yiran Wang; Yueming Liu; Mingyuan He (Fuel, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Evaluation of the anti-atherosclerotic effect for Allium macrostemon Bge. Polysaccharides and structural characterization of its a newly active fructan - Pei Lin; Qiqi Wang; Qi Wang; Jiayun Chen; Liangliang He; Zifei Qin; Shaoping Li; Jingyan Han; Xinsheng Yao; Yang Yu; Zhihong Yao (Carbohydrate Polymers, 2024)

Identification of Different Varieties of Oil Peony Seeds Combining ICP-MS with Chemometrics and Assessment of Associated Health Risk - Shuya Li; Dezhang Zhao; Yuan Shen; Lei Dai; Weihan Qin; Dan Yang; Yaxuan Li; Lin Yang; Yan Li; Dan He (Biological Trace Element Research, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Single-grain luminescence dating of Manas Lake paleoshorelines reveals late quaternary glacial meltwater forced lake level highstand in arid Central Asia - Xiaoyan Wang; Guoqiang Li; He Yang; Yixuan Wang; Ming Jin; Zhongfeng Yan; Caixin Qin; Siyi Gou; Long Pan; Jin Yang (Quaternary Geochronology, 2024)

Increased ecological land and atmospheric CO2 dominate the growth of ecosystem carbon sinks under the regulation of environmental conditions in national key ecological function zones in China - Mengyu Zhang; Honglin He; Li Zhang; Guirui Yu; Xiaoli Ren; Yan Lv; Zhong'en Niu; Keyu Qin; Yanni Gao (Journal of Environmental Management, 2024)

Construction and examination of temperature master curve for asphalt with different aging extents - Wenhao Dong; Feng Ma; Zhen Fu; Wen Qin; Cong Qi; Jiahao He; Chen Li (Fuel, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Metabolomic insights into the effects of seasonal shifts on the dynamic variation of non-volatile compounds of abalone (Haliotis discus hannai) - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Microreactors with multivariate external force field used for the chemical process intensification - Tingting Ma; Shuangfei Zhao; Weiwei Tang; Weiwei Zhong; Yuhang Liu; Yirong Feng; Zheng Fang; Hong Qin; Hong Xu; Yuguang Li; Yue Zhao; Fanrong Meng; et al. (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

Genetic affinity of cave burial and Hmong-Mien populations in Guangxi inferred from ancient genomes - Jianxin Guo; Haifeng He; Guangmao Xie; Le Tao; Xi Mai; Kongyang Zhu; Qiusheng Qin; Xiaomin Yang; Ying Xie; Rui Wang; Hao Ma; Jing Zhao; et al. (Archaeological and Anthropological Sciences, 2024)

Integrating metabolomics and network pharmacology to evaluate the effectiveness of traditional medicinal parts of Chinese herbal medicine Cassia agnes Brenan - Qin Liu; Kuanying Tan; Yi Liu; Xiaohan Tang; Weiqiong Li; Jifei He; Yafang Li; Tao Li; Minggao Zi; Hongyan Yang; Yuyi Chai (South African Journal of Botany, 2024)

Fiddler crab bioturbation stimulates methane emissions in mangroves: Insights into microbial mechanisms - Guoming Qin; Zhe Lu; Shuchai Gan; Lulu Zhang; Jingtao Wu; Christian J. Sanders; Zhili He; Xiaoli Yu; Jingfan Zhang; Jinge Zhou; Ruyi Ding; Xingyun Huang; et al. (Soil Biology and Biochemistry, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Unraveling the relationship between aroma characteristics and lipid profile of abalone (Haliotis discus hannai) during seasonal fluctuation and thermal processing - He-He Tian; Yu-Lian Li; Xu-Song Wang; Xu-Hui Huang; Yu-Ying Zhang; Zi-Chun Zhang; Da-Yong Zhou; Lei Qin (Food Chemistry, 2024)

Microalgae as future food: Rich nutrients, safety, production costs and environmental effects - Le Gao; Yujia Qin; Xu Zhou; Wenbiao Jin; Zhongqi He; Xuan Li; Qilin Wang (Science of The Total Environment, 2024)

Anemhupehins D F, sterols and chromone derivative from Anemone hupehensis and their anti-inflammatory activity - Jin-Lei Ning; Ning Qin; Hong-Fei Li; Xi-Yue Ma; Fei Zhang; Tao Feng; Juan He (Phytochemistry Letters, 2024)

Phosphorus desorption regulates phosphorus fraction dynamics in soil aggregates of revegetated ecosystems - Chengyi Li; Mingzhu He; Chunming Xin; Huijun Qin; Zhaohui Zhang (Journal of Environmental Management, 2024)

Zn stabilization mechanism during the gasification-melting of sewage sludge - Tingrui Shi; Yujia Du; Shugang Guo; Yuhong Qin; Chong He; Yuexing Wei; Haofei Li (Fuel, 2024)

Emulsion stability enhancement against storage and environment stresses using complex plant protein and betanin - Qin Geng; Ting Hu; Jun Chen; Changhong Li; Ti Li; Xuemei He; Jialong Han; Chengmei Liu; Taotao Dai (Food Bioscience, 2024)

Layer-by-layer self-assembly of durable, breathable and enhanced performance thermoelectric fabrics for collaborative monitoring of human signal - Xinyang He; Chengzu Li; Suiyuan Zhu; Jiaxin Cai; Gui Yang; Yunna Hao; Yunhe Shi; Rongwu Wang; Liming Wang; Xinxin Li; Xiaohong Qin (Chemical Engineering Journal, 2024)

Biodegradable and flame-retardant cellulose-based wearable triboelectric nanogenerator for mechanical energy harvesting in firefighting clothing - Zhicai Yu; Zhenyu Zhu; Yingzi Zhang; Xiaoqian Li; Xin Liu; Yi Qin; Zhenrong Zheng; Lianyang Zhang; Hualing He (Carbohydrate Polymers, 2024)

A novel deep-learning model based on τ-shaped convolutional network (τNet) with long short-term memory (LSTM) for physiological fatigue detection from EEG and EOG signals - Le He; Li Zhang; Xiangtian Lin; Yunfeng Qin (Medical & Biological Engineering & Computing, 2024)

Spatial and diel variations of bacterioplankton and pico-nanoeukaryote communities and potential biotic interactions during macroalgal blooms - Cui He; Guihao Li; Songbao Zou; Pengfei Zheng; Qinqin Song; Guanzhe Li; Qin Yu; Yunjun Yu; Qianqian Zhang; Xiaoli Zhang; Zhuo Shen; Jun Gong (Marine Pollution Bulletin, 2024)

Investigating the cooling effects of land cover and landscape patterns surrounding rivers: Insights from the subtropical city of Changsha, China - Jie Tan; Wenjun Kuang; De Yu; Weijun Zhou; Xigui Li; Qin Liu; Libo He (Urban Climate, 2024)

Unraveling the intrinsic mechanism behind the retention of arsenic in the co-gasification of coal and sewage sludge: Focus on the role of Ca and Fe compounds - Yujia Du; Tingrui Shi; Shugang Guo; Hugang Li; Yuhong Qin; Yuefeng Wang; Chong He; Yuexing Wei (Journal of Hazardous Materials, 2024)

Summer heatwaves promote harmful algal blooms in the Fuchunjiang Reservoir, an important drinking water source - Shiwen He; Yunlin Zhang; Na Li; Kun Shi; Yibo Zhang; Boqiang Qin; Guangwei Zhu; Mingliang Liu; Keqiang Shao (Journal of Environmental Management, 2024)

Experimental transformation of nontronite to kaolinite: implication for ferrallitization of Fe/Mg-rich clays in compositional stratigraphy on Mars - Xiaorong Qin; Jiacheng Liu; Wei Tan; Hongping He; Joseph Michalski; Yu Sun; Shangying Li; Binlong Ye; Yiping Yang; Yiliang Li (Icarus, 2024)

Optimizing fracturing techniques for enhanced hydrate dissociation in low-permeability reservoirs: Insights from numerical simulation - Zhaobin Zhang; Tao Xu; Shouding Li; Jianming He; Xiao Li; Yuxuan Li; Cheng Lu; Xuwen Qin (Gas Science and Engineering, 2024)

Influence of velocity on the transient auto-ignition of ethylene jet in a hot coflow - Bing Liu; Yuxue Li; Guoqiang He; Xin Yu; Jian An; Shaohua Zhu; Fei Qin (Fuel, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Full-Color upconversion luminescence nanoplatform for real three-dimensional volumetric color displays - Heng Jia; Jia Zhao; Zhiqiang Huo; Xiaorui Feng; Weixia Liu; Shaohong Guo; Nan Li; Daguang Li; Yu Yang; Weiyan He; Yingyue Teng; Weiping Qin (Chemical Engineering Journal, 2024)

Refining granite generation by interrogation of zircon and monazite U-Th-Pb and Hf/Nd-O isotopes - Xing Zhang; Yuanbao Wu; Bin Fu; Wenxiang Zhang; Long Li; Guangyan Zhou; Rui Li; Zhaochu Hu; Yu He; Zhengwei Qin (Chemical Geology, 2024)

Development of a stable genetic transformation system in Erigeron breviscapus: a case study with EbYUC2 in relation to leaf number and flowering time - Qin Zhu; Ying-Chun Lu; Jing-Lei Xiong; Yun-Hui Yang; Jian-Li Yang; Sheng-Chao Yang; Guang-Hui Zhang; Ben-Cai Sha; Si-Mei He (Planta, 2024)

Origin and evolution of Li-rich geothermal waters from the Kawu geothermal system, Himalayas: based on hydrochemistry and H-O, Li isotopes - Zhipeng Qin; Liangyin He; Ji Duo; Mingli Li; Yonglin Li; Qiuding Du; Gangyang Zhang; Guodong Wu; Gaoling Liu (International Geology Review, 2024)

Pollution levels and ecological risks of PPCPs in water and sediment samples of Danjiangkou Reservoir - Haiyang Jin; Chan Yu; Li Lin; Jinghua Cheng; He Qin; Jingxiang Tao; Shengfei Deng (Environmental Science and Pollution Research, 2024)

Quenching residual H2O2 from UV/H2O2 with granular activated carbon: A significant impact of bicarbonate - Jinfeng Zeng; Miao Zhang; Xinxin Qin; Yi He; Xinyue Liu; Yichun Zhu; Zuwen Liu; Wentao Li; Huiyu Dong; Zhimin Qiang; Junfeng Lian (Chemosphere, 2024)

Visible light-enhancing antibacterial ability of gold ions for its application of the prevention and treatment of dentin caries - Kangjing Li; Beibei Xie; Jun Zhou; Chunyun Liang; Cong Liu; Yiwu Qin; Fengyuan Zhou; Xuan He; Zhiyong Chen; Xiaoping Su; Ying Luo; Cuiping Li; et al. (Journal of Cleaner Production, 2024)

Rational design of cationic starch with high purification performance and insight into the working mechanism - Mingyuan Liu; Yuchen Meng; Xinyang He; Jiatai Gu; Zhen Li; Shu Yang; Yue Zhang; Maorong Zheng; Liming Wang; Xiaohong Qin (Journal of Cleaner Production, 2024)

Asynchronous Holocene human population changes in north and south China as related to animal resource utilization - Yanyan Yu; Jie Yu; Haibin Wu; Feng He; Stephen J. Vavrus; Amber Johnson; Wenchao Zhang; Qin Li; Zhengtang Guo (Global and Planetary Change, 2024)

Study on color, aroma, and taste formation mechanism of large-leaf yellow tea during an innovative manufacturing process - Yuchuan Li; Qianqian Luo; Muxue Qin; Wenluan Xu; Xiaoyong Wang; Jingtao Zhou; Chang He; Yuqiong Chen; Zhi Yu; Dejiang Ni (Food Chemistry, 2024)

Ultra-sensitive and stable All-Fiber iontronic tactile sensors under high pressure for human movement monitoring and rehabilitation assessment - Ke Ma; Daojian Su; Bolong Qin; Junxian Li; Jiaming Zhong; Chi Zhang; Fuqin Deng; Gengzhe Shen; Weijia Yang; Yue Xin; Xin He (Chemical Engineering Journal, 2024)

Seasonally extreme temperature events accelerate in arid northwestern China during 1979–2018 - Rao Zhu; Xuejiao Wu; Wei Zhang; Jianqiao He; Yu Qin; Ziqiang Li; Yongping Shen (Atmospheric Research, 2024)

Fabricating Composite Cell Sheets for Wound Healing: Cell Sheets Based on the Communication Between BMSCs and HFSCs Facilitate Full-Thickness Cutaneous Wound Healing - Gongjian Li; Qin Wang; Hao Liu; Zuojun Yang; Yuhan Wu; Li He; Xiaoyuan Deng (Tissue Engineering and Regenerative Medicine, 2024)

Blocking-baffle mechanism of vegetation to rock avalanche on the forested slope of the east Sichuan-Tibet Mountains - Yong Wu; Zhang-qing Wang; Xin-po Li; Siming He; Xiao-qin Lei (Landslides, 2024)

Transcriptome and metabolome analysis reveals the salt stress-response mechanism in desert isolated Chlorella sp. DT025 - Bangxiang He; Wenna Dai; Qin Zhang; Zhengsheng Shi; Yanbin Li; Huiling Wang (Algal Research, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Monitoring of farmland dust during tillage and sowing operations and comparative analysis of cultivation modes in the suburban areas of Beijing - Guibin Chen; Qingjie Wang; Hongwen Li; Jin He; Caiyun Lu; Wenhao Qin; Luncong Mao (Soil and Tillage Research, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

The pre-corrosion fatigue behavior of 321 steel coated by laser additively manufactured FeCoNiCrMn high-entropy alloy - Wei Li; Shengnan Hu; Shunpeng Zhu; Guowei Bo; Chipeng Zhang; Houjun Qin; Hui Chen; Libo Zhou; Xulong Peng; Jianjun He; Cong Li; Shengde Zhang; et al. (Ocean Engineering, 2024)

System stability associated with different lipid contents during mesophilic anaerobic digestion of lipid-rich food waste - Yuanyuan Ren; Yemei Li; Ziang He; Yu Qin; Takashi Sakamaki; Yu-You Li (Journal of Cleaner Production, 2024)

In vitro digestion and fecal fermentation of encapsulated starch constructed via layer-by-layer coating of calcium alginate - Congli Cui; Mingju Li; Xiaoyang He; Na Ji; Yang Qin; Lei Dai; Liu Xiong; Qingjie Sun (Food Hydrocolloids, 2024)

Polynorepinephrine-regulated filler sulfonation toward interfacial reformation and conductive promotion of nanocomposite proton exchange membrane - Tong Huang; Xin Liu; Ruibin Ma; Yangyang Gao; Xiaomin Xu; Chengrun Yan; Yuchen Guo; Xiaoxu Li; Yanzhou Qin; Lingling Liu; Jiandang Xue; Huadong Huang; et al. (Chemical Engineering Journal, 2024)

Positive effects of plant species diversity on organic carbon accumulation in soil aggregates driven by mineral protection in a subtropical forest in southwest China - Chenxi Sun; Feilong Li; Xinnuo He; Zongyao Qian; Yunbin Qin (Journal of Soils and Sediments, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Effects of soy isoflavones on growth performance, antioxidant capacity, non-specific immunity and lipid metabolism of juvenile Chinese mitten crab, Eriocheir sinensis - Long He; Han Wang; Erchao Li; Qincheng Huang; Xiaodan Wang; Fang Qiao; Chuanjie Qin; Jianguang Qin; Liqiao Chen (Aquaculture, 2024)

Electrochemical selective lithium extraction and regeneration of spent lithium iron phosphate - Zijun Qin; Xiaohui Li; Xinjie Shen; Yi Cheng; Feixiang Wu; Yunjiao Li; Zhenjiang He (Waste Management, 2024)

Motility-related microRNAs identified in pig seminal plasma exosomes by high-throughput small RNA sequencing - Yunxiang Zhao; Jiali Qin; Jingshuai Sun; Jian He; Yanmei Sun; Renqiang Yuan; Zhili Li (Theriogenology, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Enantiomeric α-pyrone derivatives with immunosuppressive activity from Talaromyces adpressus - Meijia Zheng; Chenxi Zhou; Hong Liao; Qin Li; Alan Bao; Chunmei Chen; Feng He; Peng Wu; Weiguang Sun; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2024)

A novel cold-adapted pyrethroid-degrading esterase from Bacillus subtilis J6 and its application for pyrethroid-residual alleviation in food matrix - Mengmei Zhang; Kun Yang; Li Yang; Yangyu Diao; Xingjie Wang; Kaidi Hu; Qin Li; Jianlong Li; Ning Zhao; Li He; Shujuan Chen; Aiping Liu; et al. (Journal of Hazardous Materials, 2024)

Potential agricultural contamination and environmental risk of phthalate acid esters arrived from plastic film mulching - Jixiao Cui; Runhao Bai; Weili Ding; Qin Liu; Qi Liu; Wenqing He; Changrong Yan; Zhen Li (Journal of Environmental Chemical Engineering, 2024)

Study on the decarbonization mechanism of composite adsorbent by Mg-MOF-74-based modified biochar - Chenxing Wang; Li Jia; Shuning Qin; Ling He; Yawen Wu; Qingrui Liu; Yan Jin (Fuel, 2024)

Exergetic and exergoeconomic evaluation of an SOFC-Engine-ORC hybrid power generation system with methanol for ship application - Chengjie Li; Zixuan Wang; He Liu; Fafu Guo; Chenghao Li; Xinyan Xiu; Cong Wang; Jiang Qin; Liqiu Wei (Fuel, 2024)

Characteristic volatiles of Fu brick tea formed primarily by extracellular enzymes during Aspergillus cristatus fermentation - Zhong Wang; Qifang Jin; Ronggang Jiang; Yang Liu; He Xie; Xingchang Ou; Qin Li; Zhonghua Liu; Jian'an Huang (Food Research International, 2024)

Enocyanin alleviates experimental colitis and restores gut microbiota homeostasis as functional foods - Cang Li; Yu Huang; Meilin Qin; Qian He; Zhuoyu Lin; Xiaojing Zhang; Hao Ren; Dan Xu; Xiaoping Liao; Yahong Liu; Jian Sun (Food Bioscience, 2024)

Dual-specificity phosphatase 1 inhibits Singapore grouper iridovirus replication via regulating apoptosis in Epinephelus coioides - Jia-Yang He; Yi-Jie Cai; Yong-Xuan Li; Wei Huang; Yue Zhang; Ke-Jian Liu; Zhuo Sun; Li-Ling Dai; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Manganese-induced neurological pyroptosis: Unveiling the mechanism through the ROS activaed Caspase-3/GSDME signaling pathway - Jiacheng He; Xiaoli Ma; Jie Zhang; Yi-ping Yang; Huiyan Qin; Hao Chen; Shengtao Wei; Fangfei Li; Jian Wang; Guiqiang Liang; Yunfeng Zou (Food and Chemical Toxicology, 2024)

Low variation in microbial carbon sequestration between farmland and apple orchards in typical loess-covered regions - Wangjia Ji; Ruifeng Li; Zhuohang Jin; Miao Qin; Xiaoling He; Zhi Li (Agriculture, Ecosystems & Environment, 2024)

Particle size-dependent and route-specific exposure to liquid crystal monomers in indoor air: Implications for human health risk estimations - Huiju Lin; Xinxing Li; Xian Qin; Yaru Cao; Yuefei Ruan; Michael K.H. Leung; Kenneth M.Y. Leung; Paul K.S. Lam; Yuhe He (Science of The Total Environment, 2024)

The carbon budget of China: 1980–2021 - Xiaosheng Xia; Peiyang Ren; Xuhui Wang; Dan Liu; Xiuzhi Chen; Li Dan; Bin He; Honglin He; Weimin Ju; Minqi Liang; Xingjie Lu; Jing Peng; et al. (Science Bulletin, 2024)

Disruption of the rice ALS1 localized in chloroplast causes seedling-lethal albino phenotype - Yibo Xu; Zishuai Wu; Wei Shen; Haiyu Zhou; Hu Li; Xinhua He; Rongbai Li; Baoxiang Qin (Plant Science, 2024)

Undescribed indole lactones from Alstonia scholaris protecting hepatic cell damage - Bin-Yuan Hu; Yun-Li Zhao; Ying-Jie He; Yan Qin; Xiao-Dong Luo (Phytochemistry, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Copper selenide anchored on Ti3C2 MXene via Lewis acidic etching route for efficient removal of gaseous elemental mercury - Wei Zheng; Zequn Yang; Jiefeng Chen; Weizhen He; Ruiyang Qin; Hongxiao Zu; Wenqi Qu; Jianping Yang; Lijian Leng; Hailong Li (Fuel, 2024)

Plant functional traits and tree size inequality improved individual tree height prediction of mid-montane humid evergreen broad-leaved forests in southwest China - Yuan Feng; Yong Chai; Yangping Qin; Guixiang Li; Liping He; Zhenghai Zhang; Li Wu; Guangtao Meng (Forest Ecology and Management, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Lipopolysaccharide alters VEGF-A secretion of mesenchymal stem cells via the integrin β3-PI3K-AKT pathway - Shuya Mei; Shaojie Qin; Ri Tang; Qiaoyi Xu; Yue Hu; Jinhua Feng; Zhengyu He; Yuan Gao; Hui Li; Shunpeng Xing (Molecular & Cellular Toxicology, 2024)

Isolation, identification, and induced differentiation of satellite cells from skeletal muscle of adult tree shrews - Shenghui Ke; Yiwei Feng; Liying Luo; Wanzhao Qin; Huayu Liu; Jingchong Nie; Beijiang Liang; Hongjie Ma; Mao Xie; Jingyu Li; Zhijie Niu; Guojian Li; et al. (In Vitro Cellular & Developmental Biology - Animal, 2024)

Metabolic pathways of methylmercury in rotifer Brachionus plicatilis - Hangyu Lin; Xiaodong Mao; Yanlin Wei; Songzhang Li; Jianguang Qin; Song Zhu; Shengqi Su; Tao He (Science of The Total Environment, 2023)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

Discharge dynamics of agricultural diffuse pollution under different rainfall patterns in the middle Yangtze river - Qin Li; Wei Ouyang; Jing Zhu; Chunye Lin; Mengchang He (Journal of Environmental Management, 2023)

Highly efficient removal of Aflatoxin B1 employing a flower-like covalent organic framework-based fiber membrane - Shuning Li; Kang Qin; Yixue Fu; Defu He; Dianpeng Han; Shuang Li; Yu Wang; Shuyue Ren; Yuan Peng; Zhixian Gao (Journal of Environmental Chemical Engineering, 2023)

Regionally spatial framework Al distribution in MFI channels and its impact on the n-butane cracking reaction pathways - Linjie Guan; Meiyu Liu; Honghai Liu; Li Zhang; Yiming Zhang; Yucai Qin; Binbin He; Yi Mei; Yun Zu (Fuel, 2023)

Thiol-modified hyaluronic acid improves the physical stability of curcumin-zein nanoparticles by forming disulfide bonds with zein - Guangshuai Zhang; Mengdi Qin; Mengran Guo; Mo Li; Di Zhang; Yichi Sun; Bingyang Liu; Zhonggui He; Qiang Fu (Food Chemistry, 2023)

Distribution heterogeneity of sediment bacterial community in the river-lake system impacted by nonferrous metal mines: Diversity, composition and co-occurrence patterns - Aihua Wang; Mengchang He; Huiji Liu; Wei Ouyang; Xinyi Liu; Qin Li; Chunye Lin; Xitao Liu (Environmental Pollution, 2023)

Phosphoproteomic Analysis Reveals the Predominating Cellular Processes and the Involved Key Phosphoproteins Essential for the Proliferation of Toxoplasma gondii - Xin-zhu Chen; Rui-xue Bai; Fei-yu Qin; Hong-juan Peng; Jin-feng Ren; Lang Hu; Yu-di Li; Cheng He (Acta Parasitologica, 2023)

Anti-contactin-associated protein-like 2 antibody autoimmune encephalitis with rapidly progressive parkinsonism: a case report and literature review - Xiaohong Qin; Jieying Li; Yuanyuan Luo; Yunsen He; Xiaoqiang Xiao; Arui Tan; Jun Xiao (Acta Neurologica Belgica, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

Public responses to urban heat and payment for heat-resilient infrastructure: implications for heat action plan formulation - Li Yan; Mingqiang Yin; Hongmei Yu; Guojin Qin; Bao-Jie He (Environmental Science and Pollution Research, 2023)

Adverse effects of thiamethoxam on the behavior, biochemical responses, hepatopancreas health, transcriptome and intestinal flora of juvenile Chinese mitten crab (Eriocheir sinensis) - Yiwen Yang; Cong Zhang; Xiaodan Wang; Qiuran Yu; Long He; Xinyu Cai; Erchao Li; Chuanjie Qin; Jianguang Qin; Liqiao Chen (Chemosphere, 2023)

Flagellar gene fliP contributes to the virulence of Pseudomonas plecoglossicida by regulating its motility - Li He; Lingmin Zhao; Qi Li; Lixing Huang; Yingxue Qin; Zhixia Zhuang; Xiaoru Wang; Huabin Huang; Jiaonan Zhang; Jiaolin Zhang; Qingpi Yan (Aquaculture, 2023)

Progress on the roles of zinc in sperm cryopreservation - Yuanyou Li; Shaoyu Qin; Wenfei Cui; Fan Zhao; Meiling He; Zhongliang Jiang (Theriogenology, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Separation and recovery of indium in hazardous liquid crystal display treatment by a novel silica adsorbent: Study on adsorption mechanism and process design - Jianchun Qin; Shunyan Ning; Jianing Xu; Jishu Zeng; Zheyu He; Liang Luo; Fengtao Hu; Yimin Li; Toyohisa Fujita; Yuezhou Wei (Journal of Cleaner Production, 2023)

Determination of multiclass contaminants in chilli powder based on magnetic multiwalled carbon nanotubes and UPLC-QTOF/MS - Guangyun He; Xue Hou; Mei Han; Shiting Qiu; Xi Yu; Shudi Qin; Fengyi Wang; Ying Li (Food Research International, 2023)

Characterization of the key odor-active compounds in different aroma types of Fu brick tea using HS-SPME/GC-MSO combined with sensory-directed flavor analysis - Xuexue Zheng; Tengfei Hu; He Xie; Xingchang Ou; Jianan Huang; Chao Wang; Zhonghua Liu; Qin Li (Food Chemistry, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Distinct and shared endothermic strategies in the heat producing tissues of tuna and other teleosts - Baosheng Wu; Xueli Gao; Mingling Hu; Jing Hu; Tianming Lan; Tingfeng Xue; Wenjie Xu; Chenglong Zhu; Yuan Yuan; Jiangmin Zheng; Tao Qin; Peidong Xin; et al. (Science China Life Sciences, 2023)

Will different land uses affect heavy metal pollution in soils of roadside trees? An empirical study from Shanghai - Kun He; Junjie Wang; Hefang Geng; Zhenyan Qin; Nan Li; Yanting Zhang; Ruiqing Yang; Shucheng Feng; Benyao Wang (Environmental Monitoring and Assessment, 2023)

Discrimination of Schizothorax grahami (Regan, 1904) Stocks Based on Otolith Morphology - Yang Zhou; Li Xu; Zhongtang He; Weijie Cui; Qun Lu; Jianguang Qin; Shengqi Su; Tao He (Fishes, 2023)
Otoliths grow throughout a fish’s life and are important for identifying fish stocks and fish age. This study aims to differentiate different stocks of Schizothorax grahami (Regan, 1904) in the Chishui River, an upper reach of the Yangtze River, by otolith morphology. The otolith morphology of S. grahami from three different river sections was analyzed using the Shape Index, Fourier coefficients, and wavelet coefficients. The composite discrimination success rate of the Shape Index was 59.7%, and it was difficult to distinguish in the scatter plots. In contrast, canonical principal coordinate scatter plots clearly showed three distinguished stocks. The above results indicate that otolith morphology can discriminate between stocks in plateau endemic fish, and several S. grahami stocks may be separately managed in the Chishui River.

Prophylactic norepinephrine combined with 6% hydroxyethyl starch (130/0.4) co-load infusion for preventing postspinal anesthesia hypotension during cesarean section: a randomized, controlled, dose-finding trial - Lei Guo; Xiangsheng Xiong; Rui Qin; Zhenzhou Li; Yongqiang Shi; Wei Xue; Ling He; Shuqin Ma; Yi Chen (DARU Journal of Pharmaceutical Sciences, 2023)

Dynamics and performance evaluation of wind-induced vibration of a cuboid bluff body with two ornaments - He Ren; Tian-yu Zheng; Wen-yuan Lin; Hai-Tao Li; Wei-Yang Qin; Daniil Yurchenko (Ocean Engineering, 2023)

High-resolution luminescence chronology of loess-paleosols reveals East Asian summer monsoon and winter monsoon variation in Hexi Corridor during the past 25 kyr - Guoqiang Li; Yixuan Wang; Zhongfeng Yan; Caixin Qin; Weiping Ding; He Yang; Xiaoyan Wang; Xiaojian Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Chromium isotope system of intraplate basaltic lavas: Implication for recycling materials into mantle - Ji Shen; Zhiwei Zuo; YongSheng He; Shuguang Li; Jian Huang; Gang Zeng; Liping Qin (Lithos, 2023)

Enhancing crop resilience: Understanding the role of drought priming in wheat stress response - Xiao Wang; Jiakun Ge; Mengting He; Qing Li; Jian Cai; Qin Zhou; Yingxin Zhong; Bernd Wollenweber; Dong Jiang (Field Crops Research, 2023)

In-situ growth of VS4 nanorods on Ni-Fe sulfides nanoplate array towards achieving a highly efficient and bifunctional electrocatalyst for total water splitting - Yujia He; Jun Shen; Qin Li; Xiuzhang Zheng; Zixuan Wang; Liang Cui; Jiangtao Xu; Jingquan Liu (Chemical Engineering Journal, 2023)

Advanced cobalt-ferrite layered double hydroxides sandwich-structured nanozymes for ROS-bloomed tumor therapy - Siyi Li; Xiucheng Zhao; He Ding; Jinhu Chang; Xiran Qin; Fei He; Xiangyang Gao; Shili Gai; Piaoping Yang (Chemical Engineering Journal, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

Coupled systems of pre-denitrification and partial nitritation/anammox improved functional microbial structure and nitrogen removal in treating swine manure digestate - Yunzhi Qian; Shilong He; Fuqiang Chen; Junhao Shen; Yan Guo; Yu Qin; Yu-You Li (Bioresource Technology, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

Chemical constituents of Aspergillus udagawae isolated from the soil of the Xingren coal areas and their antibacterial activities - Xing-Mei Long; Qin-Feng Zhu; Bing Wang; Guang-Gui Chen; Kai-Yu Li; Xun He; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2023)

Development and potential use of Pseudomonas plecoglossicida mutant ΔOmpRΔrpoS as a live attenuated vaccine against visceral white nodules disease in large yellow croaker (Larimichthys crocea) - Liangyin He; Youshen Li; Jiale Kang; Jianxin Li; Hetron Mweemba Munang'andu; Cheng Xu; Pan Qin; Xinhua Chen (Aquaculture, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

Pseudomonas plecoglossicida fliP gene affects the immune response of Epinephelus fuscoguttatus ♀×Epinephelus lanceolatus ♂ to infection - Li He; Lingmin Zhao; Qi Li; Lixing Huang; Yingxue Qin; Zhixia Zhuang; Xiaoru Wang; Huabin Huang; Jiaonan Zhang; Jiaolin Zhang; Qingpi Yan (Fish & Shellfish Immunology, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Effective Catalytic of Rice Straw Pyrolysis over Ni/CaZnAl Catalyst for Producing Hydrogen-Rich Syngas - Rongyi Gao; Longkai Zhu; Mingtai Zhou; Zhen Wang; Yun He; Zhenhua Qin; Jianfen Li (BioEnergy Research, 2023)

Alkaloids from lotus ( Nelumbo nucifera ): recent advances in biosynthesis, pharmacokinetics, bioactivity, safety, and industrial applications - Zhenyu Wang; Yong Li; Dandan Ma; Maomao Zeng; Zhaojun Wang; Fang Qin; Jie Chen; Mark Christian; Zhiyong He (Critical Reviews in Food Science and Nutrition, 2023)

XBP1s gene of endoplasmic reticulum stress enhances proliferation and osteogenesis of human periodontal ligament cells - Ziwei Cui; Ruoshan Qin; Jianbao Feng; Yuan Liu; Xiongtao Zhou; Xiaodong Qin; Yanmin Li; Zhidong Zhang; Xiangyi He (Tissue and Cell, 2023)

4-hydroxylonchocarpin and corylifol A: The potential hepatotoxic components of Psoralea corylifolia L - Linqi Ouyang; Zhiqiang Fan; Yang He; Long Tan; Guoyan Deng; Qin He; Yiran He; Ting Ouyang; Congjie Li; Qin Zhang; Hongyu Liu; Yajie Zuo (Toxicology Letters, 2023)

Nitrogen rather than carbon released by litter decomposition mediates nutrient relationships in a multispecies forest plantation with hemiparasite - Fangcuo Qin; Junkun Lu; Zhenshuang Li; Sen Meng; Shengkun Wang; Junfeng Liang; Xinhua He (Science of The Total Environment, 2023)

Synthesis, and biological evaluation of pyrazole matrine derivatives as an insecticide against Spodoptera frugiperda - Xingan Cheng; Fangyun Dong; Junjie Li; Qiwen Zou; Xin Liu; Huiqing He; Hanhui Zhang; Xiaojing Lv; Yuehua Wu; Xuhong Jiang; Xiangjing Qin (Pesticide Biochemistry and Physiology, 2023)

NaHCO3 synergistic electrokinetics extraction of F, P, and Mn from phosphate ore flotation tailings - Caiyue Jin; Bangjin Chen; Guangfei Qu; Jin Qin; Jieqian Yang; Ye Liu; Hailin Li; Fenghui Wu; Minjie He (Journal of Water Process Engineering, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Regulation of proliferation and apoptosis of aging periodontal ligament cells by autophagy-related gene 7 - Yiheng Wang; Xinyi Li; Xiongtao Zhou; Tao Wang; Yuan Liu; Jianbao Feng; Xiaodong Qin; Zhidong Zhang; Yanmin Li; Xiangyi He (Molecular Biology Reports, 2023)

Priming effect stimulates carbon release from thawed permafrost - Mei He; Qinlu Li; Leiyi Chen; Shuqi Qin; Yakov Kuzyakov; Yang Liu; Dianye Zhang; Xuehui Feng; Dan Kou; Tonghua Wu; Yuanhe Yang (Global Change Biology, 2023)
Climate warming leads to widespread permafrost thaw with a fraction of the thawed permafrost carbon (C) being released as carbon dioxide (CO 2 ), thus triggering a positive permafrost C‐climate feedback. However, large uncertainty exists in the size of this model‐projected feedback, partly owing to the limited understanding of permafrost CO 2 release through the priming effect (i.e., the stimulation of soil organic matter decomposition by external C inputs) upon thaw. By combining permafrost sampling from 24 sites on the Tibetan Plateau and laboratory incubation, we detected an overall positive priming effect (an increase in soil C decomposition by up to 31%) upon permafrost thaw, which increased with permafrost C density (C storage per area). We then assessed the magnitude of thawed permafrost C under future climate scenarios by coupling increases in active layer thickness over half a century with spatial and vertical distributions of soil C density. The thawed C stocks in the top 3 m of soils from the present (2000–2015) to the future period (2061–2080) were estimated at 1.0 (95% confidence interval (CI): 0.8–1.2) and 1.3 (95% CI: 1.0–1.7) Pg (1 Pg = 10 15 g) C under moderate and high Representative Concentration Pathway (RCP) scenarios 4.5 and 8.5, respectively. We further predicted permafrost priming effect potential (priming intensity under optimal conditions) based on the thawed C and the empirical relationship between the priming effect and permafrost C density. By the period 2061–2080, the regional priming potentials could be 8.8 (95% CI: 7.4–10.2) and 10.0 (95% CI: 8.3–11.6) Tg (1 Tg = 10 12 g) C year −1 under the RCP 4.5 and RCP 8.5 scenarios, respectively. This large CO 2 emission potential induced by the priming effect highlights the complex permafrost C dynamics upon thaw, potentially reinforcing permafrost C‐climate feedback.

Taxonomic and Morpho-Functional Photosynthetic Patterns of 18 Intertidal Macroalgal Species in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Quan He; Linqing Liu; Yujie Qin; Qiang Lin; Guangyan Ni; Binbin Chen; Zengling Ma; Dinghui Zou; Gang Li (Journal of Marine Science and Engineering, 2023)
Macroalgae provide food for microbial, meio- and macro-faunal communities in coastal ecosystems, thus mediating nutrient dynamics and functions in these ecosystems. Because of this vital role, it is important to clarify physiological information about macroalgae as it reflects their growth potential in the field. In this study, we examined the biomass, pigment content, and photosynthetic O2 evolution rate versus irradiance curves of 18 macroalgal species from the intertidal zone of the Guangdong–Hong Kong–Macao Greater Bay Area, China, and investigated their photosynthetic patterns in relation to phyla characteristics, morphology, and growth locations. The results showed that green algae had the highest maximum photosynthetic O2 evolution rate (Pmax), light utilization efficiency (α), and dark respiration (Rd) among the three macroalgal phyla; the sheet-like macroalgal species had the highest Pmax, α, and Rd among the four morphological categories. The macroalgal species in the upper intertidal zone showed higher Pmax and α and lower saturation irradiance (EK) and compensation irradiance (EC) than those species in the lower intertidal location. The PCA results showed that the biomass of sheet-like macroalgal species was positively correlated with factor PC1 (50.34%), and that of finely branched species was negatively correlated with factor PC2 (25.17%). In addition, our results indicate that the light absorption and utilization capabilities of macroalgae could determine whether they could dominate the intertidal zone and that their photosynthetic characteristics could be used as a potential indicator of their biomass distribution in the Greater Bay Area.

Two new isoquinolines from Corydalis saxicola - Zhi-Wei Ouyang; Ji-Man He; Feng Qin; Ling Li; Wen-Di Tang; Dian-Peng Li; Jiang-Ke Qin (Natural Product Research, 2023)

Ca2+/pH-triggered gelation of Pickering emulsion in vitro digestion: Visualization and sustained-release performance - Haifang Liu; Riting Huang; Xinyu Zhao; Shujuan Yang; Furui He; Wenqi Qin; Junhao Huang; Gaobo Yu; Yuhong Feng; Jiacheng Li; Chenghong Liao (Food Hydrocolloids, 2023)

Research on the blocking effect of baffle-net structure on rock avalanches: consider the influence of particle splashing - Yu-Zhang Bi; Dong-Po Wang; Shuai-Xing Yan; Qin-Ze Li; Si-Ming He (Bulletin of Engineering Geology and the Environment, 2023)

Hearing loss increases all-cause and cardiovascular mortality in middle-aged and older Chinese adults: the Dongfeng-Tongji Cohort Study - Haiqing Zhang; Qin Fang; Meng Li; Liangle Yang; Xuefeng Lai; Hao Wang; Meian He; Zhichao Wang; Weijia Kong; Xiaomin Zhang (Environmental Science and Pollution Research, 2023)

From the Yanshan orogeny to Late Mesozoic multi-plate convergence in East Asia - Qin Wang; Weidong Sun; Michel Faure; He Li (Tectonophysics, 2023)

Short-term cultivation limiting soil aggregate stability and macronutrient accumulation associated with glomalin-related soil protein in Eucalyptus urophylla × Eucalyptus grandis plantations - Ye Wang; Chun He; Yutian Shi; Hui Li; Yabin Tang; Bohao Chen; Qin Ke; Lichao Wu; Lijun Chen (Science of The Total Environment, 2023)

Secoiridoids from the traditional Chinese medicine Swertia pseudochinensis - Jie Liu; Qin Yan; Li-Xia Wang; Xiao-Ping He; Hong Hu; Yan-Chun Liu; Dan Li; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2023)

Bioactive triterpenoids from the traditional Chinese medicine Swertia mileensis - Xin Yuan; Qin Yan; Hong Hu; Xiao-Ping He; Li-Xia Wang; Yan-Chun Liu; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry Letters, 2023)

Knockout of cyclase-associated protein CAP1 confers tolerance towards salt and osmotic stress in Arabidopsis - Qian Zhang; Boya Wang; Xiangge Kong; Kexuan Li; Yaling Huang; Lu Peng; Li Chen; Jiajia Liu; Qin Yu; Juan He; Yi Yang; Xiaoyi Li; et al. (Journal of Plant Physiology, 2023)

Ni enhanced reactivity of Fe/TiO2 for selective catalytic reduction of NO with CO and the mechanism investigation - Kaiwen Zhao; Zhongfu Li; Tao Yan; Zhaojun Gao; Qin He; Qunfei Wang; Wenqi Liu; Jingyan Zhang; Xiaozheng Zhao; Li Liu; Conghua Liu (Journal of Environmental Chemical Engineering, 2023)

The driving force of biomass value-addition: Selective catalytic depolymerization of lignin to high-value chemicals - Quyang Tian; Piao Xu; Danlian Huang; Han Wang; Ziwei Wang; Hong Qin; Yangzhuo He; Ruijin Li; Lingshi Yin; Sha Chen; Yin Zhao (Journal of Environmental Chemical Engineering, 2023)

Isolation and characterization of a gas-producing and acid-resistant bacterium from spoiled vinegar - Xingjie Wang; Kaidi Hu; Fang Liu; Juan Mou; Jinghui Lai; Mengmei Zhang; Song Wang; Qin Li; Jianlong Li; Aiping Liu; Xiaolin Ao; Li He; et al. (International Journal of Food Microbiology, 2023)

A novel cerium organic network modified graphene oxide prepared multifunctional waterborne epoxy-based coating with excellent mechanical and passive/active anti-corrosion properties - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Pan Liu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Alterations in immune cell heterogeneities in the brain of aged zebrafish using single-cell resolution - Jiangyong He; Fangying Zhao; Bingyue Chen; Nianfei Cui; Zhifan Li; Jie Qin; Lingfei Luo; Congjian Zhao; Li Li (Science China Life Sciences, 2023)

A novel subgenotype I3 of hepatitis B virus in Guangxi, China: a 15-year follow-up study - Hui-Hua Jia; Qin-Yan Chen; Zhi-Hua Jiang; Xue-Yan Wang; Wen-Jia Zhang; Xiang He; Tim J. Harrison; J. Brooks Jackson; Li Wu; Zhong-Liao Fang (Virus Genes, 2023)

Leaching behavior and process optimization of tin recovery from waste liquid crystal display under mechanical activation - Jianchun Qin; Shunyan Ning; Jishu Zeng; Zheyu He; Fengtao Hu; Yimin Li; Toyohisa Fujita; Yuezhou Wei (Journal of Cleaner Production, 2023)

Light-tuning the host–guest interfacial recognition of Alginate-based amphiphiles for oil-in-water droplet deposition - Xinyu Zhao; Qu Zeng; Shujuan Yang; Furui He; Wenqi Qin; Zhaojun Wang; Keyang Mai; Gaobo Yu; Junhao Huang; Jiacheng Li; Yuhong Feng (Chemical Engineering Journal, 2023)

B-Cell-Activating Factor Contributes to Elevation of the Content of Regulatory B Cells in Neonatal Sepsis - W. Liao; H. Xiao; J. He; L. Huang; Y. Liao; J. Qin; Q. Yang; F. Ma; S. Li (Bulletin of Experimental Biology and Medicine, 2023)

Role of ambient climate in the response of soil respiration to different grassland management measures - Shuqi Qin; Qin Peng; Yunshe Dong; Yuchun Qi; Zhaolin Li; Yu Guo; Xingren Liu; Shengsheng Xiao; Xinchao Liu; Junqiang Jia; Yunlong He; Zhongqing Yan (Agricultural and Forest Meteorology, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

The structural and functional properties of dietary fibre extracts obtained from highland barley bran through different steam explosion-assisted treatments - Huihan Xi; Aixia Wang; Wanyu Qin; Mengzi Nie; Zhiying Chen; Yue He; Lili Wang; Liya Liu; Yatao Huang; Fengzhong Wang; Li-Tao Tong (Food Chemistry, 2023)

VOC emission profiles from typical solid fuel combustion in Fenhe River Basin: Field measurements and environmental implication - Qin Peng; Lizhen Li; Jian Sun; Kun He; Bin Zhang; Haijiang Zou; Hongmei Xu; Junji Cao; Zhenxing Shen (Environmental Pollution, 2023)

Tailoring and application of a multi-responsive cellulose nanofibre-based 3D nanonetwork wound dressing - Die Dong; Rimei Chen; Jihong Jia; Chao Zhao; Zhiping Chen; Qin Lu; Yupei Sun; Weiyi Huang; Chunfang Wang; Yao Li; Hui He (Carbohydrate Polymers, 2023)

Methimazole and sodium perchlorate exert anti-thyroidal effects in the T3-induced Xenopus laevis metamorphosis assay: A rapid assay for screening thyroid disrupting chemicals - Wei Zhou; Zhan-Fen Qin; Yuan-Yuan Li; Jin-Bo Li; Ya-li Shi; Miao-xin Dong; Xiang Li; Yong-Jun Zhang; Yi-De He (Aquatic Toxicology, 2023)

Sedimentary and tectonic evolution of the Banquan pull-apart basin and implications for late Cenozoic dextral strike-slip movement of the Tanlu Fault Zone - Peng Shu; Xiwei Xu; Shaoying Feng; Baojin Liu; Kang Li; Paul Tapponnier; Xiaojuan Deng; Guihua Chen; Nuan Xia; Hongtai Xu; Jingjing Qin; Fubing He; et al. (Science China Earth Sciences, 2023)

Formaldehyde oxidation on Pd/USY catalysts at room temperature: The effect of acid pretreatment on supports - Xiaofeng Liu; Chunying Wang; Yumin Chen; Qi Qin; Yaobin Li; Hong He (Journal of Environmental Sciences, 2023)

Learning and inferring the diurnal variability of cyanobacterial blooms from high-frequency time-series satellite-based observations - Hu Li; Chengxin Qin; Weiqi He; Fu Sun; Pengfei Du (Harmful Algae, 2023)

Molecular characterization of a teleost-specific toll-like receptor 22 (tlr22) gene from yellow catfish (Pelteobagrus fulvidraco) and its transcriptional change in response to poly I:C and Aeromonas hydrophila stimuli - Xiu-Ying Wei; Jun Wang; Sheng-Tao Guo; Yun-Yun Lv; Yan-Ping Li; Chuan-Jie Qin; Yuan-Chao Zou; Qing-Chao Shi; Peng Hu; Xiao-Qin Xiong; Yang He; Rui Li; et al. (Fish & Shellfish Immunology, 2023)

Integrative analysis of microbiome and metabolome reveals the linkage between gut microbiota and carp growth - Zhijuan Nie; Xiaotong Xu; Nailing Shao; Jian He; Pengfa Li; Pao Xu; Jiawen Hu; Wei Qin; Baozhan Wang; Gangchun Xu (Environmental Research, 2023)

Stoichiometry and energy assessment comparison between thermophilic and mesophilic high-solid anaerobic co-digestion of lipids and food waste - Yuanyuan Ren; Chen Wang; Ziang He; Yemei Li; Yu Qin; Yu-You Li (Chemical Engineering Journal, 2023)

The short-term effects of air pollution exposure on preterm births in Chongqing, China: 2015–2020 - Xin Ming; Ziyi He; Yannan Li; Yaqiong Hu; Yunping Yang; Hongyan Chen; Qin Chen; Huan Yang; Wenzheng Zhou (Environmental Science and Pollution Research, 2023)
Accumulating evidence suggested that the risk of preterm births (PTBs) following prenatal exposure to air pollution was inconclusive. The aim of this study is to investigate the relationship between air pollution exposure in the days before delivery and PTB and assess the threshold effect of short-term prenatal exposure to air pollution on PTB. This study collected data including meteorological factors, air pollutants, and information in Birth Certificate System from 9 districts during 2015–2020 in Chongqing, China. Generalized additive models (GAMs) with the distributed lag non-linear models were conducted to assess the acute impact of air pollutants on the daily counts of PTB, after controlling for potential confounding factors. We observed that PM 2.5 was related to increased occurrence of PTB on lag 0–3 and lag 10–21 days, with the strongest on the first day (RR = 1.017, 95%CI: 1.000–1.034) and then decreasing. The thresholds of PM 2.5 for lag 1–7 and 1–30 days were 100 μg/m 3 and 50 μg/m 3 , respectively. The lag effect of PM 10 on PTB was very similar to that of PM 2.5 . In addition, the lagged and cumulative exposure of SO 2 and NO 2 was also associated with the increased risk of PTB. The lag relative risk and cumulative relative risk of CO exposure were the strongest, with a maximum RR at lag 0 (RR = 1.044, 95%CI: 1.018, 1.069). Importantly, the exposure–response curve of CO showed that RR increased rapidly when the concentration exceeded 1000 μg/m 3 . This study indicated significant associations between air pollution and PTB. The relative risk decreases with day lag, while the cumulative effect increases. Thus, pregnant women should understand the risk of air pollution and try to avoid high concentration exposure.

Genome-wide association study reveals markers and candidate genes associated with growth in the rice flower carp, an economic fish species of integrated rice-fish culture in China - Hui Luo; Xianhui Pan; Yin Huang; Zhe Li; Hua Ye; Kangqi Zhou; Luting Wen; Junqi Qin; Wenping He; Xuesong Du; Dapeng Wang; Yong Lin (Frontiers in Marine Science, 2023)
The rice flower carp ( Cyprinus carpio ) is an important fish in integrated rice-fishery farming. Here, we performed the first genome-wide association study (GWAS) for seven growth traits (including body mass, total length, body length, body height, body width, caudal-peduncle depth, and eye spacing) in 200 rice flower carp samples using 369,688 high-quality SNPs and 42,225 indels obtained by double-digest genotyping-by-sequencing (ddGBS). The morphometrics of these traits were highly correlated (Pearson’s correlation coefficients = 0.74–0.99, p < 0.001). GWAS detected 15, 5, 4, 26, 7, 16, and 17 loci significant associated (-log10P ≥ 5) with body mass, total length, body length, body width, body height, caudal-peduncle depth, and eye spacing, respectively. Subsequently, within the 50 kb upstream and downstream regions surrounding these significant loci, 38, 19, 18, 20, 52, 27, and 37 candidate genes for the seven growth traits were detected, respectively. Importantly, B6_4352672 and A8_4978825 were significantly associated with more than five growth traits. These results showed loci significantly associated with more than five growth traits will be helpful for future marker-assisted selection (MAS). Interestingly, chromosomes A8 and B25 had many loci significantly associated with growth traits, most of which were shared among multiple growth-related traits. These results indicated that chromosome A8 and B25 may be closely related to growth traits. Our findings not only help understand the genetic architecture of growth traits in fish but facilitate the identification of candidate genes for marker-assisted selection towards breeding faster-growing rice flower carp in the future.

Airborne hyperspectral imaging of cover crops through radiative transfer process-guided machine learning - Sheng Wang; Kaiyu Guan; Chenhui Zhang; Chongya Jiang; Qu Zhou; Kaiyuan Li; Ziqi Qin; Elizabeth A. Ainsworth; Jingrui He; Jun Wu; Dan Schaefer; Lowell E. Gentry; et al. (Remote Sensing of Environment, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Quantitative partitioning of temporal origin of transpiration into pre- and post-plantation under deep-rooted vegetation on the Loess Plateau of China - Guangjie Chen; Wenjie Wu; Tingfang Meng; Mingyi Wen; Bingcheng Si; Jianqiang He; Min Li; Qin'ge Dong; Hao Feng; Kadambot H.M. Siddique (Journal of Hydrology, 2023)

Integrated process for zero discharge of coking wastewater: A hierarchical cycle-based innnovation - Xiong Ke; Tuo Wei; Gengrui Wei; Acong Chen; Xiaoqian Cheng; Zemin Li; Zhi Qin; Zijun Pang; Jiamin Pan; Yao Chen; Cong Wei; Xianghong Guan; et al. (Chemical Engineering Journal, 2023)

Synergistic multi-altimeter for estimating water level in the coastal zone of Beibu Gulf using SEL, ALES + and BFAST algorithms - Jiaoling Qin; Sunzhe Li; Hang Yao; Bolin Fu; Hongchang He; Feng Wang; Lilong Liu; Donglin Fan; Xu He; Yuyang Li (Frontiers in Marine Science, 2023)
Accurately monitoring and predicting the large-scale dynamic changes of water levels in coastal zones is essential for its protection, restoration and sustainable development. However, there has been a challenge for achieving this goal using a single radar altimeter and retracking technique due to the diversity and complexity of coastal waveforms. To solve this issue, we proposed an approach of estimating water level of the coastal zone in Beibu Gulf, China, by combination of waveform classifications and multiple sub-waveform retrackers. This paper stacked Random Forest (RF), XGBoost and CatBoost algorithms for building an ensemble learning (SEL) model to classify coastal waveforms, and further evaluated the performance of three retracking strategies in refining waveforms using Cryosat-2, SARAL, Sentinel-3 altimeters. We compared the estimation accuracy of the coastal water levels between the single altimeter and synergistic multi-altimeter, and combined Breaks for Additive Season and Trend (BFAST), Mann-Kendall mutation test (MK) with Long Short-Term Memory (LSTM) algorithms to track the historical change process of coastal water levels, and predict its future development trend. This paper found that: (1) The SEL algorithm achieved high-precision classification of different coastal waveforms with an average accuracy of 0.959, which outperformed three single machine learning algorithms. (2) Combination of Threshold Retracker and ALES+ Retracker (TR_ALES+) achieved the better retracking quality with an improvement of correlation coefficient (R, 0.089~0.475) and root mean square error (RMSE, 0.008∼ 0.029 m) when comparing to the Threshold Retracker & Primary Peak COG Retracker and Threshold Retracker & Primary Peak Threshold Retracker. (3) The coastal water levels of Cryosat-2, SARAL, Sentinel-3 and multi-altimeter were in good agreement (R>0.66, RMSE<0.135m) with Copernicus Climate Change Service (C3S) water level. (4) The coastal water levels of the Beibu Gulf displayed a slowly rising trend from 2011 to 2021 with an average annual growth rate of 8mm/a, its lowest water level focused on May-August, the peak of water level was in October-November, and the average annual growth rate of water level from 2022-2031 was about 0.6mm/a. These results can provide guidance for scientific monitoring and sustainable management of coastal zones.

Impact of high temperature on road injury mortality in a changing climate, 1990–2019: A global analysis - Li He; Ce Liu; Xiaobing Shan; Ling Zhang; Ling Zheng; Yunhui Yu; Xiaoyu Tian; Baode Xue; Yu Zhang; Xiao Qin; Cara Wang; Kai Zhang; et al. (Science of The Total Environment, 2023)

Transcriptome analysis preliminary reveals the immune response mechanism of golden cuttlefish (Sepia esculenta) larvae exposed to Cd - Zan Li; Huimin Qin; Yining Zhang; Xiaohua He; Xiaokai Bao; Guohua Sun; Cuiju Cui; Xiaohui Xu; Xiumei Liu; Jianmin Yang; Guoguang Zhang (Fish & Shellfish Immunology, 2023)

Various hydrogen bonds make different fates of pharmaceutical contaminants on oxygen-rich nanomaterials - Yifan Liu; Nana Li; Cong Du; Yue Wang; Kunyu He; Hao Zheng; Zhijing Xue; Qin Chen; Xiaoyun Li (Environmental Pollution, 2023)

High-performance flame-retardant aliphatic polyamide via enhanced chain entanglement - Min Jiang; Bo-Wen Liu; Feng-Ming He; Qin Zhang; Ao Wang; De-Ming Guo; Hai-Bo Zhao; Li Chen; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Propeller-shape isomers with turn-on through-space charge transfer for solution-processed non-doped organic light-emitting diodes - Jiale Li; Ling Zhou; Jiawei He; Qin Xue; Liang Xu; Guohua Xie (Chemical Engineering Journal, 2023)

Temperature tolerant all-solid-state touch panel with high stretchablity, transparency and self-healing ability - Zhenglin Chen; Fang Li; Likun Zhang; Zhengyang Lei; Canhui Yang; Chufan Xiao; Lijin Lian; Xi Yuan; Gul Ijaz; Jia'e Yang; Zijun Lin; Yunfeng He; et al. (Chemical Engineering Journal, 2023)

In-situ analysis of the sintering behavior of coal ash and a phosphorus-rich biomass ash under gasification condition - Chong He; Yujia Du; Xingrui Cai; Jirui Wang; Yuhong Qin; Zibing Zhao; Huaizhu Li; Stanislav V. Vassilev; Christina G. Vassileva (Biomass and Bioenergy, 2023)

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Diversity of endophytic fungi in Coptis chinensis Franch. and their activity against methicillin-resistant Staphylococcus aureus - Qianliang Ming; Xiuning Huang; Linming Guo; Dong Liu; Lingyue Qin; Yimo He; Yu Tang; Yanxia Liu; Junkang Liu; Peng Li (Folia Microbiologica, 2022)

Products distribution during in situ and ex situ catalytic fast pyrolysis of Chinese herb residues - Bo Li; Zehao Qian; Jie Qin; Qian He; Shengxiong Huang; Hang Dong; Nan Zhou; Mao Xia; Zhi Zhou (Environmental Science and Pollution Research, 2022)

Dissolved organic matter–assisted phytoremediation potential of cotton for Cd-contaminated soil: a relationship between dosage and phytoremediation efficiency - Tao Min; Tong Luo; Hao He; Jie Qin; Yan Wang; Liyang Cheng; Sibo Ru; Junhua Li (Environmental Science and Pollution Research, 2022)

Carbon sequestration in soil and biomass under native and non-native mangrove ecosystems - Ziming Zhang; Ying Wang; Yakun Zhu; Kehong He; Tingting Li; Umakant Mishra; Yisheng Peng; Fan Wang; Lingfei Yu; Xiaosong Zhao; Liye Zhu; Xudong Zhu; et al. (Plant and Soil, 2022)

Comparative transcriptome analyses identify genes involved into the biosynthesis of forsythin and forsythoside A in Forsythia suspensa - Wang Jun Yuan; Su Ping Zhang; Zhi Yin He; Yan Xia He; She Qi He; Li Jun Liu; Xin Sun; Qin Li (Functional & Integrative Genomics, 2022)

Competitiveness of alga Microcystis aeruginosa co-cultivated with cyanobacterium Raphidiopsis raciborskii confirms its dominating position - Zengling Ma; Xiaoqiao Zhang; Renhui Li; Min Wang; Wenli Qin; He Zhang; Gang Li; Henguo Yu; Chuanjun Dai; Min Zhao (Journal of Oceanology and Limnology, 2022)

An automatic ordering method for streams in surface-water/groundwater interaction modeling - Chengcheng Xu; Chu Wu; Tianchen Li; Chuiyu Lu; Xin He; Qingyan Sun; Tao Qin; Lingjia Yan (Hydrogeology Journal, 2022)

Preparation of Ni-La/Al2O3-CeO2-Bamboo Charcoal Catalyst and Its Application in Co-pyrolysis of Straw and Plastic for Hydrogen Production - Yiran Zhang; Jianfen Li; Bolin Li; Zeshan Li; Yun He; Zhenhua Qin; Rongyi Gao (BioEnergy Research, 2022)

Collapse mechanism of deep buried tunnel subjected to pore water pressure with generalized nonlinear unified strength theory - Lingli Xie; Dexin Lei; Jing Wang; Ruibing He; Tiange Qin; Li Wu (Arabian Journal of Geosciences, 2022)

Global regulatory factor VeA upregulates the production of antitumor substances in endophytic Fusarium solani - Lu Cai; Jiankang Wang; Yongjie Li; Min Qin; Xuemin Yin; Zhangjiang He; Jichuan Kang (Antonie van Leeuwenhoek, 2022)

Localization of salt-tolerant QTL in rice germination stage under different salinity concentrations - Yanning Wang; Liping Chen; Guiting Song; Tao Huang; Guangliang Wu; Jingai Tan; Peng Wang; Qin Cheng; Caijing Li; Qi Zhong; Shiying Huang; Mengmeng Yang; et al. (Euphytica, 2022)

Re-evaluation of the identities of Glossadelphus borneensis and its associated synonyms, G. attenuatus and G. nitidus - Zhao-Qin Yi; Si He; Jun-Jie Wang; Li-Qiang Mu; Yu Jia (Brittonia, 2022)

Integrated medical resource consumption stratification in hospitalized patients: an Auto Triage Management model based on accurate risk, cost and length of stay prediction - Qin Zhong; Zongren Li; Wenjun Wang; Lei Zhang; Kunlun He (Science China Life Sciences, 2022)

Astragaloside IV suppresses migration and invasion of TGF-β1-induced human hepatoma HuH-7 cells by regulating Nrf2/HO-1 and TGF-β1/Smad3 pathways - Lili Li; Qin Wang; Yinghao He; Liangjie Sun; Yan Yang; Xiaonan Pang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Suitable chemical fertilizer reduction mitigates the water footprint of maize production: evidence from Northeast China - Jianqin Wang; Lijie Qin; Jingru Cheng; Chenchen Shang; Bo Li; Yongcai Dang; Hongshi He (Environmental Science and Pollution Research, 2022)

Effects of extreme precipitation on hospitalization risk and disease burden of schizophrenia in urban and rural Lu’an, China, from 2010 to 2019 - Yudong Wu; Zhenghai Yao; Gongyan Ma; Jian Cheng; Huabin Xu; Wei Qin; Weizhuo Yi; Rubing Pan; Qiannan Wei; Chao Tang; Xiangguo Liu; Yangyang He; et al. (Environmental Science and Pollution Research, 2022)

A Comprehensive Monitoring and Assessment System for Multiple Fisheries Resources in the Northwest Pacific Based on Satellite Remote Sensing Technology - Hao Tian; Yang Liu; Yongjun Tian; Irene D. Alabia; Yuanzhe Qin; He Sun; Jianchao Li; Shuyang Ma; Sei-Ichi Saitoh (Frontiers in Marine Science, 2022)
Monitoring the dynamics of ocean-going fishing vessels is essential for fisheries stock assessment and management. In this paper, coupled fishery and remote sensing methods were applied to propose a satellite-based fishery resource monitoring and assessment system (SFRMAS) that supported chub mackerel ( Scomber japonicus ), Pacific saury ( Cololabis saira ) and neon flying squid ( Ommastrephes bartramii ) fishing activities in the northwest Pacific. A multispecies fishing vessel database was generated in the SFRMAS using visible infrared imaging radiometer suite day/night band (VIIRS/DNB) images, automatic identification system (AIS) data and multimarine remote sensing resources. The results showed that the VIIRS/DNB vessel detection (VVD) and AIS vessel detection approaches improved the extraction accuracy of multispecies fishing vessels. A high productivity area with a higher chlorophyll a concentration had the most concentrated distribution of mackerel vessels. The widest longitudinal migrations of the neon flying squid and the latitudinal ranges of Pacific saury were highly related to sea surface temperature (SST), which was well captured by the movement of the fishing vessels. In the SFRMAS, the accuracy of detected multispecies fishing days and fishing catches was mostly between 60 and 90%, which can provide data support for fisheries stock assessment and management.

Processed potatoes intake and risk of type 2 diabetes: a systematic review and meta-analysis of nine prospective cohort studies - Wei Quan; Ye Jiao; Chaoyi Xue; Yong Li; Zhaojun Wang; Maomao Zeng; Fang Qin; Zhiyong He; Jie Chen (Critical Reviews in Food Science and Nutrition, 2022)

Removal of perchlorate by a lab-scale constructed wetland using achira (Canna indica L.) - Dongqin Li; Bingqian Li; Haishuo Gao; Xinyu Du; Junhao Qin; Huashou Li; Hongzhi He; Guikui Chen (Wetlands Ecology and Management, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Response of soil respiration to water and nitrogen addition and its influencing factors: a four-year field experiment in a temperate steppe - ZhaoLin Li; Qin Peng; YunShe Dong; YunLong He; ZhongQing Yan; Yu Guo; Shuqi Qin; Yuchun Qi (Plant and Soil, 2022)

Investigation of Antibiotic-Resistant Bacterial Communities and Antibiotic-Resistant Genes in Wastewater Treatment Plants: Removal of Antibiotic-Resistant Genes by the BBR Process - Zi-fan Weng; Yu-qin He; Guo-xiang Li; Xiao-tong Wu; Yi Dai; Peng Bao (Bulletin of Environmental Contamination and Toxicology, 2022)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Additive and Epistatic QTL on Cadmium (Cd) Tolerance Associated with Seed Germinating Ability in Rice - Changsheng Li; Peng Wang; Guangliang Wu; Yanning Wang; Qin Cheng; Yicong Cai; Dahu Zhou; Caijing Li; Xiangyu Zhang; Jingai Tan; Cuijuan Li; Haohua He; et al. (Journal of Plant Growth Regulation, 2021)

Microorganism and Physiochemical Characteristic of High-salt (Suan Yu), a Traditional Chinese Fermented Fish - Chengxing Lin; Furong Zhang; Qin Yang; Ju Meng; Laping He; Li Deng; Chun Ye; Xuefeng Zeng (Journal of Aquatic Food Product Technology, 2021)

Genetic control and phenotypic characterization of panicle architecture and grain yield-related traits in foxtail millet (Setaria italica) - Hui Zhi; Qiang He; Sha Tang; Junjun Yang; Wei Zhang; Huifang Liu; Yanchao Jia; Guanqing Jia; Aiying Zhang; Yuhui Li; Erhu Guo; Ming Gao; et al. (Theoretical and Applied Genetics, 2021)

Bacillus megaterium strain WW1211 promotes plant growth and lateral root initiation via regulation of auxin biosynthesis and redistribution - Shengwang Wang; Xiaofan Na; Lei Yang; Cuifang Liang; Li He; Jie Jin; Ziyu Liu; Juan Qin; Junjie Li; Xiaomin Wang; Yurong Bi (Plant and Soil, 2021)

Enhanced Biodegradation of Hexachlorocyclohexane in Soil by Application of Exogenous Amendments - Xutong Liu; He Huang; Dan Huang; Kai Zhong; Qun Rong; Xingzi Qin; Chaolan Zhang; Xue Li (Water, Air, & Soil Pollution, 2021)

Smad3 gene C-terminal phosphorylation site mutation exacerbates CCl4-induced hepatic fibrogenesis by promoting pSmad2L/C-mediated signaling transduction - Juan Yang; Yongfang Gong; Wenjing Xu; Lili Li; Zhenghao Shi; Qin Wang; Yinghao He; Chong Zhang; Chenchen Luo; Zhirui Fang; Yan Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Regulatory mechanism of GA3 on tuber growth by DELLA-dependent pathway in yam (Dioscorea opposita) - Yunyi Zhou; Yuting Li; Mingxia Gong; Fang Qin; Dong Xiao; Jie Zhan; Aiqin Wang; Longfei He (Plant Molecular Biology, 2021)

Multi-source data-based spatial variations of blue and green water footprints for rice production in Jilin Province, China - Bo Li; Lijie Qin; Jianqin Wang; Yongcai Dang; Hongshi He (Environmental Science and Pollution Research, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Genome-Wide Identification and Expression Analysis of Heavy Metal Stress–Responsive Metallothionein Family Genes in Nicotiana tabacum - Qin Yu; Linshen He; Chunsong Huo; Xiaohan Jiang; Hua Chen; Run Wang; Minzhi Tang; Ling Dong; Ji Chen; Yonghao Li; Shunqin Zhu; Wanhong Liu (Plant Molecular Biology Reporter, 2021)

Mapping Domain- and Age-Specific Functional Brain Activity for Children’s Cognitive and Affective Development - Lei Hao; Lei Li; Menglu Chen; Jiahua Xu; Min Jiang; Yanpei Wang; Linhua Jiang; Xu Chen; Jiang Qiu; Shuping Tan; Jia-Hong Gao; Yong He; et al. (Neuroscience Bulletin, 2021)

Occurrence, spatial distribution, source, and ecological risk assessment of organochlorine pesticides in Dongting Lake, China - Fengmei Cao; Zhaozhao Li; Qi He; Shaoyong Lu; Pan Qin; Linlin Li (Environmental Science and Pollution Research, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Genome-wide association mapping for resistance to bacterial blight and bacterial leaf streak in rice - Nan Jiang; Jun Fu; Qin Zeng; Yi Liang; Yanlong Shi; Zhouwei Li; Youlun Xiao; Zhizhou He; Yuntian Wu; Yu Long; Kai Wang; Yuanzhu Yang; et al. (Planta, 2021)

Hydrocotyle vulgaris L.: a new cadmium-tolerant landscape species and its physiological responses to cadmium exposure - Kehui Liu; Xiaolu Liang; Chunming Li; Leyi Wang; Xiaoyu He; Rilan Qin; Yi Li; Fangming Yu (Environmental Science and Pollution Research, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Effects of Liquid Smoking on the Microbiological and Physicochemical Characteristics of Suan Yu, a Traditional Chinese Fermented Fish Product - Xuefeng Zeng; Qin Yang; Wei Zhang; Jingui Liu; Laping He; Li Deng; Xu Guo (Journal of Aquatic Food Product Technology, 2021)

Emergency response to the reactivated Aniangzhai landslide resulting from a rainstorm-triggered debris flow, Sichuan Province, China - Bo Zhao; Haiquan Zhang; Liao Hongjian; Weile Li; Lijun Su; Wenxiu He; Lu Zeng; Haokun Qin; Megh Raj Dhital (Landslides, 2021)

Oceanomicrobium pacificus gen. nov., sp. nov., a member of the family Rhodobacteraceae isolated from seawater of tropical western Pacific - Dadong Dai; Yangjie Li; Wenxuan He; Fang Qin; Jinshui Zheng; Ming Sun; Dechao Zhang (Antonie van Leeuwenhoek, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

The formation and evolution of parent and oxygenated polycyclic aromatic hydrocarbons during a severe winter haze–fog event over Xi’an, China - Yali Lei; Zhenxing Shen; Kun He; Lijuan Li; Yiming Qin; Yaling Zeng; Jianjun Li; Hongmei Xu; Yongjing Ma; Tian Zhang; Liu Yang; Ningning Zhang; et al. (Environmental Science and Pollution Research, 2021)

Knockdown of circPUM1 impedes cell growth, metastasis and glycolysis of papillary thyroid cancer via enhancing MAPK1 expression by serving as the sponge of miR-21-5p - Yanqi Li; Jun Qin; Zhaocai He; Guang Cui; Kun Zhang; Buqiang Wu (Genes & Genomics, 2021)

Purification and Enzymatic Properties of a Difunctional Glycoside Hydrolase from Aspergillus oryzae HML366 - Yongling Qin; Yue Fu; Qiqian Li; Fengfeng Luo; Haiyan He (Indian Journal of Microbiology, 2020)

Genomewide analysis of the CIII peroxidase family in sweet orange (Citrus sinensis) and expression profiles induced by Xanthomonas citri subsp. citri and hormones - Qiang Li; Wanfu Dou; Jingjing Qi; Xiujuan Qin; Shanchun Chen; Yongrui He (Journal of Genetics, 2020)

Exploring the potential of deep factorization machine and various gradient boosting models in modeling daily reference evapotranspiration in China - Zhigao Zhou; Lin Zhao; Aiwen Lin; Wenmin Qin; Yunbo Lu; Jingyi Li; Yang Zhong; Lijie He (Arabian Journal of Geosciences, 2020)

Activation of p62-Keap1-Nrf2 Pathway Protects 6-Hydroxydopamine-Induced Ferroptosis in Dopaminergic Cells - Yiran Sun; Libo He; Taoyu Wang; Wan Hua; Huan Qin; Jingjin Wang; Li Wang; Wanqin Gu; Tingting Li; Na Li; Xinanbei Liu; Fang Chen; et al. (Molecular Neurobiology, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Increased O-GlcNAcylation induces myocardial hypertrophy - Xiaoli Chen; Li Zhang; Hui He; Yikai Sun; Qin Shen; Linsheng Shi (In Vitro Cellular & Developmental Biology - Animal, 2020)

Development of a daily soil moisture product for the period of 2002–2011 in Chinese mainland - Kun Yang; Yingying Chen; Jie He; Long Zhao; Hui Lu; Jun Qin; Donghai Zheng; Xin Li (Science China Earth Sciences, 2020)

Combining forward with recurrent neural networks for hourly air quality prediction in Northwest of China - Zhili Zhao; Jian Qin; Zhaoshuang He; Huan Li; Yi Yang; Ruisheng Zhang (Environmental Science and Pollution Research, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Generation of a porcine reproductive and respiratory syndrome virus expressing a marker gene inserted between ORF4 and ORF5a - Yuxu Wang; Wei He; Qingqing Li; Xin Xie; Nian Qin; Hao Wang; Jiabin Huang; Siyuan Lin; Kang Ouyang; Ying Chen; Weijian Huang; Zuzhang Wei (Archives of Virology, 2020)

Coupled Model of Variable Fuzzy Sets and the Analytic Hierarchy Process and its Application to the Social and Environmental Impact Evaluation of Dam Breaks - Guanjie He; Junrui Chai; Yuan Qin; Zengguang Xu; Shouyi Li (Water Resources Management, 2020)

Genetic analysis of germinating ability under alkaline and neutral salt stress by a high-density bin genetic map in rice - Xin Luo; Haodong Deng; Peng Wang; Xiangyu Zhang; Caijing Li; Cuijuan Li; Jingai Tan; Guangliang Wu; Yanning Wang; Qin Cheng; Haohua He; Jianmin Bian (Euphytica, 2020)

Production, Identification and Characterization of Erianthus rockii × Narenga porphyrocoma Intergeneric Hybrids as a New Germplasm for Sugarcane Breeding and Genetic Research - Hailong Chang; Qinnan Wang; Yongsheng Qiu; Yuanxia Qin; Xueting Li; Qingdan Wu; Weiping He; Yuqiang Guo; Wei Zhang; Junlv Chen; Na Fang (Sugar Tech, 2020)

Plastic pollution in croplands threatens long‐term food security - Dan Zhang; Ee Ling Ng; Wanli Hu; Hongyuan Wang; Pablo Galaviz; Hude Yang; Wentao Sun; Chongxiao Li; Xingwang Ma; Bin Fu; Peiyi Zhao; Fulin Zhang; et al. (Global Change Biology, 2020)
Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta‐analysis, we found that the use of plastic mulch can indeed increase crop yields on average by 25%–42% in the immediate season due to the increase of soil temperature (+8%) and moisture (+17%). However, the unabated accumulation of film residues in the field negatively impacts its physicochemical properties linked to healthy soil and threatens food production in the long term. It has multiple negative impacts on plant growth including crop yield (at the mean rate of −3% for every additional 100 kg/ha of film residue), plant height (−2%) and root weight (−5%), and soil properties including soil water evaporation capacity (−2%), soil water infiltration rate (−8%), soil organic matter (−0.8%) and soil available phosphorus (−5%) based on meta‐regression. Using a nationwide field survey of China, the largest user of plastic mulch worldwide, we found that plastic residue accumulation in cropland soils has reached 550,800 tonnes, with an estimated 6%–10% reduction in cotton yield in some polluted sites based on current level of plastic residue content. Immediate actions should be taken to ensure the recovery of plastic film mulch and limit further increase in film residue loading to maintain the sustainability of these croplands.

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

The effects of Japanese encephalitis virus antibodies on Zika virus infection - Xiaoen He; Xinyue Lang; Jianhai Yu; Li Zhu; Zhiran Qin; Xuling Liu; Pei Chen; Chengguqiu Dai; Tingting Chen; Xujuan Li; Yangyang Chen; Dongrui Zhou; et al. (Medical Microbiology and Immunology, 2020)

Preparation of a novel iron-based biochar composite for removal of hexavalent chromium in water - Luyao Qin; Li He; Wenjie Yang; Aijun Lin (Environmental Science and Pollution Research, 2020)

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

A simple and low-energy method to prepare loratadine nanosuspensions for oral bioavailability improvement: preparation, characterization, and in vivo evaluation - Dandan Yang; Ruirui Li; Fang Zhang; Li Qin; Feifei Peng; Shanshan Jiang; Huiyang He; Xiumei Lu; Peng Zhang (Drug Delivery and Translational Research, 2020)

Molecular Cloning and Expression Analysis of Ethylene-Insensitive3-Like 1 (ScEIL1) Gene in Sugarcane - Fan-Wei Wang; Jian-Bin Yu; Dong Xiao; Yang-Rui Li; Long-Fei He; Ai-Qin Wang (Sugar Tech, 2019)

Alterations in intestinal microbiota of colorectal cancer patients receiving radical surgery combined with adjuvant CapeOx therapy - Cheng Kong; Renyuan Gao; Xuebing Yan; Linsheng Huang; Jide He; Hao Li; Jie You; Huanlong Qin (Science China Life Sciences, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Three new alkaloids from the roots of Sophora tonkinensis - Chun Wu; Lijun He; Xue Yi; Juan Qin; Yaolan Li; Yubo Zhang; Guocai Wang (Journal of Natural Medicines, 2019)

Mechanical Effect Analysis and Comparative Site Tests on Surrounding Rock with Different Bolt Anchoring Lengths and Pre-tightening Forces - Qi Wang; Hongtao Wang; Rui Pan; Shucai Li; Manchao He; Bei Jiang; Qian Qin; Chong Zhang; Yingdong Xu (Geotechnical and Geological Engineering, 2019)

Differences of Cd uptake and expression of MT family genes and NRAMP2 in two varieties of ryegrasses - Yanhua Li; Yuli Qin; Weihong Xu; Yourong Chai; Tao Li; Chunlai Zhang; Mei Yang; Zhangmi He; Deyu Feng (Environmental Science and Pollution Research, 2019)

Differences of Cd uptake and expression of OAS and IRT genes in two varieties of ryegrasses - Sunlin Chi; Yuli Qin; Weihong Xu; Yourong Chai; Deyu Feng; Yanhua Li; Tao Li; Mei Yang; Zhangmi He (Environmental Science and Pollution Research, 2019)

Transmissibility of citrus yellow vein clearing virus by contaminated tools - Yanhui Zhang; Yingjie Liu; Yingli Wang; Qin Wang; Shaoguo He; Xueyan Li; Yan Zhou (Journal of Plant Pathology, 2019)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

Three new isoflavones from the Pueraria montana var. lobata (Willd.) and their bioactivities - Tinghui Cui; Shiyun Tang; Chunbo Liu; Zhenjie Li; Qin Zhu; Junheng You; Xiaoxi Si; Fengmei Zhang; Pei He; Zhihua Liu; Mingming Miao; Guangyu Yang; et al. (Natural Product Research, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

The complete mitochondrial genome sequence and phylogenetic analysis of white-lipped deer (Cervus albirostris) - Pu Zhao; Huailiang Xu; Diyan Li; Meng Xie; Huaming Xu; Jiayun Wu; Anxiang Wen; Qingyong Ni; Mingwang Zhang; Qin Wang; Guangxiang Zhu; Tao He; et al. (Conservation Genetics Resources, 2018)

Trends in extreme temperature indices in Huang-Huai-Hai River Basin of China during 1961–2014 - Gang Wang; Denghua Yan; Xiaoyan He; Shaohua Liu; Cheng Zhang; Ziqiang Xing; Guangyuan Kan; Tianling Qin; Minglei Ren; Hui Li (Theoretical and Applied Climatology, 2018)

The Antibacterial Mechanism of Terpinen-4-ol Against Streptococcus agalactiae - Yuetian Zhang; Ruizhang Feng; Lixia Li; Xun Zhou; Zhengwen Li; Renyong Jia; Xu Song; Yuanfeng Zou; Lizi Yin; Changliang He; Xiaoxia Liang; Wanhai Zhou; et al. (Current Microbiology, 2018)

Influence of temperature on the brittle failure of granite in deep tunnels determined from triaxial unloading tests - Guoqing Chen; Tianbin Li; Guangming Li; Chang’an Qin; Yonghua He (European Journal of Environmental and Civil Engineering, 2018)

Climatology of tracked persistent maxima of 500-hPa geopotential height - Ping Liu; Yuejian Zhu; Qin Zhang; Jon Gottschalck; Minghua Zhang; Christopher Melhauser; Wei Li; Hong Guan; Xiaqiong Zhou; Dingchen Hou; Malaquias Peña; Guoxiong Wu; et al. (Climate Dynamics, 2018)

42,573 cases of hepatectomy in China: a multicenter retrospective investigation - Binhao Zhang; Bixiang Zhang; Zhiwei Zhang; Zhiyong Huang; Yifa Chen; Minshan Chen; Ping Bie; Baogang Peng; Liqun Wu; Zhiming Wang; Bo Li; Jia Fan; et al. (Science China Life Sciences, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Comparative analysis of otolith morphology in three species of Scomber - Tao He; Jiao Cheng; Jian-guang Qin; Yun Li; Tian-xiang Gao (Ichthyological Research, 2018)

Human amylin induces CD4+Foxp3+ regulatory T cells in the protection from autoimmune diabetes - Xiao-xi Zhang; Yong-chao Qiao; Wan Li; Xia Zou; Yin-ling Chen; Jian Shen; Qin-yuan Liao; Qiu-jin Zhang; Lan He; Hai-lu Zhao (Immunologic Research, 2018)

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata - Chuan-Wen Lei; Zhi-Qin Yang; Yan-Ping Zeng; Yun Zhou; Yi Huang; Xin-Sheng He; Guo-You Li; Xiao-Hong Yuan (Natural Product Research, 2018)

Association mapping analysis of fiber yield and quality traits in Upland cotton (Gossypium hirsutum L.) - Mulugeta Seyoum Ademe; Shoupu He; Zhaoe Pan; Junling Sun; Qinglian Wang; Hongde Qin; Jinhai Liu; Hui Liu; Jun Yang; Dongyong Xu; Jinlong Yang; Zhiying Ma; et al. (Molecular Genetics and Genomics, 2017)

Hydro-mechanical analysis of rainfall-induced fines migration process within unsaturated soils - Xiao-qin Lei; Zong-ji Yang; Si-ming He; En-long Liu; Henry Wong; Xin-po Li (Journal of Mountain Science, 2017)

Research on reasonable coal pillar width of roadway driven along goaf in deep mine - Qi Wang; Hongke Gao; Bei Jiang; Shucai Li; Manchao He; Dechao Wang; Wei Lu; Qian Qin; Song Gao; Hengchang Yu (Arabian Journal of Geosciences, 2017)

Bacillus zanthoxyli sp. nov., a novel nematicidal bacterium isolated from Chinese red pepper (Zanthoxylum bungeanum Maxim) leaves in China - Ma Li; Cao Yong Hong; Wang Xiao Yan; Zheng Shuai Chao; Yang Cheng Gang; Duo Jin Ling; Zhou Xing Kui; Xi Jia Qin; Zhu Ming Liang; Mo Ming He (Antonie van Leeuwenhoek, 2017)

Protective mechanisms of hypaconitine and glycyrrhetinic acid compatibility in oxygen and glucose deprivation injury - Li-qin Wang; Yu He; Hao-fang Wan; Hui-fen Zhou; Jie-hong Yang; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Nuclear magnetic resonance T2 spectrum: multifractal characteristics and pore structure evaluation - Jian-Ping Yan; Xu He; Bin Geng; Qin-Hong Hu; Chun-Zhen Feng; Xiao-Pan Kou; Xing-Wen Li (Applied Geophysics, 2017)

Cycloartane-type triterpenoids from Astragalus hoantchy French. - Kai Guo; Xiaofeng He; Dengxue Lu; Yanping Zhang; Xiuzhuang Li; Zhiqiang Yan; Bo Qin (Natural Product Research, 2017)

Differential genotoxicity mechanisms of silver nanoparticles and silver ions - Yan Li; Taichun Qin; Taylor Ingle; Jian Yan; Weiwei He; Jun-Jie Yin; Tao Chen (Archives of Toxicology, 2017)

Phytotoxicity mechanisms of two coumarin allelochemicals from Stellera chamaejasme in lettuce seedlings - Zhiqiang Yan; Dandan Wang; Haiyan Cui; Denghong Zhang; Yuhe Sun; Hui Jin; Xiuzhuang Li; Xiaoyan Yang; Hongru Guo; Xiaofeng He; Le Pan; Xia Ren; et al. (Acta Physiologiae Plantarum, 2016)

Patterns and drivers of soil microbial communities in Tibetan alpine and global terrestrial ecosystems - Yong‐Liang Chen; Jin‐Zhi Ding; Yun‐Feng Peng; Fei Li; Gui‐Biao Yang; Li Liu; Shu‐Qi Qin; Kai Fang; Yuan‐He Yang (Journal of Biogeography, 2016)
Aim Soil microorganisms play key roles in regulating many important ecosystem processes. However, our understanding of the patterns and drivers of soil microbial communities remains limited. This study aims to test the hypothesis that edaphic factors are more important in explaining variations in soil microbial communities than climatic and biotic factors, as soils directly provide substrates and environment for soil microbial communities. Location Tibetan alpine grasslands and global terrestrial biomes. Methods On the basis of phospholipid fatty acid ( PLFA ) analysis, we investigated large‐scale patterns and drivers of soil microbial communities using data obtained from 196 sites within two major grassland types (alpine steppe and alpine meadow) on the Tibetan Plateau. We also explored global patterns of soil microbial communities by analysing published data from around the world. Results Soil microbial PLFA s in Tibetan alpine grasslands were positively associated with mean annual temperature and mean annual precipitation ( MAP ), contradicting patterns previously observed across global biomes. A combined stepwise regression and variation partitioning analysis revealed that soil microbial community variations in Tibetan alpine grasslands were mainly explained by edaphic factors, such as soil organic carbon, C : N ratio, pH and soil texture, then by biotic factors, such as aboveground biomass and plant species richness, and further by climatic factors, such as MAP . The global analysis confirmed that edaphic factors accounted for a greater portion of the variation in soil microbial communities than did climatic and biotic variables. Main conclusions These results provide strong support for the hypothesis that edaphic factors are the dominant drivers of spatial variations in soil microbial communities across regional and global scales.

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Spatial and temporal variation of drought index in a typical steep alpine terrain in Hengduan Mountains - Gno-feng Zhu; Ling Yang; Da-he Qin; Hua-li Tong; Yuan-feng Liu; Jia-fang Li (Journal of Mountain Science, 2016)

The Receptor-Like Cytoplasmic Kinase OsRLCK102 Regulates XA21-Mediated Immunity and Plant Development in Rice - Jing Wang; Guanwen Wu; Chunfang Peng; Xiaogang Zhou; Weitao Li; Min He; Jichun Wang; Junjie Yin; Can Yuan; Weiwei Ma; Bintian Ma; Yuping Wang; et al. (Plant Molecular Biology Reporter, 2016)

An ethylene response-related factor, GbERF1-like, from Gossypium barbadense improves resistance to Verticillium dahliae via activating lignin synthesis - Weifeng Guo; Li Jin; Yuhuan Miao; Xin He; Qin Hu; Kai Guo; Longfu Zhu; Xianlong Zhang (Plant Molecular Biology, 2016)

Effects of perchlorate bioaccumulation on Spodoptera litura growth and sex ratio - Junhao Qin; Yinghua Shu; Yongjun Li; Hongzhi He; Huashou Li (Environmental Science and Pollution Research, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Impacts of snow disaster on meat production and adaptation: an empirical analysis in the yellow river source region - Yi-ping Fang; Chen Zhao; Yong-jian Ding; Da-he Qin; Jia-li Huang (Sustainability Science, 2016)

Assessment of Montan Resin on Germination and Growth of Wheat Seed - Juxiang Liu; Mi Zhang; Baocai Li; Yi Qin; Cheng Xiang; Jing He (Agricultural Research, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

PPR protein PDM1/SEL1 is involved in RNA editing and splicing of plastid genes in Arabidopsis thaliana - Hong-Dao Zhang; Yong-Lan Cui; Chao Huang; Qian-Qian Yin; Xue-Mei Qin; Te Xu; Xiao-Fang He; Yi Zhang; Zi-Ran Li; Zhong-Nan Yang (Photosynthesis Research, 2015)

An artificially constructed Syngonium podophyllum-Aspergillus niger combinate system for removal of uranium from wastewater - Jia-dong He; Yong-dong Wang; Nan Hu; Dexin Ding; Jing Sun; Qin-wen Deng; Chang-wu Li; Fei Xu (Environmental Science and Pollution Research, 2015)

Occurrence of Polychlorodibenzothiophenes in Nanjing Section of the Yangtze River, China - Qun He; Li Qin; Xuesheng Zhang; Liansheng Wang; Ping Sun; Zunyao Wang (Archives of Environmental Contamination and Toxicology, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Plant-assisted rhizoremediation of decabromodiphenyl ether for e-waste recycling area soil of Taizhou, China - Yan He; Xinfeng Li; Xinquan Shen; Qin Jiang; Jian Chen; Jiachun Shi; Xianjin Tang; Jianming Xu (Environmental Science and Pollution Research, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Effects of reducing dietary protein on the expression of nutrition sensing genes (amino acid transporters) in weaned piglets - Li Wu; Liu-qin He; Zhi-jie Cui; Gang Liu; Kang Yao; Fei Wu; Jun Li; Tie-jun Li (Journal of Zhejiang University-SCIENCE B, 2015)

A Time-Course Proteomic Analysis of Rice Triggered by Plant Activator BTH - Zhuo Chen; Binghua Chen; Qin Guo; Li Shi; Ming He; Zhiyang Qin; Lianhua Li; Peng He; Zhenchao Wang; Deyu Hu; Song Yang (Journal of Plant Growth Regulation, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

Geissoschizine methyl ether N -oxide, a new alkaloid with antiacetylcholinesterase activity from Uncaria rhynchophylla - Wei-Wei Jiang; Jia Su; Xing-De Wu; Juan He; Li-Yan Peng; Xiao Cheng; Qin-Shi Zhao (Natural Product Research, 2015)

Analysis of DNA methylation in tissues and development stages of pearl oyster Pinctada fucata - Yao-guo Li; Yun-yan Guan; Qin Li; Mao-xian He (Genes & Genomics, 2015)

Fluorometric Titration Assay of Affinity of Tight-Binding Nonfluorescent Inhibitor of Glutathione S-transferase - Bangtian Xu; Deng Tan; Xiaolan Yang; Xiaolei Hu; Yanling Xie; Jialin Qin; Chunyan Chen; Chenxiong He; Yuanli Li; Jun Pu; Fei Liao (Journal of Fluorescence, 2015)

Rapid Detoxification of Jatropha curcas Seed Cake by Hydrogen Peroxide Oxidation and Acute Toxicity Evaluation of Detoxified Product - Mi Zhang; Kuanjun Gong; Shiyun Jiao; Yi Qin; Cheng Xiang; Jing He; Baocai Li (Agricultural Research, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Cloning and expression analyses of the anthocyanin biosynthetic genes in mulberry plants - Xiwu Qi; Qin Shuai; Hu Chen; Li Fan; Qiwei Zeng; Ningjia He (Molecular Genetics and Genomics, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Development of proteomic technology of shotgun and label free combined with multiple reaction monitoring to simultaneously detect southern rice black-streaked dwarf virus and rice ragged stunt virus - Zhuo Chen; Qin Guo; Bing-Hua Chen; Xiang-Yang Li; Zhen-Chao Wang; Peng He; Fei Yan; De-Yu Hu; Song Yang (VirusDisease, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Genistein Alleviates Radiation-Induced Pneumonitis by Depressing Ape1/Ref-1 Expression to Down-regulate Inflammatory Cytokines - Guo-Dong Liu; Lei Xia; Jian-Wu Zhu; Shan Ou; Meng-Xia Li; Yong He; Wei Luo; Juan Li; Qian Zhou; Xue-Qin Yang; Jin-Lu Shan; Ge Wang; et al. (Cell Biochemistry and Biophysics, 2014)

Molecular characterization of StNAC2 in potato and its overexpression confers drought and salt tolerance - Qinfen Xu; Qin He; Shuai Li; Zhendong Tian (Acta Physiologiae Plantarum, 2014)

Down-regulated Six2 by knockdown of neurofibromin results in apoptosis of metanephric mesenchyme cells in vitro - Puhui Zhou; Tielin Chen; Yin Fang; Honglian Wang; Mi Li; Pengpeng Ma; Lu He; Qianyin Li; Tianming Liu; Xianggui Yang; Fang Nie; Xiaoyan Wang; et al. (Molecular and Cellular Biochemistry, 2014)

Serum lipocalin-2, cathepsin S and chemerin levels and nonalcoholic fatty liver disease - Zi Ye; Suijun Wang; Zhen Yang; Min He; Shuo Zhang; Weiwei Zhang; Jie Wen; Qin Li; Ying Huang; Xuanchun Wang; Bin Lu; Zhaoyun Zhang; et al. (Molecular Biology Reports, 2014)

Association between statin use and colorectal cancer risk: a meta-analysis of 42 studies - Yanqiong Liu; Weizhong Tang; Jian Wang; Li Xie; Taijie Li; Yu He; Yan Deng; Qiliu Peng; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Fumigant activity of Illicium verum fruit extracts and their effects on the acetylcholinesterase and glutathione S-transferase activities in adult Sitophilus zeamais - Shi-Guang Li; Mao-Ye Li; Yan-Zhang Huang; Ri-Mao Hua; Hua-Feng Lin; Yu-Jie He; Lin-Lin Wei; Zhu-Qin Liu (Journal of Pest Science, 2013)

Inhibition of hepatocellular carcinoma growth and angiogenesis by dual silencing of NET-1 and VEGF - Yuan-Yuan Wu; Li Chen; Gui-Lan Wang; Yi-Xin Zhang; Jia-Ming Zhou; Song He; Jing Qin; Yuan-Yuan Zhu (Journal of Molecular Histology, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

Net fluxes of ammonium and nitrate in association with H+ fluxes in fine roots of Populus popularis - Jie Luo; Jingjing Qin; Fangfang He; Hong Li; Tongxian Liu; Andrea Polle; Changhui Peng; Zhi-Bin Luo (Planta, 2013)

Systemic Treatment with Vanadium Absorbed by Coprinus comatus Promotes Femoral Fracture Healing in Streptozotocin-Diabetic Rats - Guangbin Wang; Jiashi Wang; Yonghui Fu; Lunhao Bai; Ming He; Bin Li; Qin Fu (Biological Trace Element Research, 2013)

The Influence of NaIO3-Induced Retinal Degeneration on Intra-retinal Layer and the Changes of Expression Profile/Morphology of DA-ACs and mRGCS - Zui Tao; Jiaman Dai; Jianrong He; Chunshi Li; Yaochen Li; Zheng Qin Yin (Molecular Neurobiology, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Association between the OGG1 Ser326Cys and APEX1 Asp148Glu polymorphisms and lung cancer risk: a meta-analysis - Wu Wei; Xiao-Feng He; Jiang-Bo Qin; Jiao Su; Shao-Xia Li; Yi Liu; Ying Zhang; Wei Wang (Molecular Biology Reports, 2012)

Atorvastatin suppresses oxidized LDL-induced dendritic cell-like differentiation of RAW264.7 cells regulated by the p38 MAPK pathway - Liu-hua Hu; Tuo Zhang; Qin Shao; Dan-dan Li; Shu-xuan Jin; Peng Nie; Jing Yi; Ben He; Ling-hong Shen (Molecular and Cellular Biochemistry, 2012)

Comparison of Effects of Vanadium Absorbed by Coprinus comatus with Those of Inorganic Vanadium on Bone in Streptozotocin-Diabetic Rats - Guangbin Wang; Ming He; Pei Yi; Jiashi Wang; Bin Li; Jianjun Li; Yonghui Fu; Lunhao Bai; Qin Fu (Biological Trace Element Research, 2012)

Direct and indirect organogenesis of Clivia miniata and assessment of DNA methylation changes in various regenerated plantlets - Qin-Mei Wang; Yu-Zhang Wang; Li-Li Sun; Feng-Zhan Gao; Wei Sun; Jing He; Xiang Gao; Li Wang (Plant Cell Reports, 2012)

Effect of hepcidin on intracellular calcium in human osteoblasts - Guang-Fei Li; You-Jia Xu; Yin-Feng He; Ben-Cai Du; Peng Zhang; Dong-Yang Zhao; Chen Yu; Chen-Hao Qin; Kai Li (Molecular and Cellular Biochemistry, 2012)

Surface Display of Human Serum Albumin on Bacillus subtilis Spores for Oral Administration - Langyong Mao; Shantong Jiang; Guohui Li; Yuanqing He; Liang Chen; Qin Yao; Keping Chen (Current Microbiology, 2012)

Monocyte to macrophage differentiation-associated (MMD) positively regulates ERK and Akt activation and TNF-α and NO production in macrophages - Qiang Liu; Jin Zheng; Dan-Dan Yin; Jie Xiang; Fei He; Yao-Chun Wang; Liang Liang; Hong-Yan Qin; Li Liu; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2012)

An integrated genetic linkage map of cultivated peanut (Arachis hypogaea L.) constructed from two RIL populations - Hongde Qin; Suping Feng; Charles Chen; Yufang Guo; Steven Knapp; Albert Culbreath; Guohao He; Ming Li Wang; Xinyou Zhang; C. Corley Holbrook; Peggy Ozias-Akins; Baozhu Guo (Theoretical and Applied Genetics, 2012)

Effects of applied urea and straw on various nitrogen fractions in two Chinese paddy soils with differing clay mineralogy - Shao-Jun Qiu; Pei-Qin Peng; Ling Li; Ping He; Qiang Liu; Jin-Shui Wu; Peter Christie; Xiao-Tang Ju (Biology and Fertility of Soils, 2012)

The mechanism of mimecan transcription induced by glucocorticoid in pituitary corticotroph cells - Xiao Na Zhang; Li Qiong Xue; He Jiang; Shao Ying Yang; Huai Dong Song; Qin Yun Ma (Molecular and Cellular Biochemistry, 2012)

Positive association between NTNG1 and schizophrenia in Chinese Han population - YUZHANG ZHU; HUAN YANG; YUXIA BI; YING ZHANG; CHAO ZHEN; SHOUFU XIE; HEPING QIN; JIA HE; LI LIU; YING LIU (Journal of Genetics, 2011)

Expression analysis of Bombyx mori parvo-like virus VD2-ORF1 gene encoding a minor structural protein - Jie Kong; Zhaogyang Hu; Yuanqing He; Guohui Li; Jian Cao; Fenghua Wang; Keping Chen; Qin Yao (Biologia, 2011)

The Non-Structural Protein NS-2 of Bombyx mori Parvo-like Virus is Localized to the Nuclear Membrane - Fenghua Wang; Zhaoyang Hu; Yuanqing He; Guohui Li; Jie Kong; Jian Cao; Keping Chen; Qin Yao (Current Microbiology, 2011)

Inhibition of Hydrogen Sulfide Generation Contributes to 1-Methy-4-Phenylpyridinium Ion-Induced Neurotoxicity - Xiao-Qing Tang; Li-Li Fan; Yu-Juan Li; Xin-Tian Shen; Yuan-Yuan Zhuan; Jian-Qin He; Jin-Hua Xu; Bi Hu; Yuan-Jian Li (Neurotoxicity Research, 2011)

Fungistatic Intensity of Agricultural Soil Against Fungal Agents and Phylogenetic Analysis on the Actinobacteria Involved - Li Zhi Fang; Xu Chuan Kun; Zou Chang Song; Xi Jia Qin; He Yue Qiu; Duan Chang Qun; Mo Ming He (Current Microbiology, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Association of Apolipoprotein M Gene Polymorphisms with Ischemic Stroke in a Han Chinese Population - Dongxue Zhao; Zhiyi He; Xue Qin; Lei Li; Fang Liu; Shumin Deng (Journal of Molecular Neuroscience, 2011)

Chemical-protein interactome and its application in off-target identification - Lun Yang; Ke-Jian Wang; Li-Shan Wang; Anil G. Jegga; Sheng-Ying Qin; Guang He; Jian Chen; Yue Xiao; Lin He (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Bacillus hunanensis sp. nov., a slightly halophilic bacterium isolated from non-saline forest soil - Yi-Guang Chen; Di-Fei Hao; Qi-Hui Chen; Yu-Qin Zhang; Jian-Ben Liu; Jian-Wu He; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Isolation and characterization of a thermostable cellulase-producing Fusarium chlamydosporum - Yongling Qin; Haiyan He; Nan Li; Min Ling; Zhiqun Liang (World Journal of Microbiology and Biotechnology, 2010)

Stress responsive gene CIPK14 is involved in phytochrome A-mediated far-red light inhibition of greening in Arabidopsis - YuZhi Qin; Ming Guo; Xu Li; XingYao Xiong; ChangZheng He; XianZhou Nie; XuanMing Liu (Science China Life Sciences, 2010)

Elevation of PTH and PTHrp Induced by Excessive Fluoride in Rats on a Calcium-deficient Diet - Hui Xu; Qin-yi Liu; Jing-min Zhang; He Zhang; Guang-sheng Li (Biological Trace Element Research, 2010)

Yaniella soli sp. nov., a new actinobacterium isolated from non-saline forest soil in China - Yi-Guang Chen; Jun Chen; Qi-Hui Chen; Shu-Kun Tang; Yu-Qin Zhang; Jian-Wu He; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2010)

Characterization of an Alien Chromosome of Oryza officinalis Transferred the Genomic and Cytological Environment of Oryza sativa - Gang Li; Ming Tang; Wei Hu; Guangcun He; Hong Liu; Xuequn Liu; Rui Qin (Journal of Plant Biology, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Antioxidative responses related to H2O2 depletion in Hypnum plumaeforme under the combined stress induced by Pb and Ni - Shou-Qin Sun; Ming He; Tong Cao; Yusufujiang Yusuyin; Wei Han; Jin-Ling Li (Environmental Monitoring and Assessment, 2010)

Retinoid X receptor agonists inhibit phorbol-12-myristate-13-acetate (PMA)-induced differentiation of monocytic THP-1 cells into macrophages - Lei Zhou; Ling-hong Shen; Liu-hua Hu; Heng Ge; Jun Pu; Da-jun Chai; Qin Shao; Li Wang; Jin-zhang Zeng; Ben He (Molecular and Cellular Biochemistry, 2010)

Characterization of Bombyx mori parvo-like virus non-structural protein NS1 - Guohui Li; Chen Sun; Junhong Zhang; Yuanqing He; Huiqing Chen; Jie Kong; Guoping Huang; Keping Chen; Qin Yao (Virus Genes, 2009)

Chronic effects of perfluorooctanesulfonate exposure on immunotoxicity in adult male C57BL/6 mice - Guang-Hui Dong; Ying-Hua Zhang; Li Zheng; Wei Liu; Yi-He Jin; Qin-Cheng He (Archives of Toxicology, 2009)

Immunotoxic changes associated with a 7-day oral exposure to perfluorooctanesulfonate (PFOS) in adult male C57BL/6 mice - Li Zheng; Guang-Hui Dong; Yi-He Jin; Qin-Cheng He (Archives of Toxicology, 2009)

Differential belowground allelopathic effects of leaf and root of Mikania micrantha - Ai-Ping Wu; Hua Yu; Shu-Qin Gao; Zhen-Ying Huang; Wei-Ming He; Shi-Li Miao; Ming Dong (Trees, 2009)

Transformation of sugarcane with ACC oxidase antisense gene - Ai-Qin Wang; Wei-Qing Dong; Yuan-Wen Wei; Cheng-Mei Huang; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2009)

Simple sequence repeat analyses of interspecific hybrids and MAALs of Oryza officinalis and Oryza sativa - Gang Li; Wei Hu; Rui Qin; Huajun Jin; Guangxuan Tan; Lili Zhu; Guangcun He (Genetica, 2008)

Molecular cloning and tissue specific expression of an elongation factor 1A gene in sugarcane stalks - Ai-Qin Wang; Ying-Zhi Qin; Xing-Zhi Ye; Ye-Geng Fan; Long-Fei He; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2008)

Retention capacities of several bryophytes for Hg(II) with special reference to the elevation and morphology of moss growth - Shou-Qin Sun; Ding-Yong Wang; Ming He; Xian-Yuan Li; Cheng Zhang (Environmental Monitoring and Assessment, 2007)

Cloning and functional characterization of PpDBF1 gene encoding a DRE-binding transcription factor from Physcomitrella patens - Ning Liu; Nai-Qin Zhong; Gui-Ling Wang; Li-Juan Li; Xiang-Lin Liu; Yi-Kun He; Gui-Xian Xia (Planta, 2007)

Optimization of wheat co-transformation procedure with gene cassettes resulted in an improvement in transformation frequency - Qin Yao; Ling Cong; Guangyuan He; Junli Chang; Kexiu Li; Guangxiao Yang (Molecular Biology Reports, 2007)

Cloning of three members of acc synthase gene family in sugarcane - Ai-Qin Wang; Li-Tao Yang; Zi-Zhang Wang; Yu-Tuo Wei; Long-Fei He; Yang-Rui Li (Sugar Tech, 2006)

An optimal pooling strategy applied to high-throughput screening for rare marker-free transformants - Jinrui Zhang; Qin Xiao; Kexiu Li; Mingjie Chen; Junli Chang; Liting Luo; Yang Li; Yong Liu; Peter R. Shewry; Guangyuan He (Biotechnology Letters, 2006)

Synergistic promotion of gibberellin and cytokinin on direct regeneration of floral buds from in vitro cultures of sepal segments in sinningia speciosa hiern - Ji-Liang Pang; Li-Lin Wang; Jiang-Qin Hu; Tai-He Xiang; Hai-Man Liang (In Vitro Cellular & Developmental Biology - Plant, 2006)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

Detection of Two Fungal Biocontrol Agents against Root-knot Nematodes by RAPD Markers - Ming Liang Zhu; Ming He Mo; Zhen Yuan Xia; Yun Hua Li; Shu Jun Yang; Tian Fei Li; Ke Qin Zhang (Mycopathologia, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Development of a Latex Agglutination Test Using The Major Epitope Domain of Glycoprotein E of Pseudorabies Virus Expressed in E. coli to Differentiate Between Immune Responses in Pigs Naturally Infected or Vaccinated with Pseudorabies Virus - Tang Yong; Chen Huan-chun; Xiao Shao-bo; Qin Ya-li; He Qi-gai; Ren Yu-qi (Veterinary Research Communications, 2005)

Vitreoscilla hemoglobin overexpression increases submergence tolerance in cabbage - Xian Li; Ri-He Peng; Hui-Qin Fan; Ai-Sheng Xiong; Quan-Hong Yao; Zong-Ming Cheng; Yi Li (Plant Cell Reports, 2005)

Different effects on ACC oxidase gene silencing triggered by RNA interference in transgenic tomato - Ai-Sheng Xiong; Quan-Hong Yao; Ri-He Peng; Xian Li; Pei-Lai Han; Hui-Qin Fan (Plant Cell Reports, 2005)

Variations of stomatal density and carbon isotope values of Picea crassifolia at different altitudes in the Qilian Mountains - Wei-ya Qiang; Xun-ling Wang; Tuo Chen; Hu-yuan Feng; Li-zhe An; Yuan-qin He; Gang Wang (Trees, 2003)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)

Information gain in prospect assessment by using basin modeling - Ruozhe Qin; Yanhui Li; Yongmei He (Natural Resources Research, 1997)